Sorghum can fully replace corn in diets for juvenile Nile tilapia - Milene Santos da Silva; Cherlle Kally Lima de Almeida; Luiz Felipe Pomes Bernardino; Janilson Felix da Silva; Seldon Almeida de Souza; Diego Lima Medeiros; Carlos Eduardo Copatti; Luiz Vitor Oliveira Vidal (Aquaculture, 2027)

Beyond metabolism: towards a Dynamic Endocrine Framework for Eating Behaviour under Gender-Affirming Hormone Therapy - Felipe de Souza Cardoso; Elaine Cristina de Souza Lima (Appetite, 2026)

The 2′-α-Fluoro,2′-β-Bromo uridine phosphoramidate prodrug (2-BFU) reduces dengue virus replication and attenuates infection-induced thrombocytopenia In Vivo - Angélica Samer Lallo Dias; Felipe Rocha da Silva Santos; Jenniffer Ramos Martins; Viviane Lima Batista; Talita Cristina Martins da Fonseca; Leticia Pereira Soldati; Celso Martins Queiroz-Junior; Franck Amblard; Raymond F. Schinazi; Mauro Martins Teixeira; Vivian Vasconcelos Costa (Medical Microbiology and Immunology, 2026)
Dengue virus (DENV) infection remains a major global health concern, with clinical manifestations ranging from mild febrile illness to severe, life-threatening complications. In the absence of specific antiviral therapies, the development of novel treatment strategies is crucial. This study evaluates the in vivo antiviral efficacy of 2-BFU, a 2′-α-fluoro,2′-β-bromouridine monophosphate prodrug, in a murine model of DENV Serotype 2 (DENV-2) infection. Adult A129 mice were infected subcutaneously with DENV-2 and treated intraperitoneally with 2-BFU at 15 mg/kg, starting 12 h post-infection. Treatment with 2-BFU significantly reduced viral titers in plasma, spleen, and liver, demonstrating potent antiviral activity. Moreover, 2-BFU effectively attenuated DENV-2 -induced thrombocytopenia at 72- and 120-h post-infection. However, the treatment did not significantly affect the production of inflammatory mediators, nor did it prevent infection-associated weight loss or mortality. These findings suggest that 2-BFU holds promise as an antiviral candidate by lowering viral burden and ameliorating thrombocytopenia, although it may require adjunctive anti-inflammatory strategies to improve overall clinical outcomes. Further investigation is warranted to optimize its therapeutic potential for dengue.

Genome-wide association study identifies novel and confirms established loci associated with serum lipids levels in Brazilians - Larissa Siqueira Penna; Raphael Bruno Amemiya; Isabela Archanjo Nunez; Ágnis Iohana de Souza Grefenhagen; Vinicius Sousa Flores; Maria Vitoria Lima Oliveira; Liriel Almodobar; Jessica Honorato Mauer; Felipe Aristides Simão Neto; Ricardo di Lazzaro Filho; Guilherme Lopes Yamamoto (Human Genetics, 2026)

Fecal virome of paraguayan hairy dwarf porcupine (Coendou spinosus, Cuvier, 1823) in Rio de Janeiro, Brazil - Thamiris dos Santos Miranda; Matheus Augusto Calvano Cosentino; Filipe Romero Rebello Moreira; Francine Bittencourt Schiffler; Amanda Coimbra; Ricardo Mouta; Gabriel Medeiros; Déa Luiza Girardi; Victor Wanderkoke; Monique Lima; Thiago Henrique de Oliveira; Talitha Mayumi Francisco; et al. (Brazilian Journal of Microbiology, 2026)
The Paraguayan hairy dwarf porcupine ( Coendou spinosus , Cuvier, 1823) is a rodent species (Rodentia, Erethizontidae) widely distributed in the Brazilian Atlantic forest. However, little is known about their viral diversity. In this study, we aimed to evaluate, using high-throughput sequencing (HTS), the virome of the feces of seven healthy adult free-living porcupines from Silva Jardim, Rio de Janeiro, Brazil. Total viral nucleic acid was extracted and used for the library preparation for HTS using the Illumina MiSeq platform. The bioinformatics pipeline included quality control, with taxonomic assignments by Kraken2 and Diamond. Unclassified RNA viruses were investigated for viral genome characterization. A total of 41 viral families were classified, of which only seven were validated by both taxonomic analysis tools, including bacteriophages, vertebrate viruses, and unclassified RNA viruses. The most abundant bacterial reads identified belonged to the phylum Proteobacteria. In addition, in-depth analyses of RNA viruses revealed the presence of the Tombusviridae family, a group of plant-infecting viruses possibly associated with the host’s diet. This study provides new insights into the fecal virome of Paraguayan hairy dwarf porcupines, contributing to the knowledge of microbial diversity in Erethizontidae and supporting non-invasive virome studies in wildlife.

Automotive gasoline-induced epigenetic modifications and genotoxic effects in occupationally exposed workers - Paula Vieira Baptista da Silva; Marcia Sarpa; Ubirani Barros Otero; Katia Soares da Poça; André Luiz da Silva Christianes; Isabela Giardini; Barbara Rodrigues Geraldino; Luis Felipe Ribeiro Pinto; Sheila Coelho Soares-Lima (Toxicology, 2026)

Anti-inflammatory and antinociceptive properties of Handroanthus heptaphyllus (Vell.) Mattos hydroethanolic extract bark in mice - Joyce dos Santos Lencina; Paloma Kênia de Moraes Berenguel Losavaro; Dalila dos Santos Lencina; Gabriel Silvino de Oliveira Venâncio; Mila Marluce Lima Fernandes; Josyelen Lousada Felipe; Iluska Senna Bonfá; Lucas Luiz Machado; Djacelli Sampaio de Oliveira Dembogurski; Kamylla Fernanda Souza de Souza; Edgar Julian Paredes-Gamero; Flávio Macedo Alves; et al. (Regulatory Toxicology and Pharmacology, 2026)

Short-term air exposure triggers redox metabolic shifts in the reef-building coral Pavona cactus - Luiza de Castro Mastrangelo Dias; Marina Minari; Carol Cristina Vágula de Almeida Silva; Beatriz Rodrigues Guarinão; Luís Felipe Barcena Albertoni; Lucas do Nascimento Lima; Daniel C. Moreira; Marcelo Hermes-Lima; Helen Sadauskas-Henrique (Journal of Experimental Marine Biology and Ecology, 2026)

DNA detection of Babesia bovis in sheep, ticks and cattle during an outbreak of sheep ixodidiosis by Rhipicephalus microplus - Basílio Felizardo Lima Neto; Samira Pereira Batista; Felipe Boniedj Ventura Alvares; Ygo Santos Monteiro; Maria Lindervânia Pajeú Silva; Helvécio Evandro Castro Martins; Welitânia Inácia Silva; Gláucia Diojânia Azevedo Medeiros; Thais Ferreira Feitosa; Tatiane Rodrigues Silva; Vinícius Longo Ribeiro Vilela (Veterinary Parasitology, 2026)

From printability to food performance: A critical framework for advancing 3D food printing toward scalable food systems - Felipe Veríssimo de Lima; José Diogo da Rocha Viana; Paulo Henrique Machado de Sousa; Elisabeth Mary Cunha da Silva (Trends in Food Science & Technology, 2026)

Predictive and interpretable modeling of naphthenic acid removal by cellulosic adsorbents: Random seed effect, normalization, and SHAP analysis - Ana Carolina Ferreira Piazzi Fuhr; Lauren M.M. Machado; Chong Liu; Jandira Leichtweis; Liliana P. Lozano; Luis Felipe Oliveira Silva; Eder Claudio Lima; Guilherme Luiz Dotto (Journal of Environmental Chemical Engineering, 2026)

Phenolic profile, gastrointestinal behavior and bioaccessibility of Victoria amazonica leaves and petioles using in vitro and in silico approaches. - Clara Prestes Ferreira; Matheus da Costa de Lima; Juliana Guimarães da Silva; Henrique Silvano Arruda; Felipe Tecchio Borsoi; Glaucia Maria Pastore; Gustavo Araújo Pereira; Johnatt Allan Rocha de Oliveira; Nayara Macêdo Peixoto Araújo (Food Research International, 2026)

Anatomopathological aspects of osteoarticular lesions associated with Rhodococcus equi infection in two foals - Felipe Martins Pastor; Suzyane Oliveira Barros; Letícia Fernandes Campos; Acácia Eduarda de Jesus Nascimento; Gabriel Henrique Guimarães; Carlos Renato de Souza Guimarães Filho; Luis Ernesto Campos Torres; Pâmela Aparecida de Lima; Andressa Batista da Silveira Xavier; Rodrigo Otávio Silveira Silva; Roberto Maurício Carvalho Guedes; Rogéria Serakides; et al. (Veterinary Research Communications, 2026)
Rhodococcus equi is an important bacterium that affects foals up to six months of age, especially those that are immunocompromised. The main manifestation is pyogranulomatous pneumonia; nevertheless, extrapulmonary lesions have not only been reported, but are not uncommon, including arthritis and osteomyelitis. Despite the widespread occurrence of rhodococcosis, the macro- and microscopic lesions in the musculoskeletal system are still poorly understood, and a detailed study is needed to better understand the pathogenic potential of the organism. The aim of this report is to present the anatomopathological aspects of bone and joint lesions associated with Rhodococcus equi in two foals. The first case was a two-month-old male Quarter Horse foal with suspected cervical trauma. This horse was admitted in lateral recumbency, semi-comatose, and with atlantoaxial region enlarged. Necropsy revealed atlantooccipital arthritis with pyogranulomatous osteomyelitis, resulting in pathologic fractures of the atlas. There was also pyogranulomatous pachymeningitis leading to compressive myelopathy. In the second case, a two-month-old Brazilian Sport Horse foal presented with lameness of the left pelvic limb and enlargement of the left femorotibial and femoropatellar and right scapulohumeral joints. Necropsy revealed femorotibial and femoropatellar arthritis and purulent osteomyelitis in the femur, as well as extensive necrosis and bone rarefaction with focal detachment of the epiphyseal plate. Both animals had pyogranulomatous pneumonia and lymphadenitis with extracellular and intracytoplasmic gram-positive coccobacilli in neutrophils and macrophages. In the first case, R. equi was isolated and confirmed by MALDI-TOF. R. equi infection should be considered in the differential diagnosis of osteoarticular lesions in foals.

The Missing Branches of the Bee Tree of Life: Addressing Global Darwinian Shortfalls and Their Drivers - Felipe Walter Pereira; Matheus Lima Araujo; Anderson Lepeco; Bruno Ferreira Marques; Hugo Bampi; Lucas Jardim; Luísa Vareira; Luisa G. Carvalheiro; Thiago F. Rangel; José Alexandre F. Diniz Filho (Journal of Biogeography, 2026)
Aim Estimate the Darwinian shortfall (i.e., the lack of knowledge about phylogenetic relationships) of bees worldwide, as well as identify their drivers. Location Global. Taxon Bees (Hymenoptera, Anthophila). Methods We built phylogenies for over 12,000 bee species, combining the most comprehensive phylogeny and an algorithm with random solutions to insert missing lineages. The Darwinian shortfall was quantified as the Phylogenetic Diversity (PD) deficit, the ratio of inserted branch lengths at the assemblage level. We identified potential ecological and socioeconomic drivers of the Darwinian shortfall using Simultaneous Autoregressive (SAR) models. Results The highest shortfalls were identified in the Southern Hemisphere. Mean species range size and species richness were the strongest drivers, as smaller ranges and higher richness were associated with higher deficits. Per capita GDP was negatively associated with PD deficits, while population and road densities showed positive but weak effects. Sample completeness had a weaker effect, limited by missing occurrence data in many regions. Main Conclusions Our findings underscore the need for integrative efforts combining taxonomy, data digitization, adequate research investments, and targeted sampling, especially in the Global South. Overcoming the Darwinian shortfall is essential to develop robust strategies to preserve the Tree of Life, especially for one of the most important groups of pollinators while facing the ongoing biodiversity crisis.

Venom characterization and structural insights into phospholipase D isoforms from the spider Loxosceles aff. variegata - Ana Luiza Silva-Araújo; Rafaela Silva-Magalhães; Pamella Peres-Damásio; Elaine Henriques Teixeira Pereira; Ramon de Oliveira Souza; Luana Silveira da Rocha Nowicki Varela; Luiz Marcelo Ribeiro Tomé; Felipe Campos de Melo Iani; Adriano Lima Silveira; Márcia Helena Borges; Raíssa Medina-Santos; Carlos Chavez-Olórtegui; et al. (Toxicon, 2026)

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Cover crops shape soil microbiome and ecological interactions in the soybean rhizosphere under long-term no-till - Caio César Gomes Freitas; Carolinne Rosa de Carvalho; Nariane de Andrade; Rafael Lima Oliveira; Victor Lucas Vieira Prudêncio Araújo; Felipe Martins do Rêgo Barros; João Henrique dos Santos Ferreira; José Roberto Portugal; Carlos Alexandre Costa Crusciol; Fernando Dini Andreote (Soil and Tillage Research, 2026)

Effect of addition of nicotinamide and cholesterol before cryopreservation on the quality of sheep semen and its fertilizing potential - Beatriz Cavalcanti de Freitas; Edilson Soares Lopes Júnior; Elenice Andrade Moraes; Davi Felipe Soares Coelho; Jairo José da Silva Santos; Mabel Freitas Cordeiro; Rafael Soares dos Anjos; Érika Karoline de Oliveira Aureliano; Andreza Mayara Carneiro Lima; Bruna Moura Silva; Guilherme Rocha Moreira; Pedro Humberto Félix de Sousa (Reproductive Biology, 2026)

The alginate-carrageenan blend exhibits good printability and supports adhesion of ovarian stromal cells in bioprinted scaffolds - Solano Dantas Martins; Iana Lira Nogueira; Maria Alice Felipe Oliveira; Pedro Everson Alexandre De Aquino; Marjory Lima Holanda Araújo; Vânia Marilande Ceccatto; Valdevane Rocha Araújo (Reproductive Biology, 2026)

Intramolluscan alterations of sporocysts induced by sublethal concentrations of Bauhinia monandra protein fraction in the Biomphalaria glabrata–Schistosoma mansoni interaction - Thierry Wesley de Albuquerque Aguiar; Kennya Hevellyn Martins de Souza; Silvio Assis de Oliveira Ferreira; Lucas Andrade Oliveira Cavalcante; Wilza Wanessa Melo França; João Victor Ritinto da Rocha; Thaynara Maria Arantes; Dewson Rocha Pereira; Rafael Xavier Martins; Davi Felipe Farias; Ana Maria Mendonça de Albuquerque Melo; Hallysson Douglas Andrade de Araújo; et al. (Journal of Invertebrate Pathology, 2026)

Corrigendum to "Phenolic profile, gastrointestinal behavior and bioaccessibility of Victoria amazonica leaves and petioles using in vitro and in silico approaches" [Food Res. Int. 242 (2026) 119830] - Clara Prestes Ferreira; Matheus da Costa de Lima; Juliana Guimarães da Silva; Henrique Silvano Arruda; Felipe Tecchio Borsoi; Glaucia Maria Pastore; Gustavo Araujo Pereira; Johnatt Allan Rocha de Oliveira; Nayara Macêdo Peixoto Araujo (Food Research International, 2026)

Experimental gasification of glycerol-impregnated eucalyptus biomass for hydrogen-rich syngas - Daniela Araújo Costa; Marcos Fábio de Jesus; Felipe Lima de Araújo; Felipe Andrade Torres; Delano Mendes de Santana; Silvio A.B.V. de Melo; Francisco Jarmeson Silva Bandeira; Ednildo Andrade Torres (Biomass and Bioenergy, 2026)

Assessing oceans’ health through biopsy sampling in free-ranging marine mammals: a systematic review (2014–2024) - Suelen Goulart; Giulia Galani; Lucas Fazardo de Lima; Isadora Nicole Lara Piccinin; Felipe da Silva Valente; Aline Nunes; Eduardo Pires Renault-Braga; Marcelo Maraschin (Environmental Science and Pollution Research, 2026)

Sex-dependent responses to moderate/low-intensity swimming and loaded ladder-climbing resistance exercise in mdx mice - Luana Lima Rocha da Silva; Tabata Gabriely Pereira Barbosa de Souza; Joice Luiza Silva Cassini; Beatriz Godinho Nascimento; Luis Felipe Cunha dos Reis; Thaís de Sousa Máximo; Túlio de Almeida Hermes (Journal of Muscle Research and Cell Motility, 2026)
Duchenne muscular dystrophy (DMD) is a severe genetic disorder characterized by progressive muscle degeneration, and the mdx mouse has been widely used to investigate disease mechanisms and therapeutic strategies, including the impact of different exercise modalities and sex-related responses on dystrophic muscle. This study compared moderate/low-intensity swimming and loaded ladder-climbing in male and female mdx, including sedentary control groups for each sex. Animals were subjected to a 4-week swimming (30 min/day, 4 days/week) or a 15-day ladder-climbing resistance protocol (6 sessions, 3 sets of 10 climbs, every 48 h), starting at 30 and 45 days of age, respectively. All groups (male and female sedentary controls, swimming, and resistance-trained mice) were evaluated at 60 days of age. In male mdx mice, swimming reduced serum creatine kinase levels and improved limb functional performance compared to sedentary controls. In contrast, resistance exercise increased diaphragmatic fibrosis and reduced centrally nucleated fibers in biceps brachii in male mdx mice. Resistance-trained males also exhibited lower holding impulse compared to swimming-trained males. Females exhibited a milder response, with superior fatigue resistance, greater mechanical work during climbing, and superior final holding impulse compared to males. These findings demonstrate that exercise outcomes in mdx mice depend strongly on modality, intensity, and sex. Swimming provided functional benefits, while ladder-climbing induced measurable but controlled muscle adaptations, without consistent evidence of widespread damage.

Integrated crop-livestock systems with crop diversification increase soil C and N levels and stocks in subtropical paddy fields in Brazil - Robson Bosa dos Reis; Jakeline Rosa de Oliveira; Cláudia Liane Rodrigues de Lima; Pablo Gerzson Badinelli; Júlio Kuhn da Trindade; Felipe de Campos Carmona; Rogério Oliveira de Sousa; Ibanor Anghinoni; Paulo Cesar de Faccio Carvalho; Amanda Posselt Martins; Cimélio Bayer; Filipe Selau Carlos (Agriculture, Ecosystems & Environment, 2026)

Checklist of Orchidaceae From Brazilian Amazon Restingas - Deivid Lucas de Lima da Costa; Felipe Fajardo Villela Antolin Barberena (New Zealand Journal of Botany, 2026)
In Brazil, restingas (coastal sandbank vegetation) are distributed along the coast in the Atlantic Forest, Caatinga, Cerrado, and Amazon phytogeographic domains. Orchidaceae is one of the botanical families with the greatest species richness in restingas in the Atlantic Forest but has been poorly documented in Amazonian restingas , resulting in limited knowledge in these environments. Thus, the aim of this study was to present a checklist of Orchidaceae from Brazilian Amazon restingas . We consulted herbaria, reviewed the literature, and carried out field collections on the coast of the Salgado microregion in the state of Pará. Twelve genera and 20 species of Orchidaceae were found. Two species are endemic to Brazil, and nine are new records for the study area. Orchidaceae occur in four phytophysiognomies: restinga forest (10 species, five exclusive), open thicket formation (8 spp.), dune field (7 spp., three exclusive), and herbaceous marsh (2 spp.). Eleven species were exclusively terrestrial, six exclusively epiphytes, two epiphytes and terrestrial, and one species was a nomadic climber. Future studies should investigate the ecological relationships between epiphytic orchids and their phorophytes in Amazonian restingas because these relationships have shown to be fundamental in restingas in the Atlantic Forest.

A mechanistic approach about oxidative, mutagenic, and cytotoxic effects of an organotellurane - Felipe Emannuel Alvino de Jesus; Octávio Augusto de Carvalho Maia; Antonielly Campinho dos Reis; Audinei de Sousa Moura; Anderson Nogueira Mendes; Glissia Lysandra dos Santos Marciel; Jefferson da Cruz Esteves; Shamya Gabriella Corrêa Coêlho; Isabela Ribeiro de Sá Guimarães Nolêto; Maria Luísa Lima Barreto do Nascimento; Adriana Maria Viana Nunes; Débora Caroline do Nascimento Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Organotellurium (OTe) compounds have pharmacological properties, including leishmanicidal, antimalarial, and antifungal activities. Herein, we assessed cytotoxicity effects of OTe RF07 in a panel of tumor cell lines, as well as its oxidative, toxicity, and hemolytic actions. The toxicity was evaluated on Allium cepa and Artemia salina larvae. Cell viability was also assessed by resazurin in murine cells (Sarcoma 180), human cells (HL-60, leukemia; AGP01, gastric adenocarcinoma; SKMEL-28, human melanoma; MRC-5, normal fibroblasts), and dog erythrocytes. The oxidative capacity of RF07 was evaluated by wild-type and antioxidant-mutated enzyme strains of Saccharomyces cerevisiae . RF07 presented cytotoxic action on all normal and tumor cells, whose IC 50 ranged from 0.07 μg/mL (HL-60) to 73.45 μg/mL (Sarcoma 180) and toxicological activity on A. salina nauplii in a concentration-dependent manner after exposure for 24 h and 48 h (LC 50 values of 15.02 and 5.43 μg/mL for 24 h and 48 h, respectively). Moreover, RF07 reduced mitotic index of meristematic A. cepa cells at 5, 10 and 20 μg/mL, caused arrest in interphase, and increased chromosomal changes, including micronucleus, c -metaphases, and chromosomal bridges, loss, and delays. In summary, RF07 exhibits antiproliferative action on animal cells, high toxicity on Artemia salina nauplii, as well as clastogenic effects on growing roots. This antimitotic action is not related to direct membrane damage, although it relies on chromosomal injuries and may be related to the induction of oxidative stress as observed in yeast cells.

Correction: Lightning Behavior and Its Relationship with Topography, Precipitation, and Land Use in the São Francisco River Basin - Samuel Amorim Silva; Weber Andrade Gonçalves; Lizando Pereira de Abreu; Douglas Leonardo Sales Pedrosa; Evandro Moimaz Anselmo; Enrique Vieira Mattos; Moisés Elias Nascimento Rufino da Costa; Glenda Yasmin Pereira de Carvalho; Bruno Felipe Moreira Lima; Daniele Tôrres Rodrigues; Vitória Régia Silva de Souza; Thiago Gonçalves da Silva (Pure and Applied Geophysics, 2026)

Rhizosphere organic acids drive nutrient release from silicate rock powders across contrasting tropical soils - Rafael Lima Oliveira; Nariane de Andrade; Caio César Gomes Freitas; Danilo Ferreira da Silva; Felipe Martins do Rêgo Barros; Mísia Souza Vieira; Rafael Santana Mendonça; Felipe Gabriel Andrino; Amanda Manuelly da Silva Oliveira; Antonio Carlos de Azevedo; Simone Possedente de Lira; Fernando Dini Andreote (Plant and Soil, 2026)
Aims Silicate rock powders can enhance nutrient availability through rhizosphere-mediated mineral weathering. Although organic acids mediate this process, how soil fertility shapes their interactions with rhizosphere microbial communities and nutrient release remains poorly understood. He, we evaluated how contrasting soil fertility influences rhizosphere organic acids, microbial communities, and nutrient release from silicate rock powders in tropical soils. Methods A 10-month greenhouse experiment was conducted with Urochloa brizantha cv. Marandu grown in low- and high-fertility tropical soils amended with phonolite, diabase, or granite. Rhizosphere organic acids, soil chemistry, plant nutrient uptake, and bacterial and fungal communities were assessed using chemical analyses, high-throughput DNA sequencing, and partial least squares path modeling. Results In low-fertility soil, rock powder reshaped rhizosphere organic acid profiles, increasing their concentrations and improving soil fertility. Organic acids were positively associated with soil fertility indicators and nutrient availability. Path modeling identified organic acids as a central mediator linking rhizosphere biological attributes to improved soil fertility (path coefficient = 0.597, P P P Conclusions Rock powder effectiveness was governed by rhizosphere-mediated processes driven by organic acids, microbial communities, and plant nutrient demand, with the strongest responses occurring in nutrient-limited tropical soils.

Solvent-dependent Sensitization and Photophysical Behavior of IrIII-EuIII Bimetallic Complexes - Felipe S. M. Canisares; Vytor C. Oliveira; Alessandro B. S. Garcia; João Honorato; Javier A. Ellena; Marian R. Davolos; Ana M. Pires; Sergio A. M. Lima (Journal of Fluorescence, 2026)
The photophysical properties of a heterobimetallic Ir III –Eu III complex were investigated in solvents with different polarity, coordinating ability, and vibrational characteristics to elucidate the factors governing Eu III sensitization. Steady-state and time-resolved luminescence measurements revealed that the solvent profoundly influences both the donor-to-acceptor energy-transfer process and the europium-centered emission. The apparent Ir III → Eu III energy-transfer rate constants (k ET ) and donor-to-acceptor energy-transfer efficiencies (η ET ) were estimated from the residual 3 MLCT emission lifetimes (τ q ) of the Ir III –Eu III complex and the corresponding Ir III –Gd III analog (τ u ). The results showed a general tendency toward higher energy-transfer rates and efficiencies in solvents with high polarity, coordinating ability, and free of O–H oscillators, reaching k ET values up to 2.6 × 10 7 s −1 and η ET values up to 90% in DMSO. Solvent polarity was found to indirectly modulate the energy transfer (ET) process by influencing the energies of the excited states and the donor–acceptor electronic coupling. In contrast, protic solvents strongly quenched Eu III emission due to the presence of high-energy O–H oscillators, despite moderate ET efficiencies. Degassing experiments performed in dichloromethane and chloroform demonstrated that dissolved oxygen has only a minor effect on the η ET efficiency. The results reveal a complex interplay between solvent polarity, coordinating ability, donor–acceptor gap, and non-radiative deactivation pathways, providing new insights into the design of efficient d–f heterobimetallic luminescent systems.

Retraction notice to “Collapse of scallop Nodipecten nodosus production in the tropical Southeast Brazil as a possible consequence of global warming and water pollution” [Sci. Total Environ. 904 (2023) 166873] - Cristiane Thompson; Leonardo Bacha; Pedro Henrique C. Paz; Marcelo de Assis Passos Oliveira; Braulio Cherene Vaz Oliveira; Claudia Omachi; Caroline Chueke; Marcela de Lima Hilário; Michele Lima; Luciana Leomil; Thais Felix-Cordeiro; Thalya Lou Cordeiro da Cruz; et al. (Science of The Total Environment, 2026)

Genetic and phenotypic diversity of Platonia insignis in a traditionally managed Amazonian population: implications for sustainable use and conservation - João Marcus Abreu da Silva; José Ribamar Gusmão Araujo; Priscila Marlys Sá Rivas; Sérgio Heitor Sousa Felipe; Amanda Costa Everton; Luis Carlos Ferreira Reis; Arilson de Jesus França Souza; Gabriel de Ribamar Carvalho Sousa; Gabriel Oliveira Lima; Ariadnes Enes Rocha; Thais Roseli Corrêa (Journal for Nature Conservation, 2026)

Processing information alters consumer perception and reduces the blind sensory advantage of ultrasound-treated orange juice: an integrated technological and consumer-based study - Géssica Cristina da Veiga; Débora Pinhatari Ferreira; Isabelli Cristina da Silveira Maia; Felipe Fabris Leite Victorino; Theisa Caroline de Assis; Marcos dos Santos Lima; Arão Cardoso Viana; Carlos Eduardo Barão; Marciane Magnani; Tatiana Colombo Pimentel (Food Bioscience, 2026)

The methanolic extract of Byrsonima intermedia mitigates colonic injury in experimental colitis through redox restoration, cytokine modulation, and tissue repair - Karla Stella Figueiredo Romano; Felipe Leonardo Fagundes; Quélita Cristina Pereira; Maycon Tavares Emílio-Silva; Larissa Lucena Périco; Vinicius Peixoto Rodrigues; Gabriela Bueno; Mateus Magami Yoshitani; Giovana Pacciulli Pereira; José Aires Pereira; Carlos Augusto Real Martinez; Alessandra Gambero; et al. (Inflammopharmacology, 2026)
This study evaluated the anti-inflammatory and antioxidant effects of a methanolic extract of Byrsonima intermedia leaves (EBi) in a rat model of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis. Male Wistar rats received intracolonic TNBS for lesion induction and relapse, followed by oral treatment with EBi for seven days. EBi markedly reduced the severity of colonic injury, as demonstrated by a 63% decrease in macroscopic damage, along with reductions in inflammatory infiltrate (32%) and neutrophil accumulation (52%) compared to the vehicle group. These protective effects were accompanied by significant attenuation of myeloperoxidase (MPO) activity and lipid peroxidation, together with increased superoxide dismutase (SOD) activity and glutathione levels (GSH), indicating restoration of redox homeostasis. EBi also modulated key inflammatory mediators, promoting IL-10 upregulation while downregulating IL-1 β , MCP-1, and TLR4 expression in colonic tissue. Histological analysis confirmed substantial improvement in tissue architecture and inflammatory status. Collectively, these findings demonstrate that B. intermedia exerts multi-target anti-inflammatory and antioxidant actions that contribute to tissue repair in experimental colitis, supporting its potential as a promising natural therapeutic candidate for inflammatory bowel disease. Graphical abstract Multi-target mechanisms underlying the protective effects of Byrsonima intermedia in experimental TNBS-induced colitis. The extract reduces macroscopic lesions, restores redox homeostasis (↑SOD, ↑GSH, ↓MDA, ↓ROS), and modulates key inflammatory mediators (↓IL-1 β , ↓MPO, ↓MCP-1, ↑IL-10), collectively promoting tissue repair and attenuation of intestinal inflammation . Created in BioRender. Pereira, Q. (2025)

Electrochemical strategies for lateral flow and LAMP-Based platforms toward pathogen detection: A critical review - Lucas F. de Lima; Paulo Felipe Neves Estrela; Leonardo Lopes-Luz; Lauro A. Pradela-Filho; Jonatas V. Souza; Daniel Júnior Almeida dos Santos; Gabriela R.M. Duarte; Wendell K.T. Coltro; Thiago R.L.C. Paixão (Analytica Chimica Acta, 2026)

Embryo-fetal and early-life protein restriction programs pulmonary structure and molecular parameters in both dams and female offspring - Flávia Alessandra Maciel; Matheus Naia Fioretto; Luisa Annibal Barata; Isabelle Tenori Ribeiro; Vinícius Alexandre de Andrade Felipe; Lucas Sobrinho Lemos; Maycon Tavares Emílio-Silva; Tainá Dorte da Silva; Flávia Karina Delella; Clélia Akiko Hiruma Lima; Wellerson Rodrigo Scarano; Luis Antonio Justulin (Molecular and Cellular Biochemistry, 2026)
The Developmental Origins of Health and Disease (DOHaD) theory proposes that adverse conditions during critical developmental windows can increase disease susceptibility throughout life. Maternal protein restriction (MPR) is a well-established experimental model that impairs offspring lung development, affecting pulmonary structure, metabolism, and molecular pathways from early life to aging. However, little is known about its effects on maternal pulmonary health and female offspring, representing an important gap in the literature. Therefore, this study investigated the effects of MPR on lung structure and metabolism in dams at the end of lactation and in female offspring at weaning. Sprague Dawley rats were fed either a control diet (17% protein) or a low-protein diet (6% protein) throughout gestation and lactation. Dams and female offspring were euthanized at weaning, and pulmonary alterations were assessed through histological, biochemical, molecular, zymographic, and in silico analyses. MPR increased collagen deposition, mast cell density, and Acta expression, while reducing reticular fibers in maternal lungs, accompanied by a trend toward increased lipid peroxidation. In female offspring, MPR reduced alveolar diameter, mast cell density, and reticular fibers, while increasing collagen deposition, MMP-2 activity, PI3K and MyoD expression, and decreasing mTOR expression as well as Nduf transcript levels. No significant alterations in antioxidant parameters were observed in either dams or offspring. Integrative analyses indicate that MPR promotes structural remodeling in maternal lungs, potentially compromising ventilatory function. In female offspring, MPR induces delayed pulmonary development, extracellular matrix remodeling, alterations in smooth muscle-related pathways, and disturbances in energy metabolism. Together, these findings demonstrate that maternal protein resQ1triction adversely affects pulmonary health in both dams and female offspring, revealing potential mechanisms linking early-life nutritional adversity to the developmental origins of respiratory disease.

Development of citrinin-loaded liposomes and in vitro toxicogenetic evaluation on breast cells - Ag-Anne Pereira Melo de Menezes; Maria Luísa Lima Barreto do Nascimento; Antonielly Campinho dos Reis; Michely Laiany Vieira Moura; Taline Alves Nobre; Athanara Alves de Sousa; Jorddam Almondes Martins; Sérgio Eduardo Matos Cazarotti Francisco; João Pedro Alves Damaceno do Lago; Igor Gabriel Barbosa de Sousa; Helber Alves Negreiros; Marjorie Pereira Gualter; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
This study aimed to synthesize a liposomal nanoformulation containing citrinin (LP-CIT) to improve its availability and to evaluate its toxicogenomic profile, focusing on cytotoxic and genotoxic effects in breast cancer (MDA-MB-231) and non-tumorigenic mammary epithelial (MCF-10A) cell lines. The formulation was characterized by macroscopic appearance, pH, particle size, polydispersity index (PDI), zeta potential, encapsulation efficiency, and estability of nanoparticles. Citrinin content, encapsulation efficiency, and liposome stability were evaluated. Cytotoxicity was assessed using MTT, trypan blue exclusion, and flow cytometry. Cell death mechanisms were investigated by mitochondrial membrane potential analysis and expression of apoptotic markers (caspase-9 and BAX). Genotoxicity was evaluated using the comet assay. The liposomal nanosystem consisted of small unilamellar vesicles with a mean diameter of 143.3 nm, a PDI of 0.3, and a positive surface charge (+ 28.5 mV). The average was 63.69 ± 0.18% of citrinin encapsulated in liposomes with stability more than 21 days. Both free citrinin (CIT) and LP-CIT showed cytotoxic effects in MDA-MB-231 and MCF-10A cells, with lower LC₅₀ values observed for LP-CIT. Although LP-CIT induced more pronounced cytotoxic and genotoxic effects in the cancer cell line, toxic effects were also observed in non-tumorigenic cells, indicating limited selectivity. Cell death was associated with mitochondrial membrane depolarization and increased caspase-9 and BAX expression. Both formulations induced DNA damage as detected by the comet assay. Liposomal encapsulation enhanced citrinin biological activity but did not indicate tumor selectivity. Thus, this study represents a toxicogenomic assessment of citrinin and its liposomal formulation for potential therapeutic applicability.

Lightning Behavior and Its Relationship with Topography, Precipitation, and Land Use in the São Francisco River Basin - Samuel Amorim Silva; Weber Andrade Gonçalves; Lizando Pereira de Abreu; Douglas Leonardo Sales Pedrosa; Evandro Moimaz Anselmo; Enrique Vieira Mattos; Moisés Elias Nascimento Rufino da Costa; Glenda Yasmin Pereira de Carvalho; Bruno Felipe Moreira Lima; Daniele Tôrres Rodrigues; Vitória Régia Silva de Souza; Thiago Gonçalves da Silva (Pure and Applied Geophysics, 2026)
This study quantifies how topographic features influence lightning activity in the São Francisco River Basin, Brazil, filling a critical gap by establishing previously unavailable thresholds. A 16-year climatology (1998–2013) was developed using LIS/TRMM lightning data, ASTER GDEM topography, CHIRPS precipitation, and MapBiomas land use, all standardized to a 0.1° grid. The analysis integrates elevation, slope, aspect, and land use with lightning flash rate density (FRD) and precipitation. Results show a non-linear response of lightning to topography, with a 261.7% increase in FRD above 517.14 m during the dry season, and additional thresholds of 45.4% above 601.96 m (spring) and 24.9% above 583.14 m (summer). Lightning hotspots range from 29.2 to 39.9 flashes km –2 yr –1 , with the maximum value recorded in São Desidério (BA), concentrated in the Western Bahia Plateau (Cluster 04). A seasonal shift is identified, with large-scale thermodynamics dominating in the wet season and topographic forcing controlling lightning activity in the dry season. Ultimately, this study establishes a robust quantitative framework for the terrain–lightning relationship, highlighting zones of elevated risk for expanding agricultural activities in the basin.

Planting trays and cell models impact the growth of pink trumpet tree (Handroanthus heptaphyllus) seedlings in aquaponics systems with tambaqui (Colossoma macropomum) - Priscila Caroline Alves Lopes; Fábio Carneiro Sterzelecki; João Francisco Garcez Cabral Junior; Bruna dos Santos Miranda; Deyselana Lima da Costa; Nuno Felipe Alves Correia De Melo; Marco Shizuo Owatari; Sávio Lucas de Matos Guerreiro; Glauber David Almeida Palheta (Aquaculture International, 2026)

Legacy P from rock phosphate promotes growth of eucalypt coppice stands without further P application - Adam da Cruz Rodrigues; Cassio Rafael Costa dos Santos; Maria Leidiane Reis Barreto; Felipe Tavares Lima; Antonio Leite Florentino; Alexandre de Vicente Ferraz; José Leonardo de Moraes Gonçalves (Forest Ecology and Management, 2026)

Clinical and non-clinical Escherichia coli from chickens reveal antimicrobial resistance patterns of one health concern - Marianna Rodrigues de Souza Campos; Thomas Salles Dias; Verônica Dias Gonçalves; Marcia Lima Festivo; Emily Moraes Roges; André Felipe das Mercês Santos; Pedro Henrique Nunes Panzenhagen; Laura Maria Andrade de Oliveira; Patrícia Carvalho de Sequeira; Dália dos Prazeres Rodrigues; Maria Helena Cosendey de Aquino (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Synthesis and characterization of chitosan-functionalized nanostructured lipid carriers with temozolomide: cytotoxic effects and chromosomal instability in human glioblastoma cells - Helber Alves Negreiros; João Pedro Alves Damaceno do Lago; Victor Alves de Oliveira; Lia Raquel Alves Silva; Ana Carolina Lima de Melo; Igor Gabriel Barbosa de Sousa; Jefferson da Cruz Esteves; Sérgio Eduardo Matos Cazarotti Francisco; Samuel Lemos Paiva; João Pedro Crispim Guerra Rodrigues; Lucas Medeiros Martins Carvalho; Pedro Henricke Oliveira de Souza; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Multiform glioblastoma (GBM) is the most aggressive primary brain tumor, associated with high heterogeneity, treatment resistance, and poor survival. Temozolomide (TMZ), although the main chemotherapeutic agent used, shows limited efficacy due to low solubility, chemical instability, and acquired resistance. In this context, nanostructured systems can enhance their antitumor efficacy. This study aimed to develop and characterize chitosan-functionalized nanostructured lipid carriers loaded with Temozolomide (NLCTQ), as well as to assess their biological activity in human glioblastoma cells (U87-MG). Lipid nanoparticles functionalized with chitosan were prepared by hot emulsification and sonication. Physicochemical characterization included DLS, zeta potential, FTIR, and HPLC for drug quantification and encapsulation efficiency. Biological activity was evaluated in U87-MG cells using the cell viability assay MTT and trypan blue, the comet assay, the spheroid model, fluorescence cell death, and the CBMN assay. The formulation presented a homogeneous nanometric size and positive zeta potential, although with moderate encapsulation efficiency (39%). Biological assays demonstrated that NLCTQ significantly reduced cell viability, overcoming the U87-MG cell line’s resistance to TMZ by achieving cytotoxicity at doses up to 20 times lower than free TMZ. Additionally, NLCTQ promoted the formation of biomarkers of chromosomal instability, such as micronuclei, bridges, and nuclear buds, which may explain the observed cytotoxic effects. Together, the results indicate that TMZ nanoencapsulation in NLCTQ enhances its antitumor efficacy, representing a promising strategy to overcome the limitations of conventional chemotherapy in glioblastoma treatment.

Environmental filtering and spatial structure drive nestedness–turnover dynamics in bivalve mollusk metacommunities in the Atlantic continental margin of South America, Brazil - J. Weverton S. Souza; Silvio Felipe Barbosa Lima; Gustavo Luis Hirose; Adriana Bocchiglieri; Carmen Regina Parisotto Guimarães (Aquatic Sciences, 2026)
Species distributions along environmental gradients may exhibit nestedness, turnover, or clumping patterns. In environments subject to strong environmental variability, such as continental shelves, environmental filters exert a decisive influence on community composition, which may alternate across seasonal periods, leading to temporal variations in the structure and diversity of marine communities. This study aimed to investigate the organizational patterns of the metacommunity at small (north, central, and south sectors) and large spatial scales (continental margin) during two seasonal periods along a depth gradient on the northeastern Brazilian continental margin. Taxonomic α-diversity was higher in the southern sector and during the rainy periods. β-Diversity did not differ among sectors, but species composition exhibited high dissimilarity, particularly between the northern–southern and central–southern sectors, reflecting stronger species turnover during the rainy season, whereas richness differences predominated in the dry period. The metacommunity structure along the environmental gradient was predominantly Gleasonian at smaller spatial scales, with individualistic species responses and gradual shifts in composition, whereas quasi-Clementsian patterns emerged at broader scales, revealing groups of species with similar distributional limits and abrupt compositional changes. The metacommunity was primarily structured by environmental filters, with depth and gravel as the main predictors. Spatial processes had a limited influence and were associated with dispersal limitation, whereas most of the variation remained unexplained by the measured variables. Overall, the results indicate that environmental filtering (depth and gravel) constitutes the primary structuring mechanism, acting in conjunction with large-scale spatial effects associated with dispersal limitation and mass effects acting at smaller-scales.

Association between COVID-19 booster vaccination and influenza mortality: a nationwide retrospective cohort study using the SIVEP-Gripe database in Brazil - Daniele Melo Sardinha; Natália Melazo Machado Neves; Tamires de Nazaré Soares; Marcos Jessé Abrahão Silva; Lidiane Assunção de Vasconcelos; Luany Rafaele da Conceição Cruz; Karina Faine Freitas Takeda; Natasha Cristina Oliveira Andrade; Suziane do Socorro dos Santos; Felipe Costa Soares; Neiva José da Luz Dias Júnior; Yan Corrêa Rodrigues; et al. (Immunologic Research, 2026)
To identify clinical and epidemiological predictors of mortality among patients hospitalized with laboratory-confirmed influenza in Brazil during 2024, and to evaluate the association of vaccination and antiviral therapy with clinical outcomes. We conducted a nationwide retrospective cohort study using the Brazilian SIVEP-Gripe surveillance database. All hospitalized patients with RT-PCR–confirmed influenza and known outcomes were included. Multivariable logistic regression was initially performed to explore predictors of mortality. To more rigorously assess the association between COVID-19 booster vaccination and mortality, a propensity score–based inverse probability of treatment weighting (IPTW) approach was applied, with weights truncated at 10. E-values were calculated to assess robustness to unmeasured confounding. A total of 15,995 hospitalized influenza cases were included, with an overall case fatality rate of 12.1%. Influenza A predominated (88.0%) and was associated with higher mortality than Influenza B. In IPTW-weighted models, COVID-19 booster vaccination remained independently associated with reduced mortality (OR 0.90, 95% CI 0.84–0.97; p = 0.007). Additional risk factors included dyspnea, respiratory distress, and low oxygen saturation, as well as comorbidities such as obesity, diabetes, liver disease, and immunosuppression. Protective factors included influenza vaccination (OR 0.77) and oseltamivir use (OR 0.81). The model demonstrated good discrimination (AUC = 0.81, 95% CI 0.80–0.82). The E-value for the booster association was 1.46, indicating moderate robustness to unmeasured confounding. Influenza mortality in Brazil is primarily driven by age, comorbidities, and clinical severity at presentation, but is significantly mitigated by vaccination and antiviral therapy. The observed association between COVID-19 booster vaccination and reduced mortality suggests a possible heterologous immune effect, although causality cannot be established. These findings support integrated immunization strategies targeting multiple respiratory pathogens.

In vitro salinity priming modulates photosynthetic acclimation in Ananas comosus with limited growth recovery - Vitória K. O. Silva-Moraes; Sérgio H. S. Felipe; Givago L. Alves; Irislene C. Albuquerque; Jordanya F. Pinheiro; Aldilene S. Lima; Priscila M. S. Rivas; Diego S. Batista; Fábio A. M. M. A. Figueiredo; Fabrício O. Reis; Tiago M. Ferraz; Thais R. Corrêa (Vegetos, 2026)

Enhanced methane production from sugarcane bagasse via enzymatic hydrolysis pretreatment: A comparative study of fermentation techniques - Liliana Andréa dos Santos; Leonardo César da Silva; Guilherme Gomes de Sousa Magalhães; Jônatas Carvalho-Silva; Jorge Vinicius Fernandes Lima Cavalcanti; André Felipe de Melo Sales Santos; Tatiana Souza Porto (Journal of Environmental Chemical Engineering, 2026)

Oil spill analysis and simulations in the Foz do Amazonas sedimentary basin - Felipe R. Torres; Syumara Queiroz; Carlos A.D. Lentini; L.F.F. Mendonça; André T. Cunha Lima (Continental Shelf Research, 2026)

Neurotoxic effects of 2,4-DCP in adult zebrafish: A behavioral, biochemical, and genetic approach - Ana Luisa Pires Moreira; Rafael Xavier Martins; Romério de Oliveira Lima Filho; Silvia Regina Batistuzzo de Medeiros; Davi Felipe Farias; Ana Carolina Luchiari; Cícero Francisco Bezerra Felipe (Chemico-Biological Interactions, 2026)

Microbial Taxonomic and Functional Features Involved in Self-Purification of a Brazilian Polluted River - Lina Rocío del Pilar Rada Martinez; Luiz Ricardo Olchanheski; Eliane Gonçalves da Silva; Simone Ichiwaki; Mabel Patricia Ortiz-Vera; Felipe Rezende de Lima; Maria Inês Zanoli Sato; Gabriel Padilla; Welington Luiz Araújo (Water, Air, & Soil Pollution, 2026)
Summary The Tietê River is an anthropogenically disturbed urban water body polluted by a combination of untreated domestic sewage releasing (carbon, nitrogen and phosphorus pollution) and diffuse pollution that cross São Paulo State in Southeast of Brazil. Along its course, it presents contrasting sites showing elevated levels of nutrients and contaminants (eutrophic sites) and oligotrophic environments, in both water and sediments. In this study, we investigated how pollution influences the taxonomic and functional diversity of microbial communities in the Tietê River watershed, with the aim of understanding their role in pollutant transformation during downstream transport. Four sampling sites along a pollution gradient—from São Paulo city to a relatively pristine area near the river mouth—were evaluated. Results indicated that diversity differences were primarily linked to water quality, with higher diversity observed in less contaminated sites. Heterotrophic metabolism was more prominent in polluted regions, whereas photoautotrophic and lithotrophic microorganisms were more abundant in clean areas. Additionally, genes associated with the metabolism of aromatic compounds and virulence factors were more prevalent in environments with higher anthropogenic influence, suggesting a functional shift geared toward environmental adaptation and bioremediation. We propose that, in areas with high organic matter concentrations, microbial communities tend to adopt an r-strategy lifestyle, characterized by rapid growth and reproduction, while in oligotrophic, less polluted sites, more competitive k-strategists predominate. Although the following hypothesis was not extensively studied, the lower abundance of genes involved in secondary metabolic synthesis in eutrophic sites suggests that pollution may reduce the availability of novel species or traits relevant for biotechnological applications. Additionally, community shifts appear to be influenced by "conditionally rare taxa," which temporarily alter their activity and abundance in response to environmental constraints, playing a critical role in water self-purification processes. Overall, these findings offer new insights into the environmental factors driving self-purification in the Tietê River and shed light on the ecological mechanisms underpinning river resilience.

Demonstration of Anaplasma marginale transmission to cattle through the intra-transstadial and by unfed larvae of Rhipicephalus microplus routes, with subsequent calculation of infection rates - Luciana Maffini Heller; Dina María Beltrán Zapa; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Luiz Fellipe Monteiro Couto; Lídia Mendes de Aquino; Lucianne Cardoso Neves; Bianca Barbara Fonseca da Silva; Lorena Lopes Ferreira; Felipe da Silva Krawczak; Caio Marcio de Oliveira Monteiro; et al. (Tropical Animal Health and Production, 2026)
The objective of this study was to assess the infection rate of Anaplasma marginale in cattle by Rhipicephalus microplus . Two experiments were conducted for this purpose. Experiment 1 evaluated the infection rate by the intrastadial and transstadial routes. Calves naturally infected with A. marginale were infested with R. microplus and were called “positive with ticks” (PWT). These PWT animals were housed together with A. marginale -negative, tick-free calves, called “negative and free-tick” (NFT) for 31 consecutive days. On day 31, the PWT animals were removed from the pens and returned to the farm/herd of origin. The NFT animals remained in the pens until day 84, and the possible infection rate of these calves with A. marginale by cattle ticks via the transstadial or intrastadial route was investigated (using blood smears, PCR, and ELISA). During this period, we evaluated the transfer rate of R. microplus from PWT to NFT animals. As a result of Experiment 1, only adult male and female ticks were found on the NFT animals. The transfer rate of ticks from PWTs to NFT calves was 0.10% (31/28464), and 70% (7 of 10), and all the NFT animals housed along with PWT animals became infected by A. marginale. In Experiment 2, the infection rate of A. marginale in calves by R. microplus larvae was carried out in two steps. The first step involved the use of the first tick generation larvae, which were used to infest (at 40,000 larvae per animal) five NFT calves. If any of these five NFT animals became infected with this rickettsia, fully engorged females detached from these animals were collected to perform the second step of the Experiment 2, conducted with the second-generation larvae. The second-generation larvae came from the first generation. Another five NFT calves were infested with 40,000 larvae/animal from the second tick generation. As a result of Experiment 2, 100% of NFT calves were infected by A. marginale due to infestation with R. microplus larvae of the first and second generations. This tick species has epidemiological importance in the transmission of A. marginale to calves by the intra-transstadial or unfed larval route.

Macroptilium chuquisacense (Leguminosae: Papilionoideae): a new species from the Bolivian Chaco - Carolina Lima Ribeiro; Felipe da Silva Santos; Cristiane Snak; Gwilym Peter Lewis; Luciano Paganucci de Queiroz (Kew Bulletin, 2026)
Summary Macroptilium comprises approximately 20 species native to the Americas. Eleven of these have been recorded in Bolivia, representing all three currently recognised sections. This article describes an additional species for the country, Macroptilium chuquisacense . This new species is recorded from Chuquisaca and is currently represented by only two collections, which, morphologically, most closely resemble Macroptilium prostratum . It is primarily distinguished by its lanceolate leaflets with a sericeous indumentum, flowers approximately 6.5 mm long with petals described as lilac and sericeous floral bracts that exceed the length of the buds at the apex of the inflorescence. A detailed morphological description, illustrations, taxonomic notes, distributional data and an identification key to the Bolivian species of Macroptilium are provided.

Analysis of the chemical, physical, and rheological properties of asphalt binder modified with pequi oil for potential application in asphalt mixtures - Marco Aurélio de Teixeira e Lima; Paulo Germano Tavares Marinho Filho; Arthur Felipe de Farias Monteiro; Lara Pereira Tavares Mendes; Sonaly Mendes Arruda; Brenda Maria Barreto de Souza; Leda Christiane de Figueiredo Lopes Lucena; Osires de Medeiros Melo Neto (Innovative Infrastructure Solutions, 2026)

Maternal bovine appeasing substance analog mitigates the effects of excitable temperament on timed artificial insemination outcomes in Nellore cows - Samuel Rodrigues Bonamichi do Couto; Júlia Medeiros Cruz de Lima Martins; Felipe Zandonadi Brandão; Nicolas Moreira Piedras Monnerat Caparelli; Thiago Souza Vieira; João Paulo Nascimento Andrade; Marco Roberto Bourg de Mello (Animal Reproduction Science, 2026)

Complete genome and phylogenetic characterization of a novel papillomavirus from Cuniculus paca in the Brazilian Amazon - Cleyton Silva de Araújo; Laura Gabrielly Alves Henrique; Hanna Gabriela da Silva Oliveira; Jhonatan Henrique Lima da Rocha; Junio Damasceno de Souza¹; Agnes de Souza Lima; Vania Maria França Ribeiro; Francisco Carlos da Silva; David Driemeier; Cláudio Wageck Canal; John Munday; Felipe Masiero Salvarani; et al. (Archives of Virology, 2026)

Integrative taxonomy reveals two new species of whiptail catfishes Loricaria (Siluriformes: Loricariidae) from northeastern Brazil - Ananda. C. Serejo‐Saraiva; Nivaldo M. Piorski; Felipe P. Ottoni; Mark H. Sabaj; Sergio M. Q. Lima (Journal of Fish Biology, 2026)
Two new species of whiptail catfish, Loricaria (Siluriformes: Loricariidae), were discovered in the Munim and Itapecuru river basins, Maranhão State, northeastern Brazil, through an integrative taxonomic approach combining morphology and mitochondrial DNA. Linear discriminant analysis revealed three morphometrically distinct groups, and coxI ‐based phylogeny identified four genetically divergent lineages of Loricaria in northeastern Brazil. The new species are clearly distinguished from their closest congeners, L. turi and L. parnahybae , by unique diagnostic traits, including abdominal plate patterns, pectoral girdle coverage and the shape of the postorbital notch. Genetic divergences among lineages, estimated as mean interspecific K2P distance, ranged from 2.2% to 4.1%, similar thresholds commonly applied for species delimitation in Loricariidae. Both species exhibit restricted distributions and are endemic to river basins under increasing anthropogenic pressure. These results underscore the underestimated diversity of Loricaria in northeastern Brazil and reinforce the role of coastal drainages as areas of endemism and speciation.

Reassessing and Updating Regulatory Standards on the Declaration of Storage Conditions in the Product Information of Medicinal Products: An Evidence-Based Proposal under EMA Guidance - Helena Pericão; Henrique Cavaco; Miguel Dias; Luís Sarmento; Mário Magalhães; Bernardo Filipe; Herivelto Vieira; João Rita; Pedro Gonçalves; Matilde Vaz; Beatriz Coimbra; Beatriz Monteiro; et al. (Pharmaceutical Research, 2026)
Purpose The European Medicines Agency (EMA) guideline Declaration of Storage Conditions in the Product Information of Medicinal Products (CPMP/QWP/609/96/Rev.2) was last revised in 2007. Since then, advances in stability science, increased climatic variability, and evolving regulatory expectations have highlighted limitations in the framework, particularly the use of vague descriptors such as “room temperature” or “no special storage conditions.” This work reassesses the scientific and regulatory basis for storage statements, integrating current understanding of mean kinetic temperature (MKT), climate-related risks, and developments in ICH and WHO guidance, and proposes a harmonized revision (Rev.3). Methods A structured analysis of regulatory and scientific principles was conducted, incorporating MKT, climate-related risks, and developments in ICH and WHO guidance. These elements informed a revised framework and model storage statements, including a decision table linking stability outcomes to label statements. Results The proposed update introduces explicit temperature-based statements, strengthens the linkage between stability data and label wording, clarifies requirements for moisture- and light-sensitive products, expands guidance for sterile and reconstituted preparations, and provides contingency instructions for temperature excursions. A decision table mapping stability outcomes to label statements is included to support regulatory implementation. Conclusion This revision provides an updated synthesis of EMA, ICH, and WHO requirements, translating regulatory principles into clear storage statements and contingency guidance. It offers a more precise framework reducing ambiguity, supports justification of storage conditions through stability data and MKT-informed risk assessment, aiming to improve understanding among patients and healthcare professionals, strengthening real-world product quality and contributing to future EMA guideline development. Highlights Identifies scientific and regulatory limitations in current “no special storage conditions” terminology; Links ICH stability guidelines and climatic variability to precise storage statements; Proposes harmonised core label phrases for room temperature, fridge, and freezer; Introduces contingency labelling for climate-related and cold-chain excursions.

Influence of pulp industry dregs on the physical and mechanical properties of mortar - Luis Felipe Moreira Cesar; Agda Eunice de Souza Albas; Nelson Batista de Lima; Jorge Luis Akasaki; João Carlos Silos Moraes (Environmental Science and Pollution Research, 2026)
This study examined the constituents and evaluated the effects of incorporating a pulp industry residue (dregs) on the physical and mechanical properties of mortar. The properties of the mortar constituents were evaluated using thermogravimetry–differential scanning calorimetry (TG-DSC), energy-dispersive spectroscopy (EDS), X-ray Fluorescence spectroscopy (XRF), X-ray diffraction (XRD), and tests specified in standards NBR 16605 (2017), NBR 11579 (2013), and NM 18 (2012). The hardened mortar was evaluated through mechanical testing (NBR 7215 2019), water absorption testing (NBR 9778 2005), and mercury intrusion porosimetry. XRD data from dregs treated at different temperatures were analyzed using the Rietveld refinement method. The specific gravities of the cement, dregs, and sand were 3.13, 2.58 and 2.62 g/cm 3 , respectively. The main chemical elements detected in the dregs (> 1 atom%) were Ca, Mg, Mn, Si, Na, S, and Al. Thermal analysis revealed two endothermic events: the evaporation of sulfur-containing compounds and the decomposition of calcium magnesium carbonate. Lattice parameters were obtained for the Ca 0.87 Mg 0.13 (CO 3 ) 2 phase, observed in the dregs treated at 100 and 500 °C, and for the CaO and MgO phases, observed after treatment at 750 °C. To evaluate compressive strength, water absorption, and porosity, mortars were prepared under three distinct conditions: one without dregs; four with dregs added to the mixture, keeping the cement and sand contents constant; and four with dregs as a partial replacement for Portland cement, keeping the sand content constant. Compressive strength decreases with increasing dregs content, with a more pronounced reduction when Portland cement is replaced by dregs than when dregs are added. Incorporating 40 wt% dregs reduced compressive strength by 73% under the Substitution condition and 52% under the Addition condition, relative to the reference mortar without dregs. This reduction in compressive strength is associated with increased water absorption and porosity as the dregs content increases.

Recycling waste, recycling risk: cypermethrin-contaminated poultry litter triggers sublethal toxicity in Folsomia candida at realistic environmental concentrations - Monizze Vannuci-Silva; Carolina C.S. Gomes; Lucas V. Sousa-Lima; Sidney F. Sales Junior; Evelyn O. Silva; Mariana F. Maia; Felipe Lucena; João Paulo M. Torres; Olaf Malm; Júlia C. Niemeyer; Enrico M. Saggioro; Cláudio E.T. Parente (Chemosphere, 2026)

Mebendazole impairs the expression and function of enzymes in nucleotide metabolism pathways, leading to Selective Cytotoxicity, Cell Cycle Arrest, and Damage to Cell Morphology in Gastric Cancer - Emerson Lucena da Silva; Felipe Pantoja Mesquita; Pedro Victor da Rocha Lima; José Hélio de Araújo Filho; Francisco Laio de Oliveira; Ana Beatriz da Lima; Pedro Filho Noronha Souza; Raquel Carvalho Montenegro (Chemico-Biological Interactions, 2026)

Small ruminant lentiviruses in dairy goats under tropical conditions: evidence of recombinant genotypes - Nathalie Costa da Cunha; Alana de Oliveira Campello; Leandro dos Santos Machado; Thomas Salles Dias; Thalyta Rodrigues Silva; Arthur de Almeida Figueira; Beatriz Pinheiro Melo da Silva; Lilian Gregory; Barbara Colitti; Dayse Lima da Costa Abreu; Isadora de Fátima Braga Magalhães; Elmiro Rosendo do Nascimento; et al. (Tropical Animal Health and Production, 2026)
Small Ruminant Lentiviruses (SRLVs) are widespread retroviruses of goats and sheep with significant economic and health impacts on small ruminant production systems. This study aimed to investigate the prevalence and genotype distribution of SRLVs in dairy goat flocks from Brazil. A total of 433 blood samples from eight dairy goat farms were analyzed via PCR targeting the gag gene. The overall SRLV prevalence was 32.6%, with marked variation between farms (7.1% to 90.0%). Phylogenetic analysis of 37 selected samples revealed that most sequences clustered within the B1 subtype. Notably, two sequences from farms C and G grouped with subtype A1 and showed evidence of recombination between B1 and A1 strains. These findings provide evidence of recombinant SRLV strains circulating in Brazilian goats. The findings highlight the circulation of distinct and recombinant SRLV strains in the region, reinforcing the importance of continuous molecular surveillance, improved biosecurity practices, and the development of effective control strategies to reduce viral dissemination and mitigate long-term impacts on small ruminant farming.

Short-term taxonomic and functional responses of zooplankton to the Floc and Sink technique: implications for non-target ecological effects - Juliana dos Santos Severiano; Laissa Lima do Nascimento; Felipe Antonio dos Santos; Daniely de Lucena-Silva; Amanda Myrna de Meneses e Costa; Maria Eduarda Dantas César; José Etham de Lucena Barbosa (Hydrobiologia, 2026)
Geoengineering techniques have been applied to control phosphorus and cyanobacteria, showing promising outcomes for the restoration of eutrophic aquatic ecosystems worldwide. However, the effects of the materials used in these techniques on non-target organisms, like zooplankton communities, are not well understood. This study evaluated the impacts of the materials used in the Floc and Sink geoengineering technique—specifically aluminum sulfate and polyaluminum chloride coagulants, alone or in combination with lanthanum-modified bentonite—on the taxonomic and functional diversity of zooplankton, identifying the functional traits associated with species sensitivity and tolerance. To achieve this, we conducted a 192-h bench-scale experiment using water from a eutrophic reservoir. We monitored biomass, taxonomic (richness, Shannon, and evenness) and functional (functional richness, evenness, and divergence) diversity, and functional traits related to mobility and feeding mode. Significant reductions in zooplankton biomass and diversity were observed, particularly in the treatments containing bentonite. Small-bodied, low-mobility filter feeders (e.g., rotifers and nauplii) were the most sensitive, while larger, more mobile raptorial copepods were more tolerant. These findings demonstrate that functional traits can predict species sensitivity or tolerance to geoengineering materials and highlight the importance of considering non-target impacts when applying the Floc and Sink technique for eutrophication management.

Seasonal biochemical characterization of the red seaweed Kappaphycus alvarezii cultivated in southern Brazil - Alex Ricardo Schneider; Felipe de Souza Dutra; Aline Nunes; Alex Alves dos Santos; Eva Regina Oliveira; Gadiel Zilto Azevedo; Susane Lopes; Giuseppina Pace Pereira Lima; Sidnei Moura; Marcelo Maraschin (Aquatic Botany, 2026)

PEGylated liposomal fluopsin C triggers cuproptosis and ferroptosis pathways and suppresses 3D tumor spheroid growth in NCI-H460 cells - Luan Vitor Alves de Lima; Matheus Felipe da Silva; Liana Martins de Oliveira; Maria Claudia Terkelli de Assis; Isabella Cristina Oliveira Carvalho; Isaura Maria Fuzinatto; Simone Cristine Semprebon; Renan Vinícius de Oliveira Nocetti; Danielle Lazarin-Bidoia; Celso Vataru Nakamura; Ingrid Felicidade; Sandra Regina Lepri; et al. (Archives of Toxicology, 2026)
Copper-based metallodrugs are promising anticancer agents, but their toxicity limits clinical translation. This study evaluated the toxicological and molecular effects of PEGylated Fluopsin C (PEG-FlpC) in in vitro human non-small-cell lung carcinoma (NCI-H460) cells cultured as 2D monolayer and 3D spheroids. Cells were exposed to PEG-FlpC at its IC 50 (1.0 µM) for 24 h. Flow cytometry revealed G₁-phase arrest and non-apoptotic cell death. PEG-FlpC markedly suppressed spheroid growth, with 2 × IC 50 -treated spheroids growing only 58.1% compared to 131.6% in the control. Ultrastructural analyses showed mitochondrial clustering and swelling, ER dilation, and cytoplasmic vacuolization. Gene profiling demonstrated downregulation of TP53 and BECN1 , with upregulation of TP73 and SQSTM1 , consistent with autophagy blockade and stress activation. PEG-FlpC modulated ferroptosis-related ( GPX4 , SLC7A11 , and TFRC ) and cuproptosis-related ( ATP7B , MTF1 , DLAT , and CDKN2A ) genes. Pharmacological inhibition confirmed a predominantly copper-mediated mechanism, as TTM (10 µM) restored 77.7% of metabolic activity. Combined inhibition with TTM and Fer-1 (1 µM) further increased viability to 89.4%, indicating that PEG-FlpC induces non-apoptotic regulated cell death through an interconnected cuproptosis–ferroptosis mechanism associated with mitochondrial dysfunction.

Modeling Future Climate Impacts on Brazil’s Operational Wind and Solar Energy Capacity - Felipe Husadel Poyer; Francisco Lopes Lima; Rodrigo Santos Costa; André Rodrigues Gonçalves; Fernando R. Martins; André F. P. Lucena; Enio Bueno Pereira (Environmental Modeling & Assessment, 2026)
Over the past decade, the Brazilian electricity sector has undergone a profound transformation, driven by the large-scale deployment of wind and solar photovoltaic power plants, a trend that is expected to continue in the years ahead. Although the transition to these variable renewable energy resources helps to reduce greenhouse gas emissions and mitigate the climate crisis, they are vulnerable to the very climate changes they help to avert. This study uses projections from CMIP6 global climate models under two future scenarios (SSP2-4.5 and SSP5-8.5) to assess potential impacts on power generation in the existing centralized wind and solar power facilities in Brazil. The study innovates by assessing the effects of climate change on the future performance of the power plants using measured historical capacity factors as a proxy, thereby eliminating the need for climate bias correction and standardized manufacturer power curves. Projections indicate a nationwide increase in wind potential between 6% and 15% by the end of the century, contributing to an extended wind season in the northeastern region and a stronger seasonality in the southern region. In contrast, the photovoltaic potential reveals modest change; the positive effects of increasing surface radiation are counterbalanced by the negative effects of warmer air temperatures across the assessed scenarios. These findings offer valuable insights for strengthening Brazil’s energy security under future climate conditions.

Integration of Multi-Omics Data To Understand the Multifaceted Role of RAMP1 across Different Cancer Types - Gabrielle da Costa Cabral; Letícia Almeida Rodrigues; Júlia de Almeida Cabral Candiago; João Felipe Fernandes Ferreira Procópio; Júlia Costa Cerqueira Silva; Maria Eduarda Barbosa de Lima; Ana Stella Gisela Ellery Costa Lima; José Valmir Falcão da Costa Júnior; David Abner Santos de Araújo; João Paulo Emiliano da Silva; Sofia Amancio de Almeida Oliveira; Rafael de Oliveira Calaça Farias; et al. (Cell Biochemistry and Biophysics, 2026)
Receptor Activity-Modifying Protein 1 (RAMP1) is a Calcitonin Receptor-Like Receptor (CALCRL)-associated protein with significant relevance in oncogenesis and tumor progression. It acts as a context-dependent allosteric modulator of GPCRs. This integrative review synthesizes evidence from multiple omics layers—transcriptomics, proteomics, epigenomics, and pan-cancer datasets—to clarify the role of RAMP1, its signaling pathways, and its relationship with the tumor microenvironment. Multi-omics integration highlighted several key findings: transcriptomic and regulatory signatures frequently associate RAMP1 overexpression with epithelial–mesenchymal transition; RAMP1 is associated with the coordinated activation of GPCR-dependent pro-tumorigenic pathways; and the CGRP/RAMP1 axis is associated with CD8 + T-cell exhaustion and potential resistance to immune checkpoint inhibitors. Pan-cancer analyses revealed marked expression heterogeneity. RAMP1 is strongly overexpressed in hepatocellular carcinoma (LIHC) and downregulated in kidney renal clear cell carcinoma (KIRC), reinforcing the importance of context-specific interpretation. It also emerges as an unfavorable prognostic biomarker in osteosarcoma, rectal adenocarcinoma, prostate cancer, and Ewing sarcoma, suggesting its potential value as a strategic therapeutic target. Future studies should prioritize spatial transcriptomics and the pharmacological modulation of the CGRP/RAMP1 axis to refine precision oncology strategies.

Mo-CBP3-PepIII Changes the Proteomic Profile of Gastric Cancer Cells, Induces Membrane Pore Formation, and ROS Overaccumulation - Talia Rabelo Oliveira; Felipe Pantoja Mesquita; Daiane Maria Silva Brito; Antonia Catarine Gomes Vieira; Emerson Lucena da Silva; Laís Lacerda Brasil-Oliveira; Maria Elisabete Amaral de Moraes; Pedro Victor da Rocha Lima; Raquel de Carvalho Montenegro; Pedro Filho Noronha de Souza (International Journal of Peptide Research and Therapeutics, 2026)
Background Synthetic peptides have gained prominence due to their potential structural alterations and selective toxicity. In this context, Mo -CBP 3 -PepIII, derived from Moringa oleifera , was developed to increase selectivity against tumor cells. This study evaluated its activity in AGS cells and demonstrated low toxicity in non-tumor cells, MNP-01. Its mechanism of action was investigated using membrane integrity analyses, reactive oxygen species accumulation, morphological alterations assessed by scanning electron microscopy, and proteomics. Findings The results indicate increases of 2.5-, 2.8-, and 1.5-fold, respectively, in membrane permeability, pore formation, and ROS accumulation in peptide-treated cells compared to controls. Scanning electron microscopy revealed that Mo-CBP3-PepIII-treated cells were severely damaged compared with control cells. Additionally, proteomic analysis identified 3052 proteins in control cells (1970) and treated cells (1532). A deeper look into differentially accumulated proteins revealed that Mo-CBP3-PepII interfere in the accumulation of proteins required for cancer cell growth, development and maintenance, drug resistance. Conclusion Therefore, future studies should delve deeper into its effects on apoptosis, migration, and tumor invasion, examine the cell signaling pathways involved, and explore the proteins identified in this study to understand their functions in tumor biology and the possible interactions of Mo-CBP3-PepIII with conventional drugs.

Low doses of ascorbic acid modulate the effect of chemotherapy agents in sarcoma 180 tumor-bearing mice - Josemar José da Silva Júnior; Leonardo da Rocha Sousa; Victor Alves de Oliveira; Antonio Lima Braga; Ag-Anne Pereira Melo de Meneses; Ricardo Melo de Carvalho; Joedna Cavalcante Pereira; Reyca Rodrigues e Silva; Raí Pablo Sousa de Aguiar; Antonielly Campinho dos Reis; Sérgio Eduardo Matos Cazarotti Francisco; Shamya Gabriella Corrêa Coêlho; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Tree planting in public squares in an Amazonian capital: are morphometric and ecological aspects considered for decision-making? - Hiago Felipe Cardoso Pacheco; Walmer Bruno da Rocha Martins; Julia Isabella de Matos Rodrigues; Joathan Cipriano Castro; Paula Daniele Martins Moraes; José Rozendo de Lima Silva; Marcos Alexandre Vieira Nascimento Filho; Lucas Lopes da Silva (Trees, 2026)
Key message This study highlights native species’ potential for urban landscaping in the Amazon region, prioritizing safety and ecosystem benefits. Abstract Public squares can be important elements for sustainable urban development and adaptation to climate change, for which an adequate tree composition is key. In the Amazon region, despite the high tree biodiversity, it is common to select unfitted species to compose public squares’ landscaping. Therefore, this research aimed to evaluate the suitability of species used for landscaping of public squares in an Amazonian state capital, based on 4 morphometric and 3 ecological features. 50 public squares were selected and inventoried, tree species were evaluated and classified according to morphometric features (crown projection, slenderness, overhang index, and coverage index), as well as ecological features (leaf habit, fruit weight, and species origin). Species were ranked from the most to the least suitable using weighted values based upon the 7 features employed. The results indicated that, within species currently in used in Belém public squares, Andira inermis (W.Wright) DC. (Cabbage bark) and Ceiba pentandra (L.) Gaertn. (Kapok tree), native to the Amazon region, were the most fitted for public squares landscaping among all the species encountered. Native species such as Bertholletia excelsa Bonpl. (Brazil nut) and Swietenia macrophylla King (Brazilian mahogany), although promising, showed limitations due to their high weighted fruits. This study highlights the need for further research on the use of native Amazonian flora in public squares, especially on its regulating and cultural ecosystem services provision in urban contexts. Additionally, it emphasizes that the implementation of some species should be discontinued due to risks to the safety of urban square visitors and possible damage to urban infrastructure.

Camphor-Induced Seizures in Rats Increase the Potency of Gamma Oscillations During the Ictal Period, A Component that may Lead to Refractoriness in Seizure Control - Priscille Fidelis Pacheco Hartcopff; Clarissa Araujo da Paz; Luciana Eiró Quirino; Thaysa de Sousa Reis; Daniella Bastos de Araujo; Rafael dos Reis de Souza; Caio Gabriel da Silva Motta; Mateus Felipe Ferreira Araújo; Marcelo Victor dos Santos Brito; Murilo Farias dos Santos; Alisson Bruno Leite Lima; Axell Lins; et al. (Neurotoxicity Research, 2026)
Particularly in the evaluation of substances that can cause neuronal hyperexcitability, triggering refractoriness to antiepileptic drugs, this has always been of interest to science. This study investigated the neurobehavioral and electrocorticographic (ECoG) characteristics of seizures induced by camphorated oil in Wistar rats and compared them to those triggered by pentylenetetrazol (PTZ), a classical chemoconvulsant model. Male rats received intraperitoneal administration of camphor (470 mg/kg), and behavioral evolution was monitored to characterize seizure onset and progression. ECoG recordings from the motor cortex were acquired for 30 min to assess cortical oscillatory activity during ictal and interictal periods. Camphor administration elicited six distinct and rapidly evolving behavioral patterns culminating in generalized clonic seizures with loss of postural reflexes. ECoG analyses revealed cyclic high-power ictal discharges interspersed with low-power interictal activity, resembling PTZ-induced seizures but with lower potency. Evaluation of anticonvulsant efficacy demonstrated that camphor-induced seizures were refractory to phenobarbital and phenytoin, whereas diazepam and propofol significantly reduced β- and γ-band power and effectively controlled convulsive activity. These findings suggest that camphor produces a reproducible chemoconvulsant model characterized by prominent cortical excitability and partial pharmacoresistance, supporting its potential utility in neurotoxicological and neuropharmacological studies aimed at understanding seizure mechanisms and testing antiepileptic drug responsiveness.

Records for ticks (Acari: Ixodidae) on free-ranging Coendou spinosus from State of São Paulo, Brazil - Ticiana Zwarg; Marcelo Bahia Labruna; Mariana Morgado Hereny; Thaís Caroline Sanches; Mayra Hespanol Frediani; Vanessa Caldeira Olivares; Melissa Prosperi Prosperi; Felipe Almeida Lucato; Giovanna Silva Alves de Lima; Adriana Marques Joppert; Sergio Mello Novita Teixeira; Alex Junior Souza de Souza; et al. (Experimental and Applied Acarology, 2026)
Ticks and tick-borne diseases have spread since the mid-twentieth century largely due to major anthropogenic changes impacting natural ecosystems. The Coendou spinosus is a medium sized rodent found in the southeast of Brazil. There is little information about the presence and richness of ticks on porcupines. The objective of this study was to identified ticks collected from C. spinosus received at a triage center of wildlife in the city of São Paulo, from 1996 to 2025 (almost 30 years). Ticks from a total of 100 free-ranging porcupines were collected. A total of 223 ticks in various life stages were analyzed. Fifty-eight larvae, 17 nymphs, and 148 adults were identified. Of these, 89 were males and 59 were females. Some animals presented mixed infestations, with more than one tick species. The most prevalent species was Amblyomma longirostre , with samples from 86 animals, followed by A. parkeri (18 animals), A. dubitatum (1 animal), A. ovale (1 animal), A. sculptum (1 animal), and Haemaphysalis juxtakochi (1 animal). To the best of our knowledge, this is the first report of the presence of Haemaphysalis juxtakochi parasitizing this porcupine species. Additionally, we highlight the observation of a male of A. longirostre attached to the porcupine’s spine. Ticks are important vectors of several pathogens causing zoonotic diseases. This work contains information that can contribute to knowledge and conservation of porcupines, and to the development of environmental surveillance strategies.

Genomic, biological, and chemical studies of Streptomyces sp. LaBMicrA B280 isolated from the rhizosphere of Inga edulis Martius in the Amazon - Rafael de Souza Rodrigues; Antonia Queiroz Lima de Souza; Jania Lilia da Silva Bentes; Kamila Rangel Primo Fernandes; Felipe Moura Araújo da Silva; Maria de Fátima Oliveira Almeida; Rafael Pinto e Souza; Anderson Nogueira Barbosa; Fábio César Sousa Nogueira; Gabriel Reis Alves Carneiro; Ricardo de Melo Katak; Ivanildes dos Santos Bastos; et al. (Antonie van Leeuwenhoek, 2026)
In this study, we investigated the taxonomic identity and biotechnological potential of the actinobacterium Streptomyces sp. LaBMicrA B280, isolated from the rhizosphere of Inga edulis (Mart.). Our approach combined a phylogenomic approach, annotation of metabolic subsystems and biosynthetic gene clusters (BGCs), biological assays to assess antifungal, antimalarial, cytotoxic, and larvicidal activities, classical molecular networking analysis, and characterization of the major compound in the most active fraction (FR3). The digital DNA–DNA hybridization values, using the d2 (GGDC) and d4 (TYGS) formulas, average nucleotide identity, and average amino acid identity ( Streptomyces genus. Our genomic analysis revealed 39 BGCs, including the cluster responsible for pentamycin biosynthesis, 314 metabolic subsystems, and 24 gene categories. In the molecular networking analysis, pentamycin was the only compound identified. Biological assays with fraction FR3 at a concentration of 50 µg/mL showed 96.59% ± 0.03 and 72.39% ± 0.18 inhibition against Plasmodium falciparum strains W2 and 3D7, respectively, as well as 91.45% ± 0.55 cytotoxicity against the HEp-2 cancer cell line. Larvicidal activity assays demonstrated 100% efficacy against Aedes aegypti (FO) at 250 µg/mL after 48 h. Pentamycin, a known antifungal compound, was successfully isolated from the highly active FR3 fraction. These findings highlight that LaBMicrA B280 exhibits a broad biotechnological potential and represents a promising source of important secondary metabolites for future application.

High Seroprevalence Rates of Toxoplasma gondii and Neospora caninum in Dogs in the Pantanal Region of Mato Grosso, Brazil - Gabriel Lucas Artiaga-Silva; Álvaro Felipe de Lima Ruy Dias; Matheus Roberto Carvalho; Kamilla Silva Melo; Arleana do Bom Parto Ferreira de Almeida; João Luis Garcia; Richard de Campos Pacheco; Valéria Régia Franco Sousa (Acta Parasitologica, 2026)

Thymic epithelial cell responses to the friedelin triterpene in vitro - Felipe Lima Porto; Marvin Paulo Lins; Salete Smaniotto; Maria Danielma dos Santos Reis (Natural Product Research, 2026)

Detection of Brucella spp. in compost-bedding pack barn and its relationship with infections in dairy cows during the transition period - Marcilene Daniel Damasceno; Maysa Serpa Gonçalves; Maria Eduarda de Souza Teixeira Campos; Amanda Carvalho Rosado Ferreira; Dircéia Aparecida Costa Custódio; Eduarda Moraes Magossi Silva; Vivian Aparecida Malta; Alice Gonçalves dos Reis; Bruno Borges Silva; Ana Clara de Serpa Carvalho; Júlia Lima Paz; Pedro Felipe Rodrigues e Oliveira; et al. (Research in Veterinary Science, 2026)

Expanding the genus Macroptilium (Leguminosae): a new species from the Brazilian Cerrado - Carolina Lima Ribeiro; Felipe da Silva Santos; Cristiane Snak; Gwilym Peter Lewis; Luciano Paganucci de Queiroz (Kew Bulletin, 2026)

Evaluation of Viligen® NE as a feed additive for Pacific white shrimp reared in a biofloc system during the nursery phase - Camilla Souza Miranda; Ivanilson de Lima Santos; Ramon Felipe Siqueira Carneiro; Isabela Claudiana Pinheiro; Norha Constanza Bolívar; Débora Machado Fracalossi; Philip Lyons; Anne Koontz; Scheila Anelise Pereira Dutra; Felipe Boéchat Vieira (Aquaculture International, 2026)
The aim of this study was to evaluate Viligen® NE (Alltech®, USA) as a feed additive for Penaeus vannamei reared in a biofloc system during the nursery phase, focusing on growth performance, intestinal microbiological analysis, and resistance tocold challenge. Shrimp post-larvae (41 mg) were fed for 6 weeks with four experimental diets: (a) 0.5 g Viligen® NE kg⁻ 1 , (b) 1 g Viligen® NE kg⁻ 1 , (c) 2 g Viligen® NE kg⁻ 1 , and (d) a control diet (0 g Viligen® NE kg⁻ 1 ). The experiment was conducted in quadruplicate, totaling 16 experimental tanks, with a stocking density of 2000 post-larvae m⁻ 3 . Shrimp growth performance parameters were positively influenced by the inclusion of Viligen® NE in the diet. Polynomial regression indicated an optimal inclusion level of 1.17 g kg⁻ 1 for maximizing specific growth rate and weight gain. Additionally, supplementation at 1 g kg⁻ 1 enhanced shrimp resistance to cold challenge. However, no significant differences were observed in intestinal counts of total heterotrophic bacteria or Vibrio spp. among treatments. In conclusion, dietary supplementation with Viligen® NE at an optimal level of 1.17 g kg⁻ 1 improved growth performance, and 1 g kg⁻ 1 enhanced cold challenge resistance of nursery-phase shrimp reared in a biofloc system.

Life cycle inventories of global metal and mineral supply chains: a comprehensive data review, analysis and processing - Frédéric Lai; Stéphanie Muller; Audrey Philippe; Robert Istrate; Brenda Miranda Xicotencatl; Afsoon Mansouri Aski; Aina Mas Fons; Juliana Segura-Salazar; Jair Santillán Saldivar; Alexander Cimprich; Stephen Northey; Lígia da Silva Lima; et al. (Resources, Conservation and Recycling, 2026)

Phylogenomics of Amazonian squirrel monkeys (Saimiri: Primates, Cebidae) - Michelle P. Mercês; Hazel Byrne; Natalie Finnegan; Maria L. Harada; Fernanda P. Paim; Felipe E. Silva; Anita Stone; Marcela G.M. Lima; Anthony B. Rylands; José de Sousa e Silva Júnior; Jessica W. Lynch (Molecular Phylogenetics and Evolution, 2026)

Bromeliads of the semi-arid Caatinga: Ecosystem services and cultural keystone roles of macambiras (Encholirium and Bromelia) as a model for other plant species - Jaqueiuto S. Jorge; André Felipe de V. Duarte; Roberto Lima Santos; Eliza Maria X. Freire; Adriano Caliman (Journal of Arid Environments, 2026)

Unraveling molecular thermotolerance mechanisms in the wild rice species Oryza australiensis - Yugo Lima-Melo; Paloma Koprovski Menguer; Aléxis Cardama Kin; Evelise Bach; Thomaz Stumpf Trenz; Érika Frydrych Capelari; Janette Palma Fett; Marcia Margis-Pinheiro; Felipe Klein Ricachenevsky (Planta, 2026)

Assessment of Vancomycin Penetration into Cerebrospinal Fluid in Patients with Ventriculitis Using a Physiologically Based Pharmacokinetic Approach - Larissa Martins Alves Guimarães; Letícia Oliveira de Vasconcellos Nacif; Jhohann Richard de Lima Benzi; Mayra Torres de Oliveira Santos; Carolina Yamada; Felipe Francisco Tuon; João Paulo Telles; Fernanda de Lima Moreira (Pharmaceutical Research, 2026)
Introduction Vancomycin is an antimicrobial agent for treating central nervous system (CNS) infections caused by Gram-positive bacteria. Due to practical and ethical reasons, it is difficult to evaluate vancomycin exposure in cerebrospinal fluid (CSF) and its relationship with therapeutic outcomes. Therefore, alternative methodologies are required. We developed a physiologically based pharmacokinetic (PBPK) model to characterize vancomycin exposure in plasma and CSF in patients with ventriculitis enrolled in a therapeutic drug monitoring program. Methodology PBPK modeling and simulation were conducted using PK-Sim® version 11.3. A PBPK model was constructed to simulate vancomycin exposure in plasma and CSF. Physicochemical parameters of vancomycin were incorporated into a large molecule model, and tissue distribution was described using the Rodgers-Rowland model. Results The final PBPK model incorporated vancomycin’s low brain permeability by adjusting the CSF-to-plasma partition coefficient to 0.17. Model validation was performed using data from 33 patients with ventriculitis under external ventricular drainage. The dosing regimen consisted of a 30 mg/kg loading dose followed by a continuous intravenous infusion of 60 mg/kg/day. Mean simulated vancomycin concentrations in plasma and CSF were 32 mg/L and 7.2 mg/L, respectively. The predicted CSF/plasma concentration ratio was 0.22, which closely matched the observed ratio of 0.17. Conclusion Vancomycin penetration into the CNS is low and variable, highlighting the importance of therapeutic drug monitoring and individualized therapy in patients with ventriculitis. In the future, this model may facilitate the selection of optimal dosing regimens by simulating alternative dosing strategies and establishing PK/PD relationships for CNS infections.

The effects of skeletal muscle conditioned medium on oxidative stress and morphometry of murine testicles cultured in vitro - Fernanda Lima Alves; Maria Alice Felipe Oliveira; Solano Dantas Martins; Maria Joana Nogueira de Moura; Cibele dos Santos Borges; Leiz Maria Costa Veras; Vânia Marilande Ceccatto; Valdevane Rocha Araújo (In Vitro Cellular & Developmental Biology - Animal, 2026)

Systematics, phylogeography and integrative taxonomy of European Luciola fireflies (Lampyridae: Luciolinae) - Viviane C. S. Nunes; OctÁvio S. Paulo; Martin Novák; Daniela Maeda Takiya; Yelena Pacheco; Julie Cadigan; Raphael De Cock; Paula Malaquias Souto; GorÁn VignjeviĆ; Ana CatalÁn; Marcel Koken; Kathrin Stanger-Hall; et al. (Systematics and Biodiversity, 2026)

Acute and chronic effects of salinity on nitrification in a recirculating aquaculture system with açaí seeds (Euterpe oleracea) as biological media - Deyselana Lima da Costa; Bruno José Corecha Fernandes Eiras; Jean Danilo da Silva Pereira; Adriele Carolina Raiol Rodrigues; Hayanna Lucy Barbosa Barros; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; Maria de Lourdes Souza Santos; João Felipe Nogueira Matias; Fabio Carneiro Sterzelecki (Frontiers in Marine Science, 2026)
Introduction The Blue Amazon represents an extensive coastal zone with high biodiversity and wide salinity variation, which poses challenges for marine fish farming, particularly regarding the efficiency of biofilters in recirculating aquaculture systems (RAS). In this context, açaí seeds ( Euterpe oleracea ), previously evaluated in freshwater, emerge as a promising alternative for use as filter media under different salinity conditions. The objective of this study was to evaluate the potential of açaí seeds as substrate in RAS biofilters, analyzing their acute and chronic impact on the physicochemical parameters of water and the removal of ammonia, nitrite and nitrate over 28 days. Methods The experiment was conducted in six independent systems (three aquaria each), subjected to salinities of 0, 7, 14, 21, 28 and 35‰. After Acute (0, 20, 40, 60,80,100 and 120 minutes) and chronic (2,3,4,14,21 and 28 days) salinity change, water samples were collected to measure physicochemical quality and to assess nitrification efficiency and nitrogen compound removal. Results Higher oxygen consumption and ammonia clearance were observed at 0, 7 and 14‰ after 120 minutes of salinity change, while nitrate accumulation was significantly higher in freshwater. In long term, after 28 days, ammonia clearance was significantly lower at 35‰, though nitrate accumulation was not affected by salinity. The highest ammonia removal rates were recorded in the 0‰ and 7‰ treatments. Discussion The results demonstrate that açaí seeds are capable of removing ammonia after a few minutes and can sustain the growth of nitrifying bacteria under different salinity levels, although more efficiently in low salinity waters (seven times).

Global patterns of pesticide residues in seaweeds: A systematic review - Gadiel Zilto Azevedo; Felipe de Souza Dutra; Aline Nunes; Giuseppina Pace Pereira Lima; Marcelo Maraschin (Marine Pollution Bulletin, 2026)

Sustainable assessment of Brazilian shrimp farming in coastal zone a spotlight on legislation: A review - Maria Carolina Da Silva; Genes Fernando Gonçalves Junior; Ítalo Felipe Mascena Braga; Priscilla Celes Maciel De Lima; Danielli Matias De Macêdo Dantas; Alfredo Olivera Gálvez; Soraya Giovanetti El-Deir (Regional Studies in Marine Science, 2026)

Carbon cycle dynamics in the subtropical South Atlantic: orbital pacing and regional modulation over the last 772 kyr - José, Renato Derntl; Karen, Badaraco Costa; Felipe Antônio de Lima Toledo (Journal of South American Earth Sciences, 2026)

Resistance exercise training attenuates skeletal muscle atrophy in experimental pulmonary arterial hypertension - Sebastião Felipe Ferreira Costa; Luciano Bernardes Leite; Leôncio Lopes Soares; Sara Caco dos Lúcio Generoso; Mirielly Alexia Miranda Xavier; Matheus Soares Faria; Arthur Eduardo de Carvalho Quintão; Luiz Otávio Guimarães Ervilha; Thainá Iasbik Lima; Bruno Rocha Avila Pelozin; Tiago Fernandes; Edilamar Menezes Oliveira; et al. (Pflügers Archiv - European Journal of Physiology, 2026)

Associations Between APOE Polymorphisms, Neurological Symptoms, and Cognitive Assessments in Long COVID Patients: An Analysis of SNPs rs7412 and rs429358 - Isadora de Almeida Gomes; Pedro Braga-Neto; Thiago Loreto Matos; Emerson Lucena da Silva; Lais Lacerda Brasil de Oliveira; Luina Benevides Lima; José Wagner Leonel Tavares-Júnior; Alissa Elen Formiga Moura; Marcello Holanda de Andrade; Thaís de Maria Frota Vasconcelos; Reinaldo Barreto Oriá; Danilo Nunes Oliveira; et al. (Molecular Neurobiology, 2026)

Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Maycon T. Emílio-Silva; Vinícius P. Rodrigues; Antonio J. Ruiz-Malagon; Isabela G. Guidolin; Felipe L. Dario; Mariana M. Fioravanti; Alba Rodriguez-Nogales; Julio Gálvez; Clelia A. Hiruma-Lima (Inflammopharmacology, 2026)

A Marseillevirus isolate from the Brazilian wetlands - Matheus Felipe dos Reis Rodrigues; Nidia Esther Colquehuanca Arias; Talita Bastos Machado; João Victor Rodrigues Pessoa Carvalho; João Pessoa Araújo Júnior; Luiz Henrique Rosa; Luiz Carlos Junior Alcantara; Rodrigo Araújo Lima Rodrigues; Victória Fulgêncio Queiroz; Jônatas Santos Abrahão (Archives of Virology, 2026)
Marseilleviruses are giant viruses that infect amoebas and have been isolated from various environments. Here, we describe a new strain, isolated from a water sample collected from the Paraguay River in the Brazilian Pantanal, which we have named "Marseillevirus pantanense". Transmission and scanning electron microscopy revealed icosahedral particles approximately 190 nm in diameter. Genomic and phylogenetic analyses show that M. pantanense has a 379,900-bp genome with 496 open reading frames, including 12 ORFans and two tRNAs. Furthermore, phylogenetic analysis places M. pantanense within Marseillevirus lineage A, group I. The findings of in this study underscore the importance of isolating new viruses to expand our understanding of the abundance and distribution of giant viruses in Brazilian biomes.

Systematics of Amydetinae (Coleoptera: Lampyridae) - Lucas Campello-Gonçalves; André Silva Roza; Sara Rivera; José Ricardo Miras Mermudes; Marc A. Branham; Luiz Felipe Lima da Silveira (Systematics and Biodiversity, 2025)

Heatwaves in the Northern Brazil Region: Current and Future Perspectives - Felipe Jeferson de Medeiros; Samyr Barata Chebly; Glícia Ruth Garcia de Araújo; Francisco Agustinho de Brito Neto; Kellen Carla Lima (International Journal of Climatology, 2025)
Heatwaves (HWs) characteristics (number, frequency and duration) in state capitals of the Northern Brazil Region (NBR) and their climate projections throughout the century were analysed using observed data from meteorological stations and Regional Climate Models (RCMs). HWs were identified considering a minimum period of three consecutive days during which the daily maximum temperature exceeds the 90th percentile. Results showed that more than 125 HWs were recorded in each NBR capital between 1980 and 2019. On average, these HWs were observed over a span of 17–21 days per year, with individual events typically lasting between 3 and 5 days. In the last four decades (1980–2019), the number of HWs as well as their frequency and duration have increased over the NBR. Regarding the model's performance, the HWs characteristics could be reasonably reproduced by the ensemble generated by the RCM from the CORDEX‐CORE. However, the errors found led us to apply a bias‐correction method to produce a fair indication of the future changes. In a future perspective considering the most pessimistic scenario (RCP8.5), HWs are projected to increase in number, frequency, and duration in almost all capitals, with these conditions expected to worsen by the end of the century. The projected intensification suggests that the number of HWs could more than double in most NBR capitals, while the increase in frequency and duration can exceed 600% and 300%, respectively. These regional projected changes reinforce the need for deep, rapid and sustained mitigation and accelerated implementation of adaptation actions to contain and reduce global warming and its related impacts and risks for humans and ecosystems.

Fatal Bothrops atrox snakebite with thrombotic microangiopathy, hemorrhagic stroke and acute kidney injury - Larissa Rocha Alípio Duarte; Érica Carvalho; Tigran Francis Chehuan Melo; Fabiane Bianca Albuquerque Barbosa; Rosilene Viana de Andrade; Marco Sartim; Felipe Queiroz Araújo; Jacqueline Sachett; Guilherme Pivoto; Luiz Carlos de Lima Ferreira; Wuelton Monteiro (Toxicon, 2025)

Intrafollicular immature oocyte transfer (IFIOT) for IN VIVO maturation of vitrified bovine oocytes - José Eduardo Vieira Chaves; Ana Caroline Chaves Vall Nicolás; Nayara Ribeiro Kussano; Laryssa Ketelyn Lima Pimenta; Venâncio Augusto Oliveira Silva; Alice Caroline Souza e Castro; Ana Cristina Menezes Mendes Gomes; Leonardo de França e Melo; Margot Alves Nunes Dode; José Felipe Warmling Sprícigo (Theriogenology, 2025)

Nutritional and bioactive profile of Pereskia violacea leaves, a new Brazilian Ora-Pro-nobis species from the Amazon, and effects of season - Gabriela Fabiana Soares Alegre; Cynthia Tereza Corrêa da Silva Miranda; Henrique Silvano Arruda; Felipe Tecchio Borsoi; Iramaia Angélica Neri-Numa; Eduardo Adilson Orlando; Grasieli Beloni de Melo; Augusto César Costa-Santos; Juliana Azevedo Lima Pallone; Valdely Ferreira Kinupp; Glaucia Maria Pastore (Food and Humanity, 2025)

Amazonian buriti and pracaxi as potential functional feed additives to improve shrimp immunity and resistance to WSSV - José Stênio A. Rebouças; Abdon O. Vieira; Ediane M. Rubas; Doris S.M. Souza; Franceli R. Kulcheski; Larissa Müller; Vitória D. de Oliveira; Juliane Ventura Lima; Felipe W. Mendonça; Rafael D. Rosa; Luciane M. Perazzolo (Fish & Shellfish Immunology, 2025)

First molecular detection Anaplasma phagocytophilum in sheep in Brazil - Giulia Ribeiro Meireles; Julia Somavilla Lignon; Paola Renata Joanol Dallmann; Diago Dutra Lima; Tamires Silva dos Santos; Thuanne Correa Brancão; Maiza Paixão Souza; Bruno Caetano Urtassum; Kauê Rodriguez Martins; Rodrigo Casquero Cunha; Fábio Raphael Pascoti Bruhn; Felipe Geraldo Pappen; et al. (Veterinary Research Communications, 2025)

Genetic variability of Staphylococcus Pseudintermedius in animals from Mato Grosso, Brazil: methicillin-resistant clonal complexes and discovery of new sequence types - Alvair da Silva Alves; Fernanda Harumi Maruyama; Álvaro Felipe de Lima Ruy Dias; Stéfhano Luis Cândido; Lucas Gabriel Serra da Silva Soares; Letícia Camara Pitchenin; Isabela de Godoy Menezes; Luciano Nakazato; Valéria Dutra (Veterinary Research Communications, 2025)

Boron excess in Alternanthera tenella Colla under in vitro conditions: tolerance and potential for supplementation in plants - Marcel Merlo Mendes; Julia Felipe Miranda; Lívia Batista das Neves; João Paulo Rodrigues Martins; Ana Caroline Pariz Rocha; Daniela Cassol; Andreia Barcelos Passos Lima Gontijo; Antelmo Ralph Falqueto (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Boron (B) plays a crucial role in plant physiological processes, and imbalances in its supply can markedly affect plant morphophysiology. This study evaluated the effects of a B concentration gradient on the growth and morphophysiological responses of Alternanthera tenella under in vitro conditions. Stem segments were cultured on media supplemented with different B concentrations (0, 125, 250, 500, 750, 1000, and 2000 µM) for 30 days. Growth traits, anatomical features, nutrient accumulation, photosynthetic pigment content, and photosystem II (PSII) performance were assessed. Increasing B availability enhanced Mg and S accumulation, while the thickness of root vessel elements increased progressively up to 750 µM B. Tissues associated with nutrient transport exhibited improved functionality, indicating more efficient translocation from roots to shoots under adequate B supply. Photosynthetic pigment content and PSII parameters were also highest at 750 µM B. The tolerance index remained above 68% across all treatments, demonstrating that A. tenella is tolerant to elevated B levels. However, excessive B concentrations (≥ 1000 µM) induced physiological disturbances and PSII structural damage, likely associated with pigment reduction. Anatomical adjustments observed in plants exposed to high B concentrations may represent adaptive mechanisms limiting further B uptake. In addition, the study suggests that 750 µM B is recommended to enhance its morphophysiological performance under in vitro culture.

Co-application of Brassinosteroids and Salicylic Acid Improves Drought Tolerance in Pre-Flowering Sorghum Plants - Danielle Lopes Aguiar; Sebastião de Oliveira Maia Júnior; Jailma Ribeiro de Andrade; Patrick Costa Silva; Robson Felipe de Lima; Fabrício de Oliveira Reis; Tiago Massi Ferraz; Thais Roseli Corrêa; Fábio Afonso Mazzei Moura de Assis Figueiredo (Journal of Soil Science and Plant Nutrition, 2025)

Late Quaternary sedimentation patterns in the deep northeastern South China Sea: insights from IODP Hole U1432C - Amanda Gerotto; Rubens Cesar Lopes Figueira; Paulo Alves de Lima Ferreira; Felipe Stanchak; Renata Hanae Nagai (Journal of Sedimentary Environments, 2025)

IL-17 as a putative hallmark of intense arthralgia and age-related serum immune mediator networks during acute chikungunya fever - Caio Wilker Teixeira; Jonai Pacheco Dias; Lizandra Morgado-Santos; Ismael Artur da Costa-Rocha; Sarah Giarola-Silva; Ágata Lopes-Ribeiro; Letícia Gomes-de-Pontes; Thaiza Aline Pereira Santos; Joaquim Pedro Brito-de-Sousa; Erik Vinicius de Sousa Reis; Ana Carolina Campi-Azevedo; Andréa Teixeira-Carvalho; et al. (Inflammation Research, 2025)

Cratylia mollis lectin reduces inflammatory burden induced by multidrug-resistant Staphylococcus aureus in diabetic wounds - Lucas dos Santos Silva; Simeone Júlio dos Santos Castelo Branco; Izadora Souza Soeiro Silva; Miria Yasmim Miranda Paiva; Beatriz Gomes Vila Nova; Carlos Emanuel de Matos Chaves Lima; Weslley Felix de Oliveira; Felipe Eduardo Alves de Paiva; Patrícia Maria Guedes Paiva; Andrea de Souza Monteiro; Claudener Souza Teixeira; Cléver Gomes Cardoso; et al. (Histochemistry and Cell Biology, 2025)

Traditional ecological knowledge of scorpions in human communities in a Brazilian semiarid region - Luiza Eulália de Azevedo Gonzaga; José Rivaldo de Lima; Meykson Alexandre da Silva; Geraldo Jorge Barbosa de Moura; André Felipe de Araujo Lira (International Journal of Tropical Insect Science, 2025)

Removal of crystal violet and methylene blue dyes from aqueous effluents using Brazil nut (Bertholletia excelsa) wastes as a potent biosorbent from Amazonia - Júlia Cristina Diel; Matias Schadeck Netto; Isaac dos Santos Nunes; Luis Felipe Oliveira Silva; Tito José Crissien; Glaydson Simões dos Reis; Eder Cláudio Lima; Guilherme Luiz Dotto (Environmental Science and Pollution Research, 2025)

Jará açu (Leopoldinia major) waste as a potent biosorbent from Amazonia for the removal of crystal violet and methylene blue dyes from aqueous effluents - Júlia Cristina Diel; Matias Schadeck Netto; Isaac dos Santos Nunes; Laís Casarin Eich; Gabriel Penteado Prestes; Luis Felipe Oliveira Silva; Tito José Crissien; Glaydson Simões dos Reis; Eder Cláudio Lima; Guilherme Luiz Dotto (Environmental Science and Pollution Research, 2025)

Climate change will boost the invasion of the harmful cyanobacterium Raphidiopsis raciborskii in South America - Felipe Morais Zanon; Bruno Henrique Mioto Stabile; Beatriz Melissa Campos; Érica Oliveira de Lima; Matheus Juan Alarcon Sampaio; Yasmin Rodrigues de Souza; Leonardo Rodrigues Tolardo; Mayra Koma Gomes; Luddy Searom Carias de Moraes; Gabriela Sponchiado Hein; Jaqueline Dantas da Silva; Larissa da Silva Pinha; et al. (Harmful Algae, 2025)

Corrigendum to “Silver nanoparticles for control of foliar pathogens in passion fruit (Passiflora edulis) crops” [Biocatal. Agric. Biotechnol. 68 (2025) 103717] - Natália Deniz Brito; Rafael José Vilela de Oliveira; Felipe Leon Nascimento de Sousa; Ana Júlia Silva Rocha; Maria Eduarda Almeida Matos; Laura Lima Turani; Raphael Ferreira Queiroz; Bianca Galúcio Pereira Araújo; Giovanna Machado; Quelmo Silva de Novaes (Biocatalysis and Agricultural Biotechnology, 2025)

Association of corn processing methods and sodium lasalocid for beef cattle on pasture during the finishing phase - Paloma Helena Gonçalves; Gabriel Santos Souza David; Laura Franco Prados; Bianca Rodrigues Domingos; Beatriz Lima Vellini; Felipe Almeida Nascimento; Willian Manoel Ricardo Foresto; Naiara Caixeta da Silva; Flávio Dutra de Resende; Gustavo Rezende Siqueira (Tropical Animal Health and Production, 2025)

Greater occupancy of invasive hybrid marmosets compared to a threatened native species in the fragmented Atlantic Forest: implications for conservation - Samuel Lucas Brasileiro Silvério; Orlando Vitor Vital; Rodrigo Lima Massara; Felipe Santos Pacheco; Rodolfo da Cunha Sarcinelli; Fabiano Rodrigues de Melo (Primates, 2025)

Cellular toxicity of organotellurans: a systematic review of pre-clinical studies - Maria Luisa Lima Barreto do Nascimento; Isabela Ribeiro de Sá Guimarães Nolêto; Francisco Leonardo Torres-Leal; Felipe Cavalcanti Carneiro da Silva; João Marcelo de Castro e Sousa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Molecular docking and antitumor evaluation of liposomal nanoformulations containing citrinin - Ag-Anne Pereira Melo de Menezes; Michely Laiany Vieira Moura; José Williams Gomes de Oliveira Filho; Maria Luisa Lima Barreto do Nascimento; Juan Carlos Ramos Gonçalves; Marianna Vieira Sobral; Karinne Kelly Gadelha Marques; Felipe Cavalcanti Carneiro da Silva; Guilherme Barroso L. De Freitas; Vladimir Costa Silva; Shamya Gabriella Corrêa Coêlho; Marjorie Pereira Gualter; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

DNA Methylation and Oxidative Stress in a Fish from an Area of the Amazon Historically Impacted by Anthropogenic Activities - Douglas dos Santos Marcelino; Luana Beatriz Sales Pinon; Yure Jefferson da Cruz do Nascimento; Flávia dos Santos Tavares; Luan Felipe da Silva Frade; Maria Iracilda Cunha Sampaio; Luis Adriano Santos do Nascimento; Cesar Martins; Lílian Lund Amado; Adauto Lima Cardoso; Renata Coelho Rodrigues Noronha (Bulletin of Environmental Contamination and Toxicology, 2025)

Rock powder type and soil texture shape microbial community shifts and plant biomass responses in highly weathered tropical soils - Rafael Lima Oliveira; Nariane de Andrade; Caio César Gomes Freitas; Amanda Manuelly da Silva Oliveira; Danilo Ferreira da Silva; Mísia Souza Vieira; Rafael Santana Mendonça; Felipe Martins do Rêgo Barros; Antonio Carlos de Azevedo; Fernando Dini Andreote (Applied Soil Ecology, 2025)

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Successive Meso-Cenozoic brittle reactivations in a Neoproterozoic mylonitic shear zone - Luana Ribeiro Garcia; Clauzionor Lima da Silva; Felipe Garcia Porath; Jessica Miranda dos Santos (Journal of South American Earth Sciences, 2025)

Fermentation of passion fruit leaf tea with Kombucha inoculum: An upcycling approach for the development of functional fermented beverages - Alliny Samara Lopes de Lima; Ana Terra de Medeiros Felipe; Emanuelle Maria de Oliveira Paiva; Renato Dantas Medeiros; Francisco Canindé de Sousa Junior; Kátia Nicolau Matsui; Silvana Maria Zucolotto; Marcia Regina da Silva Pedrini (Food Research International, 2025)

Arsenic bioaccumulation in ready-to-eat oysters can contribute to the selection of WHO critical priority Enterobacterales displaying a virulent behavior - Felipe Vásquez-Ponce; Nicolas Gamboa-Acuña; Aline Pereira de Oliveira; Johana Becerra; Jesus G.M. Pariona; Leon de Oliveira Lima; Aline de Carvalho Elias; Maciel Santos Luz; Mateus Rocha Ribas; Gustavo Rocha; Fernanda Esposito; Patricio Muñoz; et al. (Food Research International, 2025)

Natterin-mediated NLRP3 inflammasome activation in zebrafish: evolutionary insights and aquaculture implications - Felipe Justiniano Pinto; Darlan Gusso; Jefferson Thiago Gonçalves Bernardo; Aline Ingrid Andrade-Barros; Carlos DeOcesano-Pereira; Monica Lopes-Ferreira; Carla Lima (Fish & Shellfish Immunology, 2025)

Larvicidal mechanism of the rare sesquiterpene ishwarol B from Piper alatipetiolatum (Piperaceae) against Aedes aegypti, Anopheles darlingi, and Culex quinquefasciatus (Culicidae): oxidative damage, defense enzyme modulation, and acetylcholinesterase inhibition - André Correa de Oliveira; Felipe Moura Araujo da Silva; Ingrity Suelen Sá; Maria Luiza Lima da Costa; Sergio Massayoshi Nunomura; Rosemary Aparecida Roque; Rita de Cássia Saraiva Nunomura (Chemico-Biological Interactions, 2025)

Impacts of rural and urban sources on a tropical semiarid region (Acaraú River, Ceará, Brazil): sedimentary sterols and endocrine-disrupting compounds as anthropogenic molecular markers - Rivelino M. Cavalcante; Antonio D. S. Pereira; Marcielly F. B. Lima; Pollyana Morais; Elissandra V. Marques; Gabrielle M. Fernandes; Rafael P. Santos; Ronaldo F. Nascimento; Felipe R. Santos; Lucas B. Moreira (Environmental Geochemistry and Health, 2025)

3D-printed electrochemical loop-mediated isothermal amplification (E-LAMP): A miniaturized and portable platform to detect methicillin-resistant Staphylococcus aureus (MRSA) - Lucas F. de Lima; Paulo Felipe Neves Estrela; Lucas Costa Faustino; Jonatas V. Souza; Charleane Justino de Assunção; Everson T.S. Gerôncio; Leandro Fonseca de Lima; Elisa Flávia Luiz Cardoso Bailão; William R. de Araujo; Thiago R.L.C. Paixão; Gabriela R.M. Duarte (Analytica Chimica Acta, 2025)

Physical Interactions between Cancer Cells and Tumor Microenvironment - Andressa Beatriz Apolinário da Silva Correia; Beatriz Medeiros de Souza Melo; Bruna Alves da Silva; Giovana Cruz Maciel; Guilherme Matheus Santos Marques Cavalcante; João Pedro Almeida dos Santos; Layza Maria Barbosa Silva; Luís Filipe Pereira Rocha; Maria Beatriz Cavalcante Brêda; Maria Eduarda Teixeira de Oliveira; Kayo Felipe Barbosa Lima; Luiz Ben-Hur de Oliveira Wanderley Nepomuceno; et al. (Cell Biochemistry and Biophysics, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Magmatic sulphide nickel evaluation in mafic-ultramafic bodies of the Caraíba Complex, north Itabuna Salvador Curaçá Orogen, São Francisco craton - Sylvio Dutra Gomes; Felipe de Jesus Guedes; Natali Barbosa; Alice Marques Pereira Lau; Ernesto Domingos Victorino; Nelize Lima dos Santos (Journal of South American Earth Sciences, 2025)

Mercury contamination in Amazon traditional populations: Metalloproteomic study associated with exposure frequency - Nubya Gonçalves Cavallini; Felipe Dalmazzo Cirinêu; José Cavalcante Sousa Vieira; Emerson Carlos de Almeida; Joyce Andrade da Silva; Victor Diego Faria; Tania Machado da Silva; Marcelo de Oliveira Lima; Luis Fabricio Zara; Jiri Adamec; Marília Afonso Rabelo Buzalaf; Pedro de Magalhães Padilha (Journal of Hazardous Materials, 2025)

Mixed infection of Leishmania (Leishmania) infantum and Leishmania (Viannia) braziliensis in a mare (Equus ferus caballus) from Minas Gerais State, Southeastern Brazil - Anna Luiza Moreira Martins; Letícia Gracielle Tôrres de Miranda Estevam; Marina Andrade Freire; Ana Cristina Vianna Mariano da Rocha Lima; Flávia Carvalho Bitencourt de Oliveira; Felipe Dutra-Rêgo; Gustavo Mayr de Lima Carvalho; Vitor Márcio Ribeiro; Gustavo Fontes Paz (Journal of Equine Veterinary Science, 2025)

Accuracy assessment of PlanetScope SuperDove products for aquatic reflectance retrieval over Brazilian inland and coastal waters - Rafael G. Chasles; Daniel A. Maciel; Claudio C.F. Barbosa; Evlyn M.L.M Novo; Vitor S. Martins; Rejane Paulino; Raianny Wanderley; Rogério F. Júnior; Thainara M. Lima; Pedro Bacellar; Julio C.P. dos Santos; Ana Clara da C. Silva; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Silver nanoparticles for control of foliar pathogens in passion fruit (Passiflora edulis) crops - Natália Deniz Brito; Rafael José Vilela de Oliveira; Felipe Leon Nascimento de Sousa; Ana Júlia Silva Rocha; Maria Eduarda Almeida Matos; Laura Lima Turani; Raphael Ferreira Queiroz; Bianca Galúcio Pereira Araújo; Giovanna Machado; Quelmo Silva de Novaes (Biocatalysis and Agricultural Biotechnology, 2025)

Antimicrobial resistance and genetic diversity of Escherichia coli isolated from marine bivalves - Jailton Lobo da Costa Lima; Marcelly Miranda Aybal Jayme; Felipe Piedade Gonçalves Neves; Angela Corrêa de Freitas-Almeida; Mara Lúcia Penna Queiroz; Fabio Vieira de Araujo (Brazilian Journal of Microbiology, 2025)

Scorpions in urbanized landscapes: influence of habitat type and landscape on body condition, diversity and functional traits in a Neotropical submontane forest - Matheus Leonydas Borba Feitosa; Fredy Alvarado; Hidalgo Valentim Gomes de Lima; Geraldo Jorge Barbosa de Moura; André Felipe de Araujo Lira (Acta Oecologica, 2025)

Can the tick Rhipicephalus microplus transmit Trypanosoma vivax to cattle by the transovarial and mechanical routes? - Luiz Fellipe Monteiro Couto; Dina Maria Beltran Zapa; Vanessa Ferreira Salvador; Igor Maciel Lopes de Moraes; Luccas Lourenzzo Lima Lins Leal; Artur Siqueira Nunes Trindade; Thiago Souza Azeredo Bastos; Gabriel Lopes Tamiozo; Lidia Mendes de Aquino; Ennya Rafaella Neves Cardoso; Lucianne Cardoso Neves; Felipe da Silva Krawczak; et al. (Veterinary Parasitology, 2025)

Dose and age-dependent effects of Eimeria spp. infection on cytokine and intestinal integrity gene expression in broiler chickens - Pamella Pryscila de Alvarenga Bissoli Maciel de Lima; Patrícia Gonzaga Paulino; Nelson Meireles da Silva; Karina Cristina Paes Galdino; Carla Alves Rabello; Fernanda Gonçalves de Souza; Túlio Leite Reis; Leandro dos Santos Machado; Felipe Dilelis de Resende Souza; Huarrisson Azevedo Santos (Veterinary Parasitology, 2025)

How to promote circular economy in the global South: The circular technical network framework and the case of Colombia - Ana Julieth Calderón Márquez; Nathalia Silva de Souza Lima Cano; Emília Wanda Rutkowski; André Felipe Simões; Beatrice Smyth (Resources, Conservation and Recycling, 2025)

The role of Pep4 protease in Cryptococcus neoformans cell survival and virulence factors - Gabrielle Felizardo; Adrián Adolfo Álvarez Padilla; Amanda Teixeira de Melo; Ricardo Ferreira Lima; Grasielle Pereira Jannuzzi; Kevin Felipe Cruz Martho; Sandro Rogério de Almeida; Karen Spadari Ferreira; Renata Castiglioni Pascon; Marcelo Afonso Vallim (Fungal Biology, 2025)

Survival and viability of Toxoplasma gondii oocysts under natural dry season conditions in the Brazilian semi-arid region - Ana Luzia Peixoto Silva; Brendo Andrade Lima; Victor Hugo Alves Sousa Formiga; Estefany Ferreira Lima; Geraldo Moreira Silva Filho; Welitânia Inácia Silva; Jordania Oliveira Silva; Felipe Boniedj Ventura Alvares; Vinícius Longo Ribeiro Vilela; Thais Ferreira Feitosa (Veterinary Research Communications, 2025)

Evaluation of mechanical transmission of Anaplasma marginale by Stomoxys calcitrans - Luciana Maffini Heller; Dina María Beltrán Zapa; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Luiz Fellipe Monteiro Couto; Lídia Mendes de Aquino; Lucianne Cardoso Neves; Bianca Barbara Fonseca da Silva; Lorena Lopes Ferreira; Antonio Thadeu Medeiros de Barros; Paulo Henrique Duarte Cançado; et al. (Research in Veterinary Science, 2025)

Larvicidal activity, oxidative stress, and enzymatic alterations induced by essential oil from Piper cyrtopodon (Miq.) C.DC (Piperaceae) on Aedes aegypti (Culicidae) - Maria L.L. da Costa; André C. de Oliveira; Vinícius B. Ribeiro; Suelen C. Lima; Felipe M.A. da Silva; Sergio M. Nunomura; Rita de C. S. Nunomura; Rosemary A. Roque; Tatiane P. de Souza (Biocatalysis and Agricultural Biotechnology, 2025)

Effect of the genotype and environment interaction on body weight traits in Nelore cattle (Bos indicus) - Raimundo Nonato Colares Camargo-Júnior; Cláudio Vieira de Araújo; Caio de Souza Teixeira; Simone Inoe de Araújo; Raysildo Barbosa Lôbo; Lílian Roberta Matimoto Nakabashi; Letícia M. Mendes de Castro; Flávio Luiz Menezes; André Guimarães Maciel e Silva; José Ribamar Felipe Marques; Welligton Conceição da Silva; Marco Aurélio Lopes Della Flora; et al. (Tropical Animal Health and Production, 2025)

Root-Stem Transition Zone Anatomy Assessment in Hormonal Variants of Tomato, After Growing Under Contrasting Water Saturation - Rodrigo Barbosa Kloss; Felipe Della Torre; Vinícius Politi Duarte; Fabricio José Pereira; Joni Esrom Lima; Marcel Giovanni Costa França (Journal of Plant Growth Regulation, 2025)

Hydraulic and climate controls of hypogene and epigene speleogenesis at a regional scale in northeastern Brazil - Augusto S. Auler; Philippe Audra; Jo De Waele; Rubson P. Maia; Francisco H.R. Bezerra; Xianfeng Wang; Marco Antonellini; Fabrizio Balsamo; Giovanni Bertotti; Carla Furtado; Vincenzo La Bruna; Rebeca Lima; et al. (Geomorphology, 2025)

Waste-to-resource caproic acid production by anaerobic mixed microbial cultures: A review of recent developments - Felipe Filgueiras de Almeida; Fabrício de Lima; Sávia Gavazza; Osmar Menezes (Biomass and Bioenergy, 2025)

6-Ishwarone: A novel eco-friendly botanical biocide inducing oxidative stress and disrupting defense enzyme activities in Aedes aegypti Linnaeus, 1762 and Anopheles darlingi Root, 1926 (Culicidae) - André C. de Oliveira; Ingrity S. Costa Sá; Felipe M.A. da Silva; Suelen C. Lima; Maria Luiza L. da Costa; Sergio M. Nunomura; Rosemary A. Roque; Rita C.S. Nunomura (Biocatalysis and Agricultural Biotechnology, 2025)

Description of a sheep abortion caused by atypical genotype of Toxoplasma gondii in the state of Mato Grosso, Brazil - Ícaro Guilherme dos Santos; Marlon Ribeiro; João Paulo da Silva Cavasani; Luana Dias o Nascimento; Bernardo Nassau de Souza; Rafaela Mallmann-Bohn; Fábio Bernardo Schein; João Fabio Soares; Beatriz Souza Lima Nino; João Luis Garcia; Daniel Felipe Barrantes Murillo; Tatiane Terumi Negrão Watanabe; et al. (Veterinary Research Communications, 2025)

Aluminum accumulation in mosses from the Brazilian savanna: a comparative study of two species revealing similar traits to vascular plants - Mateus Fernandes Oliveira; Ígor Abba Arriola; Guilherme Henrique Rodrigues-Mattos; Felipe Della Torre; Joni Esrom Lima; Marcel Giovanni Costa França; Rosy Mary dos Santos Isaias; Adaíses Simone Maciel-Silva (Planta, 2025)

Use of Vermicompost Modulates Physiological and Growth Responses of Paricá Seedlings more than Mineral Fertilization - Maria Leidiane Reis Barreto; Maria Bruna de Lima Oliveira; Milena de Cassia Silba Borges; Milton Garcia Costa; Renato de Mello Prado; Alexandre de Vicente Ferraz; Adam da Cruz Rodrigues; Felipe Tavares Lima; Jesus de Nazaré Santos Oliveira; Marta Oliveira da Silva; Eric Victor de Oliveira Ferreira; Cassio Rafael Costa dos Santos (Journal of Soil Science and Plant Nutrition, 2025)

Bartonella spp., Coxiella burnetii and Rickettsia rickettsii in urban bats: molecular investigation of neglected zoonoses in Brazil - Danilo Alves de França; Alana Vitor Barbosa da Costa; Leandro Meneguelli Biondo; Ana Íris de Lima Duré; Benedito Donizete Menozzi; Felipe Fornazari; Helio Langoni (Brazilian Journal of Microbiology, 2025)

Sequential macrophage DENV and ZIKV infection shows differential expression of CD86, IFN-β, and regulation of TNF-α and IL-1β depending on DENV serotype - Gustavo Andrade Brancaglion; Gabriel Augusto Pires de Souza; Leonardo Pereira de Araújo; Evandro Neves Silva; Laura Leone da Silva; Fernanda de Lima Tana; Patrícia Paiva Corsetti; Luiz Felipe Leomil Coelho; Leonardo Augusto de Almeida (Brazilian Journal of Microbiology, 2025)

Recent advances and perspectives of eco-efficient building materials from iron ore tailing: characterization, performance, and consumption - Luis Felipe dos Santos Lara; Gustavo Filemon Costa Lima; Laís Resende; Augusto Cesar da Silva Bezerra (Journal of Cleaner Production, 2025)

The loss of an unknown biodiversity: Spatial gaps in plant survey and conservation in a Brazilian hotspot of biodiversity - Priscila Silveira; Juliana Silveira dos Santos; João Carlos Pena; Natácia E. de Lima; Luciana C. Vitorino; Felipe Martello; Rejane A. Guimares; Jhonatan W. Moreira; Jordanna C. Gomes; Lara M. de Araújo; Milton C. Ribeiro; Rosane G. Collevatti (Biological Conservation, 2025)

First report of bovine genital trichomoniasis in the semi-arid region of Brazil - Vinícius Longo Ribeiro Vilela; Basílio Felizardo Lima Neto; Geraldo Moreira Silva Filho; Flaviane Teles Souza; Ana Patrícia Gomes Lima; Felipe Boniedj Ventura Alvares; Fernanda Pereira Silva Barbosa; Renata Pimentel Bandeira Melo; Rinaldo Aparecido Mota; Thais Ferreira Feitosa (Tropical Animal Health and Production, 2025)

EHMT2 as a Candidate Gene for an Autosomal Recessive Neurodevelopmental Syndrome - Laura Machado Lara Carvalho; Jessica Rzasa; Jennifer Kerkhof; Haley McConkey; Veniamin Fishman; Galina Koksharova; Alexander Augusto de Lima Jorge; Elisa Varella Branco; Danyllo Felipe de Oliveira; Beatriz Martinez-Delgado; Maria J. Barrero; Tjitske Kleefstra; et al. (Molecular Neurobiology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Analysis of recycled polystyrene electrospinning process: Fiber diameter, morphology, and filtration applications - Felipe de Aquino Lima; Ana Carolina Sguizzato Honorato; Gabriela Brunosi Medeiros; Paulo Augusto Marques Chagas; Edilton Nunes da Silva; Ana Cristina Coelho Vieira; Wanderley Pereira Oliveira; Mônica Lopes Aguiar; Vádila Giovana Guerra (Journal of Environmental Chemical Engineering, 2025)

A novel hybrid cyanobacteria mapping approach for inland reservoirs using Sentinel-3 imagery - Thainara M.A. de Lima; Claudio C.F. Barbosa; Cristina S.F. Nordi; Felipe N. Begliomini; Vitor S. Martins; Fernanda S.Y. Watanabe; Raianny L.N. Wanderley; Rejane S. Paulino (Harmful Algae, 2025)

First study confirming the transmission of Trypanosoma vivax in cattle through rectal palpation: how many animals can be infected by reusing the same procedure glove, and what role does iodine play as a disinfectant? - Luccas Lourenzzo Lima Lins Leal; Thiago Souza Azeredo Bastos; Igor Maciel Lopes de Morais; Luciana Maffini Heller; Vanessa Ferreira Salvador; Artur Siqueira Nunes Trindade; Luiz Fellipe Monteiro Couto; Dina María Beltrán Zapa; Raphaela Bueno Mendes Bittencourt; Lorena Lopes Ferreira; Felipe da Silva Krawczak; Fabiano Antonio Cadioli; et al. (Veterinary Research Communications, 2025)

First report of a cat (Felis catus) infected by Leishmania (Viannia) guyanensis from Southeastern Brazil - Thabata Santos Garcia; Vitor Márcio Ribeiro; Anna Luiza Moreira Martins; Marina Andrade Freire; Flávia Carvalho Bitencourt de Oliveira; Ana Cristina Vianna Mariano da Roch Lima; Isabela Dias Pivari; Felipe Dutra-Rêgo; Gustavo Mayr de Lima Carvalho; Letícia Gracielle Tôrres de Miranda Estevam; Gustavo Fontes Paz (Veterinary Research Communications, 2025)

Acaricidal efficacy of the monoterpene linalool against the cattle tick Rhipicephalus microplus and its synergistic potential with cypermethrin - Felipe Boniedj Ventura Alvares; Larissa Claudino Ferreira; Jordania Oliveira Silva; Ana Maria Santos Lima; Thais Ferreira Feitosa; Vinícius Longo R. Vilela (Experimental and Applied Acarology, 2025)

Genomic and epidemiological surveillance of SARS-CoV-2 variants during the pre-mass vaccination period in Botucatu, Brazil - Felipe Allan da Silva da Costa; Patricia Akemi Assato; Karen Ingrid Tasca; Leonardo Nazário de Moraes; Drielle Baptista dos Santos Figueiredo; Gabriela Ribeiro; Alex Ranieri Jerônimo Lima; Sandra Coccuzzo Sampaio; Maria Carolina Quartim Barbosa Elias Sabbaga; Carlos Magno Castelo Branco Fortaleza; Jayme Augusto de Souza-Neto; Rejane Maria Tommasini Grotto (Virus Genes, 2025)

Bioavailability of Al, Fe, Mn and Zn in a Decommissioned Mining Area Evaluated by Biomonitoring and Passive Samplers: Robustness, Efficiency and Relationships Between Biotic and Abiotic Monitoring Approaches - Guilherme dos Santos Lima; Carlos Eduardo Eismann; Lucas Pellegrini Elias; Luiz Felipe Pompeu Prado Moreira; Amauri Antonio Menegario (Archives of Environmental Contamination and Toxicology, 2025)

Antibiotic-resistance genes and metals increase in polluted tropical rivers of the Baia da Ilha Grande, Rio de Janeiro, Brazil - Leonardo F. Bacha; Marcelo de A.P. Oliveira; Felipe Landuci; Ana Carolina Vicente; Pedro H. Paz; Michele Lima; Marcella Hilário; Lucia S. Campos; Mateus Thompson; Caroline Chueke; Diogo Tschoeke; Adacto Ottoni; et al. (Science of The Total Environment, 2025)

Unlocking the transcriptional profiles of an oily waste-degrading bacterial consortium - Rita de Cássia Barreto Silva-Portela; Carolina Fonseca Minnicelli; Júlia Firme Freitas; Marbella Maria Bernardes Fonseca; Douglas Felipe de Lima Silva; Kamila Karla Silva-Barbalho; Raul Maia Falcão; Thiago Bruce; João Vitor Ferreira Cavalcante; Rodrigo Juliani Siqueira Dalmolin; Lucymara Fassarella Agnez-Lima (Journal of Hazardous Materials, 2025)

Bench-scale bioretention systems: Potential of substrates with and without coconut fiber for plant growth development - Valesca Hellen Ferreira de Sousa; Maria Thereza Rocha Chaves; Rebeca Felipe dos Santos Silva; Kelly de Araújo Rodrigues Pessoa; Rinaldo dos Santos Araújo; Teresa Raquel Lima Farias; Waleska Martins Eloi (Journal of Environmental Management, 2025)

High detection rate of parasitic load by qPCR targeting 18S rDNA in blood of patients with active leishmaniasis lesions - Gabriel Victor Castanheira; Valdir Sabbaga Amato; Felipe Francisco Tuon; Letícia Ramos Dantas; Silvio Fernando Guimarães de Carvalho; Thallyta Maria Vieira; Ana Paula Venuto Moura; Jackeline Maria de Sousa Lima Lopes; Gustavo Henrique Johanson; Christini Takemi Emori; Regina Maia de Souza (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Eeg Microstates and Balance Parameters for Stroke Discrimination: A Machine Learning Approach - Eloise de Oliveira Lima; José Maurício Ramos de Souza Neto; Felipe Leonardo Seixas Castro; Letícia Maria Silva; Rebeca Andrade Laurentino; Vitória Ferreira Calado; Isolda Maria Barros Torquato; Karen Lúcia de Araújo Freitas Moreira; Suellen Marinho Andrade (Brain Topography, 2025)

Exploring the antivirulence potential of phenolic compounds to inhibit quorum sensing in Pseudomonas aeruginosa - Emília Maria França Lima; Felipe Alves de Almeida; Uelinton Manoel Pinto (World Journal of Microbiology and Biotechnology, 2025)

Mixed models in the selection of interspecific crosses of Psidium spp. resistant to myrtle rust - Letícia da Silva Araújo; Alexandre Pio Viana; Silvaldo Felipe da Silveira; Beatriz Murizini Carvalho; Débora Souza Mendes; Joameson Antunes Lima (European Journal of Plant Pathology, 2025)

Testing the dual-memory framework: individual differences in the magnitude of the retrieval practice effect and fluid intelligence - Marcos Felipe Rodrigues de Lima; Luciano Grüdtner Buratto (Cognitive Processing, 2025)

Chemometrics and digital image colorimetry approaches applied to paper-based analytical devices: A review - Irati Berasarte; Gorka Albizu; Wendel Ferreira Santos; Lucas Felipe de Lima; Miren Ostra; Maider Vidal; William Reis de Araujo (Analytica Chimica Acta, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

Quaternary deflection of the Macuma River as it crosses the actively growing Cutucú antiformal culmination in southeastern Ecuador - Pedro Reyes; Mauricio Valarezo; Santiago Ramos; Sandra Procel; Elizabeth Lasluisa; Ana Cabero; Felipe Lima (Journal of South American Earth Sciences, 2025)

Epiphytic orchids show specificity for phorophyte and strata on palm trees in a restinga area in the Brazilian Atlantic Forest - Ianara Tamyres Fonseca Borges; Deivid Lucas de Lima da Costa; Tainan da Silva Sousa; Maura da Silva Costa Furtado; Wanderson Cunha Pereira; Felipe Fajardo Villela Antolin Barberena (Plant Ecology, 2025)

Enriched Diet With Orange Essential Oil Citrus sinensis for Tambaqui Colossoma macropomum Promotes Growth Performance and Resistance Against Aeromonas hydrophila - Jucimauro de Araújo Pereira Júnior; Domickson Silva Costa; Arthur dos Santos da Silva; Gracienhe Gomes dos Santos; Arthur Felipe Lima dos Santos; Aldeize Driely Cardoso da Silva; Márcia Valéria Silva do Couto; Carlos Alberto Martins Cordeiro; Maurício Laterça Martins; Natalino da Costa Sousa (Journal of Fish Diseases, 2025)
The objective of this study was to evaluate the effect of dietary supplementation with Citrus sinensis (L.) Osbeck essential oil on the growth, immune system, and resistance to Aeromonas hydrophila infection in Colossoma macropomum fingerlings. The experiment was conducted with five treatments (control diet, Tween80 diet, and diets supplemented with 200, 400, and 800 mg L −1 of C. sinensis essential oil) with four replicates. At the end of the experimental period, growth parameters were measured, and blood samples were collected for thrombogram, leukogram, and phagocytic activity analysis. A bacterial challenge with A. hydrophila was conducted for 96 h. C. macropomum fingerlings that were fed with 400 and 800 mg L −1 of C. sinensis essential oil had the highest growth parameters, with final weights of 533.18 ± 2.03 mg and 531.91 ± 2.67 mg, respectively, and an increase in the number of thrombocytes, lymphocytes, monocytes, and neutrophils, as well as higher phagocytosis rates compared to the control group. Regarding the challenge, fish in the 400 and 800 mg L −1 treatments also exhibited the lowest cumulative mortality rate (26.66% ± 3.33%). Therefore, supplementation with C. sinensis essential oil promotes growth, improves health, and enhances resistance to A. hydrophila in C. macropomum fingerlings.

Phosphorus cycling from residual pools underlying efficient P fertilization in rotation systems in tropical agriculture - Bernardo Amorim da Silva; Ivan Francisco de Souza; Rodrigo Lima da Motta; Vanessa de Barros Tostes Pereira; Edson Marcio Mattiello; Gustavo Franco de Castro; Fabiane Carvalho Ballotin; Hudson Wallace Pereira de Carvalho; Leonardus Vergütz; Felipe Dalla Zen Bertol (Soil and Tillage Research, 2024)

The bimodal regime of ocean waves and winds over the continental shelf of Maranhão - Bruna Larissa R. dos Reis; Claudia K. Parise; Gustavo S. Correia; Leonardo G. de Lima; Heitor Perotto; Nícolas de A. Bose; Luis Felipe F. de Mendonça (Regional Studies in Marine Science, 2024)

Effect of roasting temperature on the physicochemical characteristics, phenolic content and bioactive potential of Spondias spp. seed flours - Felipe Carlos de Macêdo Oliveira; Djalma Lopes Galvão; Júlia da Costa Santos; Lívia Maria da Costa Dantas; Larissa Aida Lemos de Souza; Ana Heloneida de Araújo Morais; Marcos dos Santos Lima; Francisco Humberto Xavier Júnior; Cristiane Fernandes de Assis; Francisco Canindé de Sousa Júnior (Food Bioscience, 2024)

Bioaccumulation and ecotoxicity of parabens in aquatic organisms: Current status and trends - Felipe Félix Costa Lima da Silveira; Viviane Amaral Porto; Bianca Leite Carnib de Sousa; Emilly Valentim de Souza; Fabiana Laura Lo Nostro; Thiago Lopes Rocha; Lázaro Wender Oliveira de Jesus (Environmental Pollution, 2024)

Non-cytotoxic sulfated agaran from red seaweed Gracilaria cornea induces antitumor phenotype on macrophages in vitro and inhibits tumor growth in vivo - Felipe Barros Teles; Alexia Nathália Brígido Assef; Renato Martins Andrade; Vitória Virgínia Magalhães Soares; Nylane Maria Nunes de Alencar; Ana Paula Negreiros Nunes Alves; Tamiris de Fátima Goebel de Souza; Roberto César Pereira Lima-Júnior; Marjory Lima Holanda Araújo; Norma Maria Barros Benevides; Diego Veras Wilke (Bioactive Carbohydrates and Dietary Fibre, 2024)

Enhancing Wheat Resilience to Water Deficit through Selenium Biofortification: Perspectives on Physiological, Biochemical and Nutritional Responses - Leônidas Canuto dos Santos; Gabryel Silva Martins; Jucelino de Sousa Lima; Guilherme Augusto Mendes da Silva; Márcio Felipe Pinheiro Neri Nunes; Indira Pereira de Oliveira; Eduarda Santos de Andrade; Vitor de Laia Nascimento; Luiz Roberto Guimarães Guilherme; Guilherme Lopes (Journal of Soil Science and Plant Nutrition, 2024)

Uses and applications of the red seaweed Kappaphycus alvarezii: a systematic review - Aline Nunes; Gadiel Zilto Azevedo; Felipe de Souza Dutra; Beatriz Rocha dos Santos; Alex Ricardo Schneider; Eva Regina Oliveira; Sidnei Moura; Fábio Vianello; Marcelo Maraschin; Giuseppina Pace Pereira Lima (Journal of Applied Phycology, 2024)

CRISPR-Cas systems in enterococci - Amanda Seabra Cabral; Fernanda de Freitas Lacerda; Vitor Luis Macena Leite; Filipe Martire de Miranda; Amanda Beiral da Silva; Bárbara Araújo dos Santos; Jailton Lobo da Costa Lima; Lúcia Martins Teixeira; Felipe Piedade Gonçalves Neves (Brazilian Journal of Microbiology, 2024)

Effect of xylanase and Lentilactobacillus buchneri on corn silage harvested at two maturity stages - Wagner Sousa Alves; Alberto Jefferson da Silva Macêdo; Gabriela Duarte Oliveira Leite; Gabriel Ferreira de Lima Cruz; Tâmara Chagas da Silveira; Danielle Nascimento Coutinho; Albert José dos Anjos; Felipe Almeida Soares; Odilon Gomes Pereira; Karina Guimarães Ribeiro (Animal Feed Science and Technology, 2024)

Ulva ohnoi as a feed additive for Pacific white shrimp post-larvae cultured in a biofloc system - Ivanilson de Lima Santos; Ramon Felipe Siqueira Carneiro; Ana Paula Mariane de Morais; Mateus Aranha Martins; Walter Quadros Seiffert; Felipe do Nascimento Vieira (Aquaculture International, 2024)

Extracellular vesicles from the mycoparasitic fungus Trichoderma harzianum - Gabrielle Rosa Silva; Felipe de Pina Cavalcanti; Reynaldo Magalhães Melo; Emilio Cintra; Eliana Martins Lima; Pedro Ricardo Vieira Hamann; Luis H. F. do Vale; Cirano José Ulhoa; Fausto Almeida; Eliane Ferreira Noronha (Antonie van Leeuwenhoek, 2024)

A review of the main tectonic settings of Neoarchaean ore deposits and mineral occurrences in the northern São Francisco Craton, NE Brazil - Rafael Gordilho Barbosa; Johildo Salomão Figueirêdo Barbosa; Felipe Padilha Leitzke; Angela Beatriz de Menezes Leal; Ísis de Moraes Cortez; Rejane Lima Luciano; Basílio Elesbão da Cruz Filho; Jocilene dos Santos Santana; Antônio Marcos Vitória de Moraes (International Geology Review, 2024)

Water level regime variation is a crucial driver for taxonomic, functional, and phylogenetic diversity in seasonally flooded tropical forests - Fernanda Moreira Gianasi; Vinícius de Andrade Maia; Aline Meyer Oliveira; Patrícia Vieira Pompeu; Cléber Rodrigo de Souza; Camila Laís Farrapo; André Maciel da Silva-Sene; Fernanda de Oliveira; Thiago Magalhães Meireles; Ana Lívia de Carvalho Rodrigues; Denise Moura Madeira; Felipe Carvalho Araújo; et al. (Science of The Total Environment, 2024)

Effect of a thiohydantoin salt derived from -Arginine on Leishmania amazonensis and infected cells: Insights from biological effects to molecular docking interactions - Bruna Taciane da Silva Bortoleti; Priscila Goes Camargo; Manoela Daiele Gonçalves; Fernanda Tomiotto-Pellissier; Taylon Felipe Silva; Virginia Marcia Concato; Mariana Barbosa Detoni; Danielle Larazin Bidóia; Camilo Henrique da Silva Lima; Carlos Rangel Rodrigues; Marcelle de Lima Ferreira Bispo; Fernando Cesar de Macedo; et al. (Chemico-Biological Interactions, 2024)

Molecular identification of thrips species in Brazilian agroecosystems - Marcos Roberto Ribeiro-Junior; Felipe Barreto da Silva; Julio Massaharu Marubayashi; Angelica Maria Nogueira; Cristiane Muller; Élison Fabrício Bezerra Lima; Daniele Maria Nascimento; Francisco Manuel Ochoa-Corona; Renate Krause-Sakate (Phytoparasitica, 2024)

Paleo-ecological quality status induced by natural and anthropogenic impacts in the last 2000 years: a multidisciplinary approach in the outer region of Sepetiba Bay (SE Brazil) - Murilo Barros Saibro; Maria Virgínia Alves Martins; Rubens Figueira; Egberto Pereira; Heitor Evangelista; Marcus Vinícius Licínio; Josefa Varela Guerra; Felipe de Castro Figueiredo Simões; Vincent Marcel Pierre Bouchet; Fabio Francescangeli; Fabrizo Fontalini; Paulo Alves de Lima Ferreira; et al. (Journal of Soils and Sediments, 2024)
Purpose Some marine organisms can be used as Biological Quality Elements to estimate the degree of environmental impact and to monitor the health of benthic habitats. Organisms with mineralized protections, such as benthic foraminifera, can provide helpful information on the evolution of the coastal system over a long period and determine the Paleo-Ecological Quality Status (Paleo-EcoQS). This work aims at reconstructing the Paleo-EcoQS in the heavily anthropized Sepetiba Bay (SB; Rio de Janeiro State, SE Brazil). Materials and methods This work is based on a multiproxy approach, including textural, geochemical, and foraminiferal data along the core SP11 retrieved near the Pico da Marambaia (a mountain on the tip of the Marambaia Barrier Island). Geochemical analyses encompassing total organic carbon (TOC), total sulfur (S), total nitrogen (N), calcium carbonate (CaCO 3 ), stable isotopes in organic matter ( OM δ 13 C, and OM δ 15 N) and elemental concentrations as well as 201 Pb, 137 Cs, and radiocarbon dating were performed to characterize the Paleo-EcoQS in the bay. Results The values of the Paleo-EcoQS.st (standardized Paleo-EcoQS) index in core SP11 indicate that the paleoenvironmental quality varied from moderate to good between ≈50 AD and ≈1500 AD and from good to high between the ~ 1920s and ~ 1990s. Since the 1990s, the Paleo-EcoQS.st has deteriorated considerably, probably due to the deposition of contaminated dredging material in nearby areas. Ballast water discharge may have introduced alien species, such as Ammonia buzasi , into the SB. Conclusions The results obtained in core SP11, compared to those of another core (i.e., SP8) from a nearby area, suggest that the reference level of maximum environmental quality is not always reached in a period before industrialization in coastal ecosystems with significant interaction with the ocean; natural factors, related, for example, to sedimentary dynamic processes or geomorphological changes, can lead to unexpected results.

Angiotensin-(1–7) decreases inflammation and lung damage caused by betacoronavirus infection in mice - Erick Bryan de Sousa Lima; Antônio Felipe S. Carvalho; Isabella Zaidan; Adelson Héric A. Monteiro; Camila Cardoso; Edvaldo S. Lara; Fernanda S. Carneiro; Leonardo C. Oliveira; Filipe Resende; Felipe Rocha da Silva Santos; Luiz Pedro Souza-Costa; Ian de Meira Chaves; et al. (Inflammation Research, 2024)

Exploring the antiparasitic and antimicrobial potential of Schinus terebinthifolius Raddi essential oil against fish and shrimp pathogens - Jucimauro de Araújo Pereira; Gracienhe Gomes dos Santos; Domickson Silva Costa; Graziella Vivine Gonçalves de Matos Silva; Paola Capistrano dos Santos; Gabriele Bueno dos Anjos; Luiz Felipe Kretzer de Moraes; Claudia Andrea Lima Cardoso; Arlene Sobrinho Ventura; Natalino da Costa Sousa; Mauricio Laterça Martins (Journal of Fish Diseases, 2024)
This study aimed to perform in vitro antiparasitic and antimicrobial tests with the essential oil (EO) of Schinus terebinthifolius against of fish and shrimp. The chemical composition of the EO of S. terebinthifolius was determined by gas chromatography. For the antiparasitic test, the protozoan Epistylis sp. obtained from parasitized Oreochromis niloticus was used, and exposed to different concentrations of EO (2%, 1%, 0.5%, 0.25%), and control with 1% grain alcohol. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) test with EO of S. terebinthifolius evaluated the antimicrobial potential, with serial dilutions starting at 2% and control with 1% grain alcohol, using the strains of Aeromonas hydrophila (2.2 × 10 8 CFU mL −1 ), Edwardsiella tarda , Vibrio parahaemolyticus , V. harveyi , and V. alginolyticus (2.0 × 10 8 CFU mL −1 ). Chemical analysis revealed that the major EO compounds of S. terebinthifolius were δ‐3‐Carene (56.00%) and α‐Pinene (16.89%). In the antiparasitic test, the concentration of 2% EO showed 100% efficacy against Epistylis sp. within 5 min. In the antimicrobial tests, the concentration of 2% EO was effective against all bacteria tested. The EO of S. terebinthifolius demonstrated antiparasitic and antimicrobial activity at a concentration of 2%, standing out as an alternative to conventional antibiotics.

Correction: Understanding the role of microbes in health and disease of farmed aquatic organisms - Cristiane C. Thompson; Wilson Wasielesky; Felipe Landuci; Michele S. Lima; Leonardo Bacha; Luciane M. Perazzolo; Cátia Lourenço-Marques; Florbela Soares; Pedro Pousão-Ferreira; Larry Hanson; Bruno Gomez-Gil; Mateus Thompson; et al. (Marine Life Science & Technology, 2024)

Effect of coconut processing by-product graded feeding on carcass traits and meat quality of lambs - Felipe J.S. Silva; Dorgival M. Lima Júnior; Beatriz D.O. Fernandes; Anaiane P. Souza; Susana P. Alves; Rui J.B. Bessa; Francisco F.R. Carvalho; Ariosvaldo N. Medeiros (Meat Science, 2024)

Occurrence of antibodies and epidemiological significance of Toxoplasma Gondii and Neospora caninum infections in canine populations of Laguna, State of Santa Catarina - Ana Paula Remor-Sebolt; Felipe Rieth de Lima; Larissa Américo; Mayckon Antônio Cardoso Padilha; Andreas Lazaros Chryssafidis; Anderson Barbosa de Moura (Veterinary Research Communications, 2024)

Understanding the role of microbes in health and disease of farmed aquatic organisms - Cristiane C. Thompson; Wilson Wasielesky; Felipe Landuci; Michele S. Lima; Leonardo Bacha; Luciane M. Perazzolo; Cátia Lourenço-Marques; Florbela Soares; Pedro Pousão-Ferreira; Larry Hanson; Bruno Gomez-Gil; Mateus Thompson; et al. (Marine Life Science & Technology, 2024)

Phenotypic and genotypic characteristics of mecA - positive oxacillin-sensitive Staphylococcus aureus isolated from patients with bloodstream infection in a tertiary hospital in Southern Brazil - Felipe Crepaldi Duarte; Anna Paula Silva Olak; Stefani Lino Cardim; Tiago Danelli; Gerusa Luciana Gomes Magalhães; Deisy Mara Lima de Oliveira; Julia da Silva Pimenta; Eliana Carolina Vespero; Sueli Fumie Yamada-Ogatta; Marcia Regina Eches Perugini (Brazilian Journal of Microbiology, 2024)

CuO nanoparticles’ effect on the photosynthetic performance in seed tissues of Inga laurina (Fabaceae) - Daniela Espanguer Graciano; Montcharles Silva Pontes; Leandro Oliveira Araujo; Regiane Godoy Lima; Renato Grillo; Amilcar Machulek; Etenaldo Felipe Santiago; Samuel Leite Oliveira; Anderson Rodrigues Lima Caires (Environmental Science and Pollution Research, 2024)

Dispersion analysis of the 2017 Persian Gulf oil spill based on remote sensing data and numerical modelling - José Milton Neves de Souza Júnior; Luís Felipe Ferreira de Mendonça; Heverton da Silva Costa; Rose Ane Pereira de Freitas; Fernanda Casagrande; Douglas da Silva Lindemann; Rafael Afonso do Nascimento Reis; Carlos Alessandre Domingos Lentini; André Telles de Cunha Lima (Marine Pollution Bulletin, 2024)

Reproductive, productive and financial consequences of chronic Trypanosoma vivax infection in a dairy cattle herd in a region without a cyclic vector - Luiz Fellipe Monteiro Couto; Thiago Souza Azeredo Bastos; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Ricardo Backstron Falavigna; José Felipe Warmling Spricigo; Rinaldo Aparecido Mota; Breno Cayero Cruz; Marcos Henrique Alcantara Colli; Alexandre Braga Scarpa; Vando Edesio Soares; et al. (Veterinary Parasitology, 2024)

Three dimensional reconstruction of skin with melanoma: A model for study of invasion in vitro - Elenn Suzany Pereira Aranha; Leilane de Sousa Mendonça; Bianca de Lima Almeida; Emerson Lucena da Silva; Felipe Pantoja Mesquita; Emersom Silva Lima; Ana Paula Negreiros Nunes Alves; Maria Elisabete Amaral de Moraes; Raquel Carvalho Montenegro; Marne Carvalho de Vasconcellos (Toxicology in Vitro, 2024)

Bee honey of the Pajeú hinterland, Pernambuco, Brazil: Physicochemical characterization and biological activity - Walter de Paula Pinto-Neto; Rayssa Karla Silva; Brener de Santana Lima; Gabriel Felipe de Souza Acioli; Giselle Alves da Paixão; Brena Coutinho Muniz; Paula Katharina Nogueira da Silva; Romero Marcos Pedrosa Brandão Costa; Fábio Sérgio Barbosa da Silva; Hélio Fernandes de Melo; Rafael Barros de Souza; Marcos Antonio de Morais Júnior (Food Bioscience, 2024)

Tongue depressor (bio)sensors: A fast decentralized self-testing of salivary biomarkers for personalized medicine - Lucas Felipe de Lima; André Lopes Ferreira; Guida Hellen Mota do Nascimento; Luana Pereira Cardoso; Marcelo Bispo de Jesus; William Reis de Araujo (Chemical Engineering Journal, 2024)

Promising conilon coffee trees clones for agroforestry and intercropping systems - João Felipe de Brites Senra; Josimar Aleixo da Silva; Marlon Dutra Degli Esposti; Maurício Lima Dan; Alex Justino Zacarias; Amanda Oliveira da Conceição; Idalina Sturião Milheiros; Uliana Ribeiro Silva (Agroforestry Systems, 2024)

Bilateral testicular myxosarcoma in a cryptorchid dog - Tábatta Arrivabene Neves; Wanderson Lucas Alves dos Santos; Marlos Melo Duarte; Camila Arrivabene Neves; Jael Soraes Batista; Tiago da Silva Teófilo; Lucas dos Santos Rebouças; Ana Kelen Felipe Lima; Francisca Elda Ferreira Dias; Mônica Arrivabene; Tânia Vasconcelos Cavalcante (Research in Veterinary Science, 2024)

Coccolithophore and paleoproductivity variations in the subtropical western South Atlantic since the late deglaciation - Heliane Bevervanso Ferrarese; Felipe Antonio de Lima Toledo; Karen Badaraco Costa (Journal of South American Earth Sciences, 2024)

Preventive effect on intestinal inflammation and modulation of the microbiota of ‘Nordestino’ donkey milk in experimental DNBS-induced colitis in mice - Emmanuella de Oliveira Moura Araújo; Daline Fernandes de Souza Araújo; Tayanna Bernardo Oliveira Nunes Messias; Valéria Costa da Silva; Anderson Wilbur Lopes Andrade; Aurigena Antunes de Araújo; Raimundo Fernandes de Araújo Júnior; Emanuella de Aragão Tavares; Celso José Bruno de Oliveira; Elma Lima Leite; Gustavo Felipe Correia Sales; Juliana Kessia Barbosa Soares; et al. (International Dairy Journal, 2024)

Public food procurement and production: Evidence of the food acquisition program in Brazil - Dieison Casagrande; Lucas Emanuel; Carlos Freitas; Alex Lima; Fábio Nishimura; Felipe Oliveira (Food Policy, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Multifactorial evaluation of an ultra-fast process for electrospinning of recycled expanded polystyrene to manufacture high-efficiency membranes for nanoparticle air filtration - Felipe de Aquino Lima; Paulo Augusto Marques Chagas; Ana Carolina Sguizzato Honorato; Edilton Nunes da Silva; Mônica Lopes Aguiar; Vádila Giovana Guerra (Journal of Environmental Management, 2024)

Lactobacillus delbrueckii CIDCA 133 fermented milk modulates inflammation and gut microbiota to alleviate acute colitis - Luís Cláudio Lima de Jesus; Andria dos Santos Freitas; Joyce da Cruz Ferraz Dutra; Gabriela Munis Campos; Monique Ferrary Américo; Juliana Guimarães Laguna; Evandro Gonçalves Dornelas; Rodrigo Dias de Oliveira Carvalho; Kátia Duarte Vital; Simone Odília Antunes Fernandes; Valbert Nascimento Cardoso; Jamil Silvano de Oliveira; et al. (Food Research International, 2024)

3D-printed electrodes using graphite/carbon nitride/polylactic acid composite material: A greener platform for detection of amaranth dye in food samples - Lucas V. de Faria; Luana M. Villafuerte; Suéllen F.L. do Nascimento; Igor C. de Sá; Diego A. Peixoto; Ruan S. de A. Ribeiro; Edson Nossol; Thiago de M. Lima; Felipe S. Semaan; Wagner F. Pacheco; Rafael M. Dornellas (Food Chemistry, 2024)

Supraphysiological doses of nandrolone decanoate disrupts spermatogenesis but did not interfere on embryo rate - Fernanda Lima Alves; Maria Alice Felipe Oliveira; Ana Normélia Pereira de Morais; Solano Dantas Martins; Naiza Arcângela Ribeiro de Sá; Vânia Marilande Ceccatto; Yeda Fumie Watanabe; Valdevane Rocha Araújo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

How soon do metabolic alterations and oxidative distress precede the reduction of muscle mass and strength in Wistar rats in aging process? - Malu Cristina de Araújo Montoro Lima; Matheus Felipe Zazula; Luiz Fernando Martins; Stephanie Rubiane Carvalhal; Ana Tereza Bittencourt Guimarães; Luiz Claudio Fernandes; Katya Naliwaiko (Biogerontology, 2024)

Anaplasmosis outbreaks in taurine and zebu cattle in Brazil: causes, treatments, and Anaplasma marginale genetic diversity - Luccas Lourenzzo Lima Lins Leal; Alliny Souza de Assis Cavalcante; Igor Maciel Lopes de Moraes; Vanessa Salvador; Luiz Fellipe Monteiro Couto; Luciana Maffini Heller; Dina Maria Beltrán Zapa; Warley Vieira de Freitas Paula; Kamila Gaudêncio da Silva Sales; Eduardo Lima; Alexandre Braga Scarpa; Ricardo Antônio Amaral de Lemos; et al. (Tropical Animal Health and Production, 2024)

Influence of mini-tunnel and different rooting environments on the production of rooted mini-cuttings of subtropical Eucalyptus - Adriana Maria Griebeler; Maristela Machado Araujo; Felipe Turchetto; Claudia Costella; Ezequiel Gasparin; Álvaro Luis Pasquetti Berghetti; Marllos Santos de Lima; Nathália Pimentel; Osmarino Pires dos Santos (New Forests, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Semi-arid’s Unsung Heroes: Hymenoptera and the Vital Ecosystem Services Enabled by Encholirium spectabile, a Rupicolous Bromeliad in the Brazilian Semi-arid Region - Jaqueiuto S. Jorge; André Felipe V. Duarte; Roberto Lima Santos; Eliza Maria. X. Freire; Adriano Caliman (Neotropical Entomology, 2024)

Heavy metals bioaccumulation in free-ranging South American rattlesnakes (Crotalus durissus) in Southeastern Brazil - Frank August de Oliveira Toledo; Daniel Oliveira dos Santos; Izabela Magalhães Arthuso Vasconcelos; Ayisa Rodrigues Oliveira; Juliana Araújo Gomes Cabral; Rômulo Antônio Righi de Toledo; Pedro Hugo Henriques Cunha; Diego Felipe Alves Batista; Fabiola de Oliveira Paes Leme; Marcelo Pires Nogueira de Carvalho; Tatiane Alves da Paixão; Mariana Machado-Neves; et al. (Environmental Science and Pollution Research, 2024)

Deformational structures in the lower Barra Velha formation, Aptian, Atapu field, Santos Basin - Silvia Amorim Terra; Andre Ribeiro; Manuella Virgolino Mafia; Felipe Nepomuceno; Douglas Renato Lima da Silva; Leonardo Borghi (Journal of South American Earth Sciences, 2024)

Production of activated carbons from technical lignin as a promising pathway towards carbon emission neutrality for second-generation (2G) ethanol plants - Brener Felipe Melo Lima Gomes; Silvio Vaz Júnior; Leandro Vinícius Alves Gurgel (Journal of Cleaner Production, 2024)

Steam pretreatment of bone char for adsorption of refractory organics from electrodialysis concentrate produced by petroleum refinery - Felipe de Aquino Lima; Isabel Pereira da Silva; Paula Valamiel de Oliveira Vieira; Sônia Denise Ferreira Rocha; Patrícia da Luz Mesquita (Clean Technologies and Environmental Policy, 2024)

Anti-biofilm and anti-inflammatory active diterpene isolated from the fruit of Xylopia benthamii R.E.Fr. - Emilly J. S. P. de Lima; Weider H. P. Paz; Nállarett M. Dávila Cardozo; Ana Paula A. Boleti; Patrícia Souza e Silva; Lincoln T. H. Mukoyama; Felipe M. A. da Silva; Emmanoel V. Costa; Josean F. Tavares; Ludovico Migliolo; Hector H. F. Koolen (Natural Product Research, 2024)

Addressing coffee crop diseases: forecasting Phoma leaf spot with machine learning - Lucas Eduardo de Oliveira Aparecido; Pedro Antonio Lorençone; João Antonio Lorençone; Guilherme Botega Torsoni; Rafael Fausto de Lima; Felipe Padilha; Paulo Sergio de Souza; Glauco de Souza Rolim (Theoretical and Applied Climatology, 2024)

Cellular and molecular antiproliferative effects in 2D monolayer and 3D-cultivated HT-29 cells treated with zerumbone - Nayane de Oliveira Silva; Luan Vitor Alves de Lima; Liana Martins de Oliveira; Matheus Felipe da Silva; Amanda Passuello de Aguiar; Simone Cristine Semprebon; Phelipe Oliveira Favaron; Sandra Regina Lepri; Ingrid Felicidade; Mario Sergio Mantovani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Alterations in Redox Homeostasis and Profound Developmental Consequences Are at the Core of Sudden Gravity Change Responses of Sugarcane Plants - Lucas Felipe da Silva; Helaine Cristiane Silva; Diego Gomes Teixeira; Vladmir Vieira do Nascimento; Kellya Francisca Mendonça Barreto; Silvia Regina Batistuzzo de Medeiros; João Paulo Matos Santos Lima; Katia Castanho Scortecci (Journal of Plant Growth Regulation, 2024)

Application of sugarcane bagasse and peanut shell in natura as bioadsorbents for vinasse treatment - Felipe de Aquino Lima; Antônio Carvalho dos Santos Júnior; Boutros Sarrouh; Renata Carolina Zanetti Lofrano (Clean Technologies and Environmental Policy, 2024)

Valorization of winemaking residues as biochar for removing Ni(II) from real industrial painting process effluent in a fixed-bed column - Fernando de Lima Carvalho; Jaqueline Pozzada dos Santos; Salah Knani; Amani Alruwaili; Rejiane da Rosa Schio; Sabrina Frantz Lütke; Felipe Ketzer; Marcos Leandro Silva Oliveira; Luis Felipe Oliveira Silva; Guilherme Luiz Dotto (Environmental Science and Pollution Research, 2024)

Local attitudes towards conservation governance in a large tropical multiple-use Marine Protected Area in Brazil - José Gilmar Cavalcante de Oliveira Júnior; Ana Paula de Oliveira Santos; Ana Claudia Mendes Malhado; Carolina Neves Souza; Chiara Bragagnolo; Aline Olímpio dos Santos; Evelynne Letícia dos Santos Farias Cardoso de Barros; Felipe Alexandre Santos Vieira; Inaê Farias Vieira Dantas; Jacqueline Costa Aldabalde; João Vitor Campos-Silva; Johnny Antonio da Silva Lima; et al. (Ocean & Coastal Management, 2024)

Application of sugarcane bagasse and peanut shell in natura as bioadsorbents for vinasse treatment - Felipe de Aquino Lima; Antônio Carvalho dos Santos Júnior; Boutros Sarrouh; Renata Carolina Zanetti Lofrano (Clean Technologies and Environmental Policy, 2024)

Evaluation of dietary tryptophan requirement on growth, whole-body composition, and hematobiochemical parameters of tambaqui (Colossoma macropomum) in the fattening phase - Rafael Silva Marchão; Carlos Eduardo Copatti; Felipe Barbosa Ribeiro; Marcos Antonio Delmondes Bomfim; Maylanne Sousa de Lima; Vanessa Ferreira Batista; Aline da Silva Rocha; Gilmar Amaro Pereira; Thaisa Sales Costa; David Ramos da Rocha; Luiz Vítor Oliveira Vidal; José F. Bibiano Melo (Aquaculture International, 2024)

Modulation of fluoroquinolone resistance by Lippia origanoides Kunth in Staphylococcus aureus - Felipe Araújo de Alcantara Oliveira; Gabriella Maria Duarte Lemos; Jonas Nascimento de Sousa; Girlene Soares de Figueirêdo; Daniela Reis Joaquim de Freitas; Josie Haydée Lima Ferreira; Antonia Maria das Graças Lopes Citó; José de Sousa Lima Neto; José Pinto de Siqueira-Júnior; Bruna Caroline Gonçalves Vasconcelo de Lacerda; Henrique Douglas Melo Coutinho; Humberto Medeiros Barreto (Vegetos, 2024)

Beach ridge sequence evolution of Punta Verde, northern coast of the San Matías Gulf, Argentina - José Carlos Rodrigues Nunes; Eduardo Puhl; Salvador Aliotta; Elírio E. Toldo; Paula Nogueira Machado Schffer; Cristiano Fick; Francisco Pinheiro Lima-Filho; João Andrade dos Reis Junior; Gilberto Silveira dos Santos; Carla Annes Barros; Felipe Rafael Secco da Silva; Cristian Valenti Schenk (Journal of South American Earth Sciences, 2024)

An encoder–decoder deep neural network for binary segmentation of seismic facies - Gefersom Lima; Felipe André Zeiser; Ariane da Silveira; Sandro Rigo; Gabriel de Oliveira Ramos (Computers & Geosciences, 2024)

Transparency in the planning for the use of mining royalties in Brazilian municipalities - Fabio Giusti; Maria Pereira de Lima Green; Fernando de Freiras Lins; Fernando Ferreira de Castro; Felipe Soter de Mariz e Miranda (The Extractive Industries and Society, 2023)

RETRACTED: Collapse of scallop Nodipecten nodosus production in the tropical Southeast Brazil as a possible consequence of global warming and water pollution - Cristiane Thompson; Leonardo Bacha; Pedro Henrique C. Paz; Marcelo de Assis Passos Oliveira; Braulio Cherene Vaz Oliveira; Claudia Omachi; Caroline Chueke; Marcela de Lima Hilário; Michele Lima; Luciana Leomil; Thais Felix-Cordeiro; Thalya Lou Cordeiro da Cruz; et al. (Science of The Total Environment, 2023)

Chemical composition and antibacterial effects of Etlingera elatior (Jack) R.M. Smith against Staphylococcus aureus efflux pumps - Felipe de Sousa Ferreira; José Bezerra de Araújo Neto; Cícera Datiane de Morais Oliveira-Tintino; Ana Carolina Justino de Araújo; Jaime Ribeiro-Filho; Priscilla Ramos Freitas; Isaac Moura Araújo; Micheline Azevedo Lima; Francisco Roberto de Azevedo; Saulo Relison Tintino; Henrique Douglas Melo Coutinho; Daniela Maria do Amaral Ferraz Navarro (Chemico-Biological Interactions, 2023)

Effects of environmental factors and ecological integrity on semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha) diversity in Cerrado streams - Cleilton Lima Franco; Erlane José Cunha; Carlos Augusto Silva de Azevêdo; Felipe Ferraz Figueiredo Moreira (Journal of Insect Conservation, 2023)

Correction: Performance of the national institute of infectious diseases disability scale in HTLV-1-associated myelopathy/tropical spastic paraparesis - Felipe R. Schmidt; Evandro S. F. Coutinho; Marco A. Lima; Marcus T. T. Silva; Ana C. C. B. Leite; Igor O. Fonseca; Abelardo Q. C. Araujo (Journal of NeuroVirology, 2023)

Antinociceptive and anti-inflammatory properties of α-d-mannan from the yeast Kluyveromyces marxianus: evidence for a role in interleukin-6 inhibition - Renata Freitas de A. T. Calumby; Flávia Oliveira de Lima; Gildomar Lima Valasques Junior; Jener David Gonçalves Santos; Pedro Felipe Pereira Chaves; Lucimara Mach Côrtes Cordeiro; Cristiane Flora Villarreal; Milena Botelho Pereira Soares; Elisangela Fabiana Boffo; Sandra Aparecida de Assis (Archives of Microbiology, 2023)

Molecular systematics of tamarins with emphasis on genus Tamarinus (Primates, Callitrichidae) - Gerson Paulino Lopes; Fábio Rohe; Fabrício Bertuol; Érico Polo; João Valsecchi; Tamily Carvalho Melo Santos; Felipe Ennes Silva; Ivan Junqueira Lima; Ricardo Sampaio; Maria Nazareth Ferreira da Silva; Claudia Regina Silva; Jean Boubli; et al. (Zoologica Scripta, 2023)
The genus Saguinus comprises three principal clades that diverged in the Middle to Late Miocene. Their taxa are ecologically differentiated and allopatrically distributed. These clades were recently recognized as different genera, Saguinus , Tamarinus and Oedipomidas . In Tamarinus , the phylogenetic relationships among species/subspecies are poorly understood. Thus, in this study we present a comprehensive dated genomic phylogeny based on double digest restriction associated DNA for all known species and subspecies of Tamarinus . We also tested whether that Tamarinus imperator and Tamarinus subgrisescens are different species, as morphology‐based taxonomy, phenotypical divergences and mitochondrial genes recognized them as two different species. Additionally, we reconstructed time‐calibrated phylogenetics tree hypotheses of all extant species and subspecies of the genera Saguinus , Tamarinus and Oedipomidas . Our analysis robustly supported the phylogenetic hypothesis of all species/subspecies of the genus Tamarinus ; strongly supported a divergence between the three clades, Saguinus , Oedipomidas and Tamarinus ; and provided support for T . imperator and T . subgrisescens as distinct species. Therefore, we reiterate and ratify the division of Saguinus into three genera, supporting the taxonomic proposal for these genera.

Lagenocarpus rigidus (Cyperaceae) may facilitate the establishment of Catasetum gardneri (Orchidaceae) in restinga areas of Northeastern Brazil - Deivid Lucas de Lima da Costa; Ianara Tamyres Fonseca Borges; Tainan da Silva Sousa; Ariane Mendonça dos Anjos; Maura da Silva Costa Furtado; Wanderson Cunha Pereira; Felipe Fajardo Villela Antolin Barberena (Brazilian Journal of Botany, 2023)

Effects of the combination of vitamins C and E supplementation on oxidative stress, inflammation, muscle soreness, and muscle strength following acute physical exercise: meta-analyses of randomized controlled trials - Katieli Santos de Lima; Felipe Barreto Schuch; Natiele Camponogara Righi; Patricia Chagas; Mireli Hemann Lamberti; Gustavo Orione Puntel; Antonio Marcos Vargas da Silva; Luis Ulisses Signori (Critical Reviews in Food Science and Nutrition, 2023)

Machine learning for cyanobacteria mapping on tropical urban reservoirs using PRISMA hyperspectral data - Felipe N. Begliomini; Claudio C.F. Barbosa; Vitor S. Martins; Evlyn M.L.M. Novo; Rejane S. Paulino; Daniel A. Maciel; Thainara M.A. Lima; Ryan E. O'Shea; Nima Pahlevan; Marta C. Lamparelli (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Performance of the National Institute of Infectious Diseases disability scale in HTLV-1-associated myelopathy/tropical spastic paraparesis - Felipe R Schmidt; Evandro SF Coutinho; Marco A Lima; Marcus TT Silva; Ana CCB Leite; Igor O Fonseca; Abelardo QC Araujo (Journal of NeuroVirology, 2023)

Effect of the combined use of monensin with virginiamycin or bacitracin on beef cattle performance, liver gluconeogenesis, lipid metabolism and intramuscular fat content - José M. Oliveira Júnior; Bruno G.C. Homem; Daniel Cunha; Ítalo B.G. Lima; Aline C. Rodrigues; Felipe C. Maciel; Edmilson H.R. Domingues; German D. Ramírez-Zamudio; Priscilla D. Teixeira; Tathyane R.S. Gionbelli; Matheus H. Moretti; Daniel R. Casagrande; et al. (Animal Feed Science and Technology, 2023)

Effects of Passiflora cincinnata in murine models of nociception - Emmily Petícia do Nascimento Sales; Francisco Romero Cabral; Valterlúcio dos Santos Sales; Josefa Fernanda Evangelista de Lacerda; Luanna Gomes da Silva; Denise Bezerra Correia; Gyllyandeson de Araújo Delmondes; Cícera Norma Fernandes Lima; Álefe Brito Monteiro; Cícero Francisco Bezerra Felipe; Francisco Antonio Vieira dos Santos; Jaime Ribeiro-Filho; et al. (Biologia, 2023)

Mebendazole targets essential proteins in glucose metabolism leading gastric cancer cells to death - Emerson Lucena da Silva; Felipe Pantoja Mesquita; Dyane Rocha Aragão; Adrhyann Jullyanne de Sousa Portilho; Aline Diogo Marinho; Lais Lacerda Brasil de Oliveira; Luina Benevides Lima; Maria Elisabete Amaral de Moraes; Pedro Filho Noronha Souza; Raquel Carvalho Montenegro (Toxicology and Applied Pharmacology, 2023)

Essential oil encapsulation by electrospinning and electrospraying using food proteins: A review - Juliani Buchveitz Pires; Felipe Nardo dos Santos; Igor Henrique de Lima Costa; Dianini Hüttner Kringel; Elessandra da Rosa Zavareze; Alvaro Renato Guerra Dias (Food Research International, 2023)

α-D-mannan from Aureobasidium pullulans (CCMB 324): optimization extraction - Gildomar Lima Valasques Junior; Jener David Gonçalves Santos; Pedro Felipe Pereira Chaves; Lucimara Mach Côrtes Cordeiro; Elisangela Fabiana Boffo; Sandra Aparecida de Assis (Natural Product Research, 2023)

Integrated multitrophic aquaculture system applied to shrimp, tilapia, and seaweed (Ulva ohnoi) using biofloc technology - Ana Paula Mariane de Morais; Ivanilson Lima Santos; Ramon Felipe Siqueira Carneiro; Eric Arthur Bastos Routledge; Leila Hayashi; Marco Antônio de Lorenzo; Felipe do Nascimento Vieira (Aquaculture, 2023)

Characterization and subchronic oral toxicity of Pentaclethra macroloba (pracaxi) oil in Rattus norvegicus (lin. Wistar) - Bruna de Souza Eberhart; Claudia Marie Komiyama; Maria Fernanda de Castro Burbarelli; Vivian Aparecida Rios Castilho Heiss; Rodrigo Garófallo Garcia; Rafael Borges; Gisele Aparecida Felix; Claudia Andrea Lima Cardoso; Paulo Henrique Braz; Cássia Regina Teodoro; Felipe Cardoso Serpa; Erika Rosendo de Sena Gandra (Toxicon, 2023)

Effect of Crude Glycerin in the Feed of Lactating Goats on Concentrations of Essential and Toxic Metals in Serum, Urine, Milk, and Artisanal “Coalho” Cheese - Bruna Higino de Souza Silva; Rodrigo Barbosa de Andrade; Iago José Santos da Silva; Ayna Arramis Apolinário da Silva; Cristina Farias da Fonseca; Felipe Rosendo Correia; Esdras Lima de Carvalho Gueiros; Bruna Gomes Calaça Menezes; Emanuel Felipe de Oliveira Filho; João Paulo Ismério dos Santos Monnerat; Francisco Fernando Ramos de Carvalho; Pierre Castro Soares (Biological Trace Element Research, 2023)

Adsorption of chloroquine, propranolol, and metformin in aqueous solutions using magnetic graphene oxide nanocomposite - Bruna Figueiredo do Nascimento; Caroline Maria Bezerra de Araújo; Diana del Carmen Pinto Osorio; Luis Felipe Oliveira Silva; Guilherme Luiz Dotto; Jorge Vinícius Fernandes Lima Cavalcanti; Maurício Alves da Motta Sobrinho (Environmental Science and Pollution Research, 2023)

Occurrence of bean-associated cytorhabdovirus and cowpea mild mottle virus infecting cultivated and wild Passiflora spp. in Brazil - Andreza Henrique Vidal; Gustavo Pereira Felix; Emanuel Felipe Medeiros Abreu; Bruna Pinheiro-Lima; Monique Jacob Xavier Vianna; Isadora Nogueira; Ana Clara Rodrigues Abreu; Marcio Martinello Sanches; José Leonardo Santos-Jiménez; Raul Castro Carriello Rosa; Maitê Freitas Silva Vaslin; Fábio Gelape Faleiro; et al. (Crop Protection, 2023)

On the noxious black Amazonian scorpion, Tityus obscurus (Scorpiones, Buthidae): Taxonomic notes, biology, medical importance and envenoming treatment - Jonas Gama Martins; Karla de Castro Figueiredo Bordon; Jairo A. Moreno-González; Bruno Rafael Ribeiro de Almeida; Pedro P.O. Pardal; André Felipe de Araújo Lira; Denise M. Cândido; Eliane Candiani Arantes; Rudi Emerson de Lima Procópio (Toxicon, 2023)

Acute effects of intracerebroventricular administration of α-ketoisocaproic acid in young rats on inflammatory parameters - Franciele Rabelo; Isabela da S. Lemos; Camila P. Dal Toé; Débora D. Casagrande; Maria Luisa S. Freitas; Micaela R. Quadra; Igor R. Lima; Jaqueline S. Generoso; Monique Michels; Paulo C. L. Silveira; Felipe Dal Pizzol; Emilio Luiz Streck (Metabolic Brain Disease, 2023)

Evaluation of biometry and blood concentration of heavy metals in free-living Chelonia mydas with and without fibropapillomatosis in southern Brazil - Yohany Arnold Alfonso Pérez; Samara Rosolem Lima; Gustavo Martinez Souza; Thayana Gião; Felipe J.S. Bispo; Ana Maria Ferreira Reis; Juliana da Silva Leite; Kássia Valéria Gomes Coelho da Silva (Marine Pollution Bulletin, 2023)

First report of Nigrospora vesicularifera causing foot rot on sweet potato in Brazil - Thaís Regina Pintino De Almeida; Iwanne Lima Coelho; Leirson Salvador Bezerra Vasconcelos; Elder Felipe De Moura Silva; Letícia Rebeca De Araújo Barros; Maria Aparecida Pontes; Tarciana Silva Dos Santos; Willie Anderson Dos Santos Vieira; Marcos Paz Saraiva Câmara; Delson Laranjeira (Crop Protection, 2023)

In water Morita-Baylis-Hillman reactions of acrylates enabled by aqueous micellar catalysis using TPGS-750 M - Felipe C. Braga; Jamal Rafique; Roberto da Silva Gomes; Dênis P. de Lima; Adilson Beatriz (Sustainable Chemistry and Pharmacy, 2023)

Genotoxic effects of anthropogenic environments in the leaf litter-dwelling scorpion Tityus pusillus Pocock, 1893 (Scorpiones; Buthidae) - Aleson Aparecido da Silva; Érima Maria de Amorim; Maria Gislaine Pereira; Samuel Lima de Santana; Meykson Alexandre da Silva; André Felipe de Araujo Lira; Claudia Rohde (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2023)

Saline extract of Portulaca elatior leaves with photoprotective and antioxidant activities does not show acute oral and dermal toxicity in mice - Suéllen Pedrosa da Silva; Clarice Barbosa Lucena da Costa; Anderson Felipe Soares de Freitas; José Dayvid Ferreira da Silva; Wêndeo Kennedy Costa; Wênio Sandoval Filho Lima da Silva; Janaina Carla Barbosa Machado; Sandra Maria Souza da Silva; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares; Jacinto da Costa Silva Neto; Márcia Vanusa da Silva; et al. (Toxicological Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Sulfate supply decreases barium availability, uptake, and toxicity in lettuce plants grown in a tropical Ba-contaminated soil - Arnon Afonso de Souza Cardoso; Ana Paula Pereira Nunes; Éder Rodrigues Batista; Lorena del Carmen Hernandez Nataren; Márcio Felipe Pinheiro Neri Nunes; Fabrício Teixeira de Lima Gomes; Aline do Amaral Leite; Luiz Roberto Guimarães Guilherme; Valdemar Faquin; Maria Ligia de Souza Silva (Environmental Science and Pollution Research, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Sugarcane yeast with urea in replace of soybean meal in the diet of Murrah buffaloes does not cause metabolic, endocrine, and mineral disorders - Bruna Higino de Souza Silva; Rebeka Menezes Pontes; Ayna Arramis Apolinário da Silva; Esdras Lima de Carvalho Gueiros; Emanuel Felipe de Oliveira Filho; Daniel da Silva Praia; Daniel Nunes de Araújo Gonçalves; Tomás Guilherme Pereira da Silva; Ricardo Alexandre Silva Pessoa; Cláudio Coutinho Bartolomeu; Pierre Castro Soares (Tropical Animal Health and Production, 2023)

Metalloproteomic approach to liver tissue of rats exposed to mercury - Maria Gabriela A. Santiago; Victor Diego Faria; Felipe Dalmazzo Cirinêu; Lucas Luan de Lima Queiroz da Silva; Emerson Carlos de Almeida; Nubya Gonçalves Cavallini; José Cavalcante Souza Vieira; Ana Angélica Henrique Fernandes; Camila Pereira Braga; Luís Fabrício Zara; Marília Afonso Rabelo Buzalaf; Jiri Adamec; et al. (Chemosphere, 2023)

Cold damage affects the quality of noni fruits (Morinda citrifolia L.) - Francisco Tadeu Dantas de Lima; Laesio Pereira Martins; Belísia Lúcia Moreira Diniz Toscano; Eliane de Sousa Costa; Weysser Felipe Cândido de Souza; Fernando Azevedo de Lucena; Josinaldo Florêncio da Silva Filho; Solange de Sousa (Biocatalysis and Agricultural Biotechnology, 2023)

Eggshell microbiome as a potential microbial reservoir in a cavity nesting bird - Felipe Campos-Cerda; Roxana Torres; Liliana Nava; Cecilia Cuatianquiz-Lima; Yendi Navarro-Noya; Bibiana Montoya (Journal of Ornithology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Isolation by distance and past climate resistance shaped the distribution of genealogical lineages of a neotropical lizard - Felipe Camurugi; Eliana F. Oliveira; Guilherme S. Lima; Ricardo Marques; Felipe M. Magalhães; Guarino R. Colli; Daniel O. Mesquita; Adrian A. Garda (Systematics and Biodiversity, 2022)

Coconut fruit pulp by-product in the diet of sheep - Felipe José Santos da Silva; Dorgival Morais de Lima Júnior; Vitor Visintin Silva de Almeida; Aline Cardoso Oliveira; Beatriz Dantas Oliveira Fernandes; Anaiane Pereira Souza; Francisco Fernando Ramos de Carvalho; Ariosvaldo Nunes de Medeiros (Tropical Animal Health and Production, 2022)

IGF-1 increases survival of CD4+ lineage in a 2D model of thymocyte/thymic stromal cell co-culture - Larissa Fernanda de Araújo Vieira; Marvin Paulo Lins; Felipe Lima Porto; Salete Smaniotto; Maria Danielma dos Santos Reis (In Vitro Cellular & Developmental Biology - Animal, 2022)

Rpp-Gene pyramiding confers higher resistance level to Asian soybean rust - Maiara Cecilia Panho; Rogê Afonso Tolentino Fernandes; Caroline Patrícia Menegazzi; Otávio Ramos Campagnolli; Felipe Chade de Quadra; Laura Alexandra Madella; Daniela Meira; Gaspar Malone; Salvador Lima Brito Junior; Giovani Benin (Euphytica, 2022)

A review of the main tectonic settings of Palaeo-and-Mesoarchean ore deposits in the northern São Francisco Craton, NE Brazil - Johildo Salomão Figueirêdo Barbosa; Rafael Gordilho Barbosa; Felipe Padilha Leitzke; Angela Beatriz de Menezes Leal; Rejane Lima Luciano; Basílio Elesbão da Cruz Filho; Jocilene Santana; Antônio Marcos Vitória de Moraes (International Geology Review, 2022)

Meteorological droughts and water resources: Historical and future perspectives for Rio Grande do Norte state, Northeast Brazil - Felipe Jeferson de Medeiros; Rafaela dos Santos Gomes; Maytê Duarte Leal Coutinho; Kellen Carla Lima (International Journal of Climatology, 2022)
The objective of this study was to relate the meteorological droughts in the present climate (1991–2016) and their projections for near future (2025–2050) under the RCP2.6 and RCP8.5 with the water resources of the Rio Grande do Norte (RN) state, located in the Northeast Brazil. For this, we proposed a relationship between the categories of the Standardized Precipitation Evapotranspiration Index (SPEI) and the water variation of four reservoirs. The SPEI was calculated using the regional climate models (RCM) and its ensemble (obtained through the principal component analysis – RCM_Ens_PCA) from the CORDEX‐CORE project for the South America domain (SAM‐22). The results indicated that approximately 70% of the times when the SPEI was classified in drought categories (SPEI ≤ −0.50), there was a decrease in the stored volume of the reservoirs, being this impact more evident in years in which the SPEI values were more intense. For wet years (SPEI > 0.50), we found that in 80.0% of the times there was an increase in the stored volume. For the near‐future climate, the analyses indicated higher spread between simulations, indicating greater uncertainties. However, the RCM members and the ensemble projected a predominance of more wet (dry) years during the 2025–2033 (2042–2047) periods, especially in the RCP2.6. Thus, it is expected that the RN state would not face water scarcity from 2025 to 2033 but would probably face water deficit from 2042 to 2047. Therefore, our results show information that can be useful for decision‐makers to plan strategic actions for water security.

The multiple functions of PrPC in physiological, cancer, and neurodegenerative contexts - Izabella Grimaldi; Felipe Saceanu Leser; José Marcos Janeiro; Bárbara Gomes da Rosa; Ana Clara Campanelli; Luciana Romão; Flavia Regina Souza Lima (Journal of Molecular Medicine, 2022)

Applications of chitosan to the roots and shoots change the accumulation pattern of cadmium in Talinum patens (Talinaceae) cuttings - Samuel Vitor Assis Machado de Lima; Daniele Maria Marques; Matheus Felipe Soares Silva; Leticia Aparecida Bressanin; Paulo César Magalhães; Thiago Corrêa de Souza (Environmental Science and Pollution Research, 2022)

Trichosporon asahii causing subcutaneous mycoses in an immunocompetent patient: case report and a minireview - Wdson Luis Lima Kruschewsky; Pedro Massaroni-Peçanha; Simone Bravim Maifrede; Marcelo Santos Leite; Tâmea Aparecida Linhares Pôssa; Felipe Alberto-Lei; Rodrigo Cayô; Paulo Mendes Peçanha; Sarah Santos Gonçalves (Brazilian Journal of Microbiology, 2022)

Essential oil of Piper purusanum C.DC (Piperaceae) and its main sesquiterpenes: biodefensives against malaria and dengue vectors, without lethal effect on non-target aquatic fauna - André C. de Oliveira; Rejane C. Simões; Carlos A. P. Lima; Felipe M. A. da Silva; Sergio M. Nunomura; Rosemary A. Roque; Wanderli P. Tadei; Rita C. S. Nunomura (Environmental Science and Pollution Research, 2022)

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Lambs fed diets containing by-product from coconut processing: histomorphometry characteristics in the digestive and renal systems - Felipe José Santos da Silva; Dorgival Morais de Lima Júnior; Ricardo Romão Guerra; Vitor Visintin Silva de Almeida; Julimar do Sacramento Ribeiro; Beatriz Dantas Oliveira Fernandes; Anaiane Pereira Souza; Ariosvaldo Nunes de Medeiros (Tropical Animal Health and Production, 2022)

Chemical and antibacterial analysis of Cinnamomum verum leaves extract and fractions against multidrug resistant bacteria - Liliane Bezerra de Lima; Wliana Alves Viturino da Silva; Sarah Luanne Silva; Ewelyn Cintya Felipe dos Santos; Janaína Carla Barbosa Machado; Thamara Figueiredo Procópio; Maiara Celine de Moura; Thiago Henrique Napoleão; Magda Rhayanny Assunção Ferreira; Luiz Alberto Lira Soares (Natural Product Research, 2022)

Polyethylene microplastics and substrate availability can affect emergence responses of the freshwater insect Chironomus sancticaroli - Gleyson B. Castro; Aline C. Bernegossi; Mayara C. Felipe; Allan P. Ogura; Mara R. de Lima e Silva; Juliano J. Corbi (Ecotoxicology, 2022)

Genetic markers indicate that hybrids of Pseudoplatystoma (Siluriformes, Pimelodidae) are reproducing in natural environments in southeastern Brazil - Diogo Freitas-Souza; André Batista Nobile; Fernanda Dotti do Prado; Érica Alves Serrano; Felipe Pontieri Lima; Fausto Foresti; Fábio Porto-Foresti; Claudio Oliveira (Biological Invasions, 2022)

Assessing Caffeine and Linear Alkylbenzene Sulfonate Effects on Molting and Reproduction of Daphnia magna by Quantitative and Qualitative Approaches - Mara R. de Lima e Silva; Aline C. Bernegossi; Gleyson B. Castro; Allan P. Ogura; Juliano J. Corbi; Mayara C. Felipe (Water, Air, & Soil Pollution, 2022)

Synthesis and application of graphene oxide as a nanoadsorbent to remove Cd (II) and Pb (II) from water: adsorption equilibrium, kinetics, and regeneration - Brener Felipe Melo Lima Gomes; Caroline Maria Bezerra de Araújo; Bruna Figueiredo do Nascimento; Eleonora Maria Pereira de Luna Freire; Mauricio Alves Da Motta Sobrinho; Marilda Nascimento Carvalho (Environmental Science and Pollution Research, 2022)

Diagnostic Yield of Whole Exome Sequencing for Adults with Ataxia: a Brazilian Perspective - Felipe Franco da Graça; Thiago M. Peluzzo; Luciana Cardoso Bonadia; Alberto Rolim Muro Martinez; Fabricio Diniz de Lima; José Luiz Pedroso; Orlando G. P. Barsottini; Maria Thereza Drummond Gama; Fulya Akçimen; Patrick A. Dion; Guy A. Rouleau; Wilson Marques; et al. (The Cerebellum, 2022)

Inclusion of β-1,3/1,6-glucan in the ornamental fish, Jewel tetra (Hyphessobrycon eques), and its effects on growth, blood glucose, and intestinal histology - Pâmela Juliana Furlan-Murari; Ed Christian Suzuki de Lima; Felipe Pinheiro de Souza; Angela Maria Urrea-Rojas; Andreia Carla Eugenio Pupim; Eduardo José de Almeida Araújo; Paulo César Meletti; Cindy Namie Seino Leal; Letícia Lima Fernandes; Nelson Mauricio Lopera-Barrero (Aquaculture International, 2022)

Unmanned aerial vehicle to evaluate frost damage in coffee plants - Diego Bedin Marin; Gabriel Araújo e Silva Ferraz; Felipe Schwerz; Rafael Alexandre Pena Barata; Rafael de Oliveira Faria; Jessica Ellen Lima Dias (Precision Agriculture, 2021)

Tolerance mechanisms and irrigation management to reduce iron stress in irrigated rice - Felipe de Campos Carmona; Janete Mariza Adamski; Andriele Wairich; Joseane Biso de Carvalho; Gustavo Gomes Lima; Ibanor Anghinoni; Isadora Rodrigues Jaeger; Paulo Regis Ferreira da Silva; Tatiana de Freitas Terra; Janette Palma Fett; Filipe Selau Carlos (Plant and Soil, 2021)

CXCL12-driven thymocyte migration is increased by thymic epithelial cells treated with prolactin in vitro - Návylla Candeia Medeiros; Felipe Lima Porto; Clarice Agudo de Menezes; Maria Danielma dos Santos Reis; Salete Smaniotto; Marvin Paulo Lins (Journal of Biosciences, 2021)

Development of microsatellite markers and evaluation of genetic diversity of the Amazonian ornamental fish Pterophyllum scalare - Victor César Freitas Pandolfi; Andrei Lincoln Yamachita; Felipe Pinheiro de Souza; Sara Mataroli de Godoy; Ed Christian Suzuki de Lima; Daniele Cassiano Feliciano; Ulisses de Pádua Pereira; Jayme Aparecido Povh; Denise Rocha Ayres; Annaiza Braga Bignardi; Jefferson Murici Penafort; Claudete de Fátima Ruas; et al. (Aquaculture International, 2021)

Cryptic diversity in the mayfly Leptohyphodes inanis (Pictet) (Ephemeroptera: Leptohyphidae) across water basins in Southeastern Brazil - Paula Malaquias Souto; Luiz Felipe Lima da Silveira; Daniela Maeda Takiya; Frederico Falcão Salles (Systematics and Biodiversity, 2021)

Use of Trajectory Regression Analysis to Understand High-PM10 Episodes: a Case Study in Limeira, Brazil - Danilo Covaes Nogarotto; Felipe Lima Campos de Souza; Flávia Noronha Dutra Ribeiro; Simone Andréa Pozza (Water, Air, & Soil Pollution, 2021)

Expression of a DREB 5-A subgroup transcription factor gene from Ricinus communis (RcDREB1) enhanced growth, drought tolerance and pollen viability in tobacco - Tomas Felipe Costa do Rego; Mirella Pupo Santos; Glaucia Barbosa Cabral; Thaís de Moura Cipriano; Natália Lima de Sousa; Otacílio Antônio de Souza Neto; Francisco José Lima Aragão (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Characterization of Headache in COVID-19: a Retrospective Multicenter Study - Rafael César dos Anjos de Paula; Thaís de Maria Frota Vasconcelos; Francisco Bruno Santana da Costa; Lara Albuquerque de Brito; Danielle Mesquita Torres; Alissa Elen Formiga Moura; Danilo Nunes Oliveira; Guilherme Alves de Lima Henn; Pedro Gustavo Barros Rodrigues; Isabelle de Sousa Pereira; Ianna Lacerda Sampaio Braga; Felipe Araújo Rocha; et al. (Molecular Neurobiology, 2021)

Laboratory diagnosis of mange-causing mites in dogs using a modified centrifugation-flotation technique in sucrose solution - Felipe Boniedj Ventura Alvares; Vivian Silva Rosa Veleda Meireles; Juliana Trajano da Silva; Larissa Claudino Ferreira; Jossiara Abrante Rodrigues; Roberto Alves Bezerra; Brendo Andrade Lima; Thais Ferreira Feitosa; Vinícius Longo Ribeiro Vilela (Experimental and Applied Acarology, 2021)

Correction to: Leishmania infantum Infection in a domestic cat: A real threat or an occasional finding? - Lais Kelly Amâncio Ribeiro Berenguer; Caio Felipe Cavalcanti de Andrade Gomes; Janilene de Oliveira Nascimento; Jéssica Cristianne Mazer Bernardi; Victor Fernando Santana Lima; Jaqueline Bianque de Oliveira; Carlos Alberto do Nascimento Ramos; Rafael Antonio Nascimento Ramos; Leucio Câmara Alves (Acta Parasitologica, 2021)

Bauhinia holophylla (Bong.) Steud. leaves-derived extracts as potent anti-dengue serotype 2 - Michelli dos Santos; Thaiz Rodrigues Teixeira; Felipe Rocha da Silva Santos; William Gustavo Lima; Ariane Coelho Ferraz; Nathália Lucca Silva; Flávio José Leite; João Máximo Siqueira; Walter Luyten; Ana Hortência Fonseca de Castro; José Carlos de Magalhães; Jaqueline Maria Siqueira Ferreira (Natural Product Research, 2021)

Methylmercury-Induced Toxicopathologic Findings in Salivary Glands of Offspring Rats After Gestational and Lactational Exposure - Priscila Cunha Nascimento; Maria Karolina Martins Ferreira; Karolyny Martins Balbinot; Sérgio Melo Alves-Júnior; João de Jesus Viana Pinheiro; Felipe Martins Silveira; Manoela Domingues Martins; Maria Elena Crespo-Lopez; Rafael Rodrigues Lima (Biological Trace Element Research, 2021)

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Effluent treatment using activated carbon adsorbents: a bibliometric analysis of recent literature - Danilo Henrique da Silva Santos; Juliana Cristina Pereira Lima Paulino; Gleybhson Felipe dos Santos Alves; Leonardo Mendonça Tenório de Magalhães Oliveira; Patrícia de Carvalho Nagliate; José Leandro da Silva Duarte; Lucas Meili; Josealdo Tonholo; Carmem Lucia de Paiva e Silva Zanta (Environmental Science and Pollution Research, 2021)

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

Functional biogeography of Neotropical moist forests: Trait–climate relationships and assembly patterns of tree communities - Bruno X. Pinho; Marcelo Tabarelli; Cajo J. F. ter Braak; S. Joseph Wright; Víctor Arroyo‐Rodríguez; Maíra Benchimol; Bettina M. J. Engelbrecht; Simon Pierce; Peter Hietz; Bráulio A. Santos; Carlos A. Peres; Sandra C. Müller; et al. (Global Ecology and Biogeography, 2021)
Aim Here we examine the functional profile of regional tree species pools across the latitudinal distribution of Neotropical moist forests, and test trait–climate relationships among local communities. We expected opportunistic strategies (acquisitive traits, small seeds) to be overrepresented in species pools further from the equator, but also in terms of abundance in local communities in currently wetter, warmer and more seasonal climates. Location Neotropics. Time period Recent. Major taxa studied Trees. Methods We obtained abundance data from 471 plots across nine Neotropical regions, including c . 100,000 trees of 3,417 species, in addition to six functional traits. We compared occurrence‐based trait distributions among regional species pools, and evaluated single trait–climate relationships across local communities using community abundance‐weighted means (CWMs). Multivariate trait–climate relationships were assessed by a double‐constrained correspondence analysis that tests both how CWMs relate to climate and how species distributions, parameterized by niche centroids in climate space, relate to their traits. Results Regional species pools were undistinguished in functional terms, but opportunistic strategies dominated local communities further from the equator, particularly in the Northern Hemisphere. Climate explained up to 57% of the variation in CWM traits, with increasing prevalence of lower‐statured, light‐wooded and softer‐leaved species bearing smaller seeds in more seasonal, wetter and warmer climates. Species distributions were significantly but weakly related to functional traits. Main conclusions Neotropical moist forest regions share similar sets of functional strategies, from which local assembly processes, driven by current climatic conditions, select for species with different functional strategies. We can thus expect functional responses to climate change driven by changes in relative abundances of species already present regionally. Particularly, equatorial forests holding the most conservative traits and large seeds are likely to experience the most severe changes if climate change triggers the proliferation of opportunistic tree species.

Biochar and Cow Manure on Chemical and Microbial Community in Regosol with Bean - Cíntia Caroline Gouveia da Silva; Erika Valente de Medeiros; Giselle Gomes Monteiro Fracetto; Felipe José Cury Fracetto; Argemiro Pereira Martins Filho; José Romualdo de Sousa Lima; Gustavo Pereira Duda; Diogo Paes da Costa; Claude Hammecker (Journal of Soil Science and Plant Nutrition, 2021)

Leishmania infantum Infection in a Domestic Cat: A Real Threat or an Occasional Finding? - Lais Kelly Amâncio Ribeiro Berenguer; Caio Felipe Cavalcanti de Andrade Gomes; Janilene de Oliveira Nascimento; Jéssica Cristianne Mazer Bernardi; Victor Fernando Santana Lima; Jaqueline Bianque de Oliveira; Carlos Alberto do Nascimento Ramos; Rafael Antonio Nascimento Ramos; Leucio Câmara Alves (Acta Parasitologica, 2021)

Invasive plants in Brazil: climate change effects and detection of suitable areas within conservation units - Luiza Gabriela Fulgêncio-Lima; André Felipe A. Andrade; Bruno Vilela; Dilermando P. Lima-Júnior; Rodrigo Antônio de Souza; Luciano F. Sgarbi; Juliana Simião-Ferreira; Paulo De Marco Jr; Daniel P. Silva (Biological Invasions, 2021)

Evaluation of Cerebellar Function and Integrity of Adult Rats After Long-Term Exposure to Aluminum at Equivalent Urban Region Consumption Concentrations - Rafael Monteiro Fernandes; Priscila Cunha Nascimento; Maria Karolina Martins; Walessa Alana Bragança Aragão; Luis Felipe Sarmiento Rivera; Leonardo Oliveira Bittencourt; Sabrina C. Cartágenes; Maria Elena Crespo-Lopez; Cristiane do Socorro Ferraz Maia; Rafael Rodrigues Lima (Biological Trace Element Research, 2021)

Chemical composition and larvicidal activity of the essential oil from the leaves of Onychopetalum periquino (Rusby) D.M. Johnson & N.A. Murray - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Jessica B. Maciel; Carromberth C. Fernandes; André C. de Oliveira; Wanderli P. Tadei; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2021)

Spatial distribution of Toxoplasma gondii in cows and associated risk factors - Larissa Alves; Jaqueline Lima; Jade Melo; Ana Maria de Castro; Vando Soares; Gabriel Rossi; Weslen Teixeira; Lorena Ferreira; Breno Cruz; Gustavo Felippelli; Vanessa Oliveira; Paula Brom; et al. (Tropical Animal Health and Production, 2021)

Geodiversity Index Map of Rio Grande do Norte State, Northeast Brazil: Cartography and Quantitative Assessment - Marília Cristina Santos Souza Dias; Jéssica Oliveira Domingos; Silas Samuel dos Santos Costa; Marcos Antonio Leite do Nascimento; Matheus Lisboa Nobre da Silva; Larissa Praxedes Granjeiro; Rafael Felipe de Lima Miranda (Geoheritage, 2021)

Ecophysiology and morphology of seed germination and seedling emergence of Combretum lanceolatum Pohl ex Eichler - Vanessa Couto Soares; Wanderleia de Vargas; Ana Maria de Menezes Zanoni; L. Felipe Daibes; Liana Baptista de Lima (Brazilian Journal of Botany, 2021)

Sugarcane Harvester for In-field Data Collection: State of the Art, Its Applicability and Future Perspectives - Lucas de Paula Corrêdo; Tatiana Fernanda Canata; Leonardo Felipe Maldaner; Jeovano de Jesus Alves de Lima; José Paulo Molin (Sugar Tech, 2021)

Correction to: Comparative testis structure and function in three representative mice strains - Carolina Felipe Alves de Oliveira; Nathalia de Lima e Martins Lara; Bárbara Ramalho Ladeira Cardoso; Luiz Renato de França; Gleide Fernandes de Avelar (Cell and Tissue Research, 2021)

Plastic Ingestion by Commercial and Non-Commercial Fishes from a Neotropical River Basin - Felipe P. Lima; Valter M. Azevedo-Santos; Viviane M. R. Santos; Ana P. Vidotto-Magnoni; Cláudio L. Soares; Felipe V. Manzano; André B. Nobile (Water, Air, & Soil Pollution, 2021)

Otoliths-composed gelatin/sodium alginate scaffolds for bone regeneration - Daisy Pereira Valido; Wilson Déda Gonçalves Júnior; Maria Eliane de Andrade; Allan Andrade Rezende; Felipe Mendes de Andrade de Carvalho; Renata de Lima; Gabriela das Graças Gomes Trindade; Caio de Alcântara Campos; Ana Maria Santos Oliveira; Eloísa Portugal Barros Silva Soares de Souza; Luiza Abrahão Frank; Silvia Stanisçuaski Guterres; et al. (Drug Delivery and Translational Research, 2020)

Comparative testis structure and function in three representative mice strains - Carolina Felipe Alves de Oliveira; Nathalia de Lima e Martins Lara; Bárbara Ramalho Ladeira Cardoso; Luiz Renato de França; Gleide Fernandes de Avelar (Cell and Tissue Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biosynthesis and metabolic actions of simple phenolic acids in plants - Rogério Marchiosi; Wanderley Dantas dos Santos; Rodrigo Polimeni Constantin; Rogério Barbosa de Lima; Anderson Ricardo Soares; Aline Finger-Teixeira; Thatiane Rodrigues Mota; Dyoni Matias de Oliveira; Marcela de Paiva Foletto-Felipe; Josielle Abrahão; Osvaldo Ferrarese-Filho (Phytochemistry Reviews, 2020)

Sustainable neighborhoods in Brazil: a comparison of concepts and applications - Ana Paula Lima Vilela; Michelle Simões Reboita; Luiz Felipe Silva; Miglena Krasimirova Gerasimova; Daniele Ornaghi Sant’Anna (Environment, Development and Sustainability, 2020)

Status and recommendations for sustainable freshwater aquaculture in Brazil - André B. Nobile; Almir M. Cunico; Jean R. S. Vitule; Jamile Queiroz; Ana P. Vidotto‐Magnoni; Diego A. Z. Garcia; Mário L. Orsi; Felipe P. Lima; Aline A. Acosta; Reinaldo J. da Silva; Fernanda D. do Prado; Fábio Porto‐Foresti; et al. (Reviews in Aquaculture, 2020)
Brazil is a megadiverse country and is participant of fundamental environmental agreements for biodiversity conservation. However, the internal politics and the cultures that affect negatively the ecological integrity in Brazilian freshwater need to be improved on the condition of sustainable management. Scientific community, the government and stakeholders are in constant conflicts of goals. Meanwhile, the current model for Brazilian aquaculture shows problems of ecological impact due to the lack of appropriated planning and legislation to the aquatic biota. The non‐recognition of sustainable census incorporated in its environmental politics reflects in an archaic and unsustainable management, with the following characters: a non‐specific approach for technical management, the indiscriminate use of interspecific hybrids and non‐native species and the lack of skilled labour. The potential impact on native species and the introduction of pathogens are the main negative effects on aquatic biota. This way, the aim of this article is to elucidate the conflicts of interests and ecological effects of fish aquaculture in Brazil, besides providing good practices and sustainable alternatives for management.

Factors affecting occurrence of demodecosis by Demodex bovis in Sindhi cattle (Bos indicus) - José Nerivaldo de Araújo Wanderley; Ana Célia Rodrigues Athayde; José Fabio Paulino de Moura; Leilson Rocha Bezerra; Antônio Fernando de Melo Vaz; Ednaldo Queiroga de Lima; Juliana Paula Felipe de Oliveira; Wilson Wouflan Silva (Tropical Animal Health and Production, 2020)

Strengths and Weaknesses of a Hybrid Post-disaster Management Approach: the Doce River (Brazil) Mine-Tailing Dam Burst - Ana T. Lima; Felipe A. Bastos; Fernando Jakes Teubner; Renato R. Neto; Andrew Cooper; Gilberto F. Barroso (Environmental Management, 2020)

High frequency of Chlamydia pneumoniae and risk factors in children with acute respiratory infection - Matheus Silva Alves; Marilha da Silva Cariolano; Hivylla Lorrana dos Santos Ferreira; Elen Sousa de Abreu Silva; Karen Karollynny Pereira Felipe; Silvio Gomes Monteiro; Eduardo Martins de Sousa; Afonso Gomes Abreu; Lee Ann Campbell; Michael E. Rosenfeld; Mario Hiroyuki Hirata; Rosario Dominguez Crespo Hirata; et al. (Brazilian Journal of Microbiology, 2020)

Downscaling projections of climate change in Sao Tome and Principe Islands, Africa - Sin Chan Chou; André de Arruda Lyra; Jorge Luís Gomes; Daniel Andrés Rodriguez; Minella Alves Martins; Nicole Costa Resende; Priscila da Silva Tavares; Claudine Pereira Dereczynski; Isabel Lopes Pilotto; Alessandro Marques Martins; Luís Felipe Alves de Carvalho; José Luiz Lima Onofre; et al. (Climate Dynamics, 2020)

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

Ruminal and histological characteristics and nitrogen balance in lamb fed diets containing cactus as the only roughage - Kleitiane Balduino da Silva; Juliana Silva de Oliveira; Edson Mauro Santos; Felipe Queiroga Cartaxo; Ricardo Romão Guerra; Aelson Fernandes do Nascimento de Souza; Ana Cecília Souza Muniz; Gabriel Ferreira de Lima Cruz (Tropical Animal Health and Production, 2020)

Effects of the solid lipid nanoparticle of carvacrol on rodents with lung injury from smoke inhalation - Fernanda O. Carvalho; Érika R. Silva; Paula S. Nunes; Fernanda A. Felipe; Karen P. P. Ramos; Luiz Augusto S. Ferreira; Viviane N. B. Lima; Saravanan Shanmugam; Alan Santos Oliveira; Sílvia S. Guterres; Enilton A. Camargo; Tassia Virginia Cravalho Olivera; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Synthesis, anti-proliferative activity, theoretical and 1H NMR experimental studies of Morita–Baylis–Hillman adducts from isatin derivatives - Vinicius B. M. Brito; Gilmar F. Santos; Thiago D. S. Silva; Júlia L. C. Souza; Gardenia C. G. Militão; Felipe T. Martins; Fábio P. L. Silva; Boaz G. Oliveira; Edigenia C. C. Araújo; Mário L. A. A. Vasconcellos; Claudio G. Lima-Júnior; Edilson B. Alencar-Filho (Molecular Diversity, 2020)

Species richness and functional structure of fish assemblages in three freshwater habitats: effects of environmental factors and management - Jamile Queiroz‐Sousa; Sally A. Keith; Gianmarco S. David; Heleno Brandão; André B. Nobile; Jaciara V. K. Paes; Ana C. Souto; Felipe P. Lima; Reinaldo J. Silva; Raoul Henry; Katherine Richardson (Journal of Fish Biology, 2019)
In this study, the inverted trophic hypothesis was tested in the freshwater fish communities of a reservoir. The distribution of fish species in three freshwater habitats in the Jurumirim Reservoir, Brazil, was examined using both species richness and the relative proportions of different trophic groups. These groups were used as a proxy for functional structure in an attempt to test the ability of these measures to assess fish diversity. Assemblage structures were first described using non‐metric multidimensional scaling (NMDS). The influence of environmental conditions for multiple fish assemblage response variables (richness, total abundance and abundance per trophic group) was tested using generalised linear mixed models (GLMM). The metric typically employed to describe diversity; that is, species richness, was not related to environmental conditions. However, absolute species abundance was relatively well explained with up to 54% of the variation in the observed data accounted for. Differences in the dominance of trophic groups were most apparent in response to the presence of introduced fish species: the iliophagous and piscivorous trophic groups were positively associated, while detritivores and herbivores were negatively associated, with the alien species. This suggests that monitoring functional diversity might be more valuable than species diversity for assessing effects of disturbances and managements policies on the fish community.

Lernaea cyprinacea (Copepoda: Lernaeidae) in Piabarchus stramineus (Characiformes: Characidae) from the Taquari River, São Paulo State, Brazil - Rodrigo Bravin Narciso; Aline Angelina Acosta; André Batista Nobile; Felipe Pontieri de Lima; Diogo Freitas-Souza; Reinaldo José da Silva (Biologia, 2019)

The role of strict nature reserves in protecting genetic diversity in a semiarid vegetation in Brazil - Emanuel M. Fonseca; Fernanda P. Werneck; Marcelo Gehara; Eliana F. Oliveira; Felipe de M. Magalhães; Flávia M. Lanna; Guilherme S. Lima; Ricardo Marques; Daniel O. Mesquita; Gabriel C. Costa; Guarino R. Colli; Adrian A. Garda (Biodiversity and Conservation, 2019)

An approach to improve direct sensor orientation using the integration of photogrammetric and lidar datasets - Felipe André Lima Costa; Edson Aparecido Mitishita (International Journal of Remote Sensing, 2019)

Disseminated melanized fungal infection due to Cladosporium halotolerans in a dog coinfected with canine adenovirus-1 and canine parvovirus-2 - Selwyn Arlington Headley; Mariana de Mello Zanim Michelazzo; Bruno Elias; Nayara Emily Viana; Yuri Lima Pereira; Lucienne Garcia Pretto-Giordano; Jhonata Fragoso da Silva; Felipe Eduardo Scardovelli da Silva; Laurival Antonio Vilas-Boas; Karina Keller Marques da Costa Flaiban; Amauri Alcindo Alfieri; Lucas Alécio Gomes (Brazilian Journal of Microbiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Environmental improvement in the printing industry: the case study of self-adhesive labels - Diego Lima Medeiros; Felipe Luiz Braghirolli; Heloisa Ramlow; Gabriela Neves Ferri; Asher Kiperstok (Environmental Science and Pollution Research, 2019)

Assessment of acute toxicity and cytotoxicity of fluorescent markers produced by cardanol and glycerol, which are industrial waste, to different biological models - Bruno Ivo Pelizaro; Felipe Camargo Braga; Bruno do Amaral Crispim; Luiz Guilherme Maiolino Lacerda de Barros; Lucas Roberto Pessatto; Edwin José Torres Oliveira; Juliana Miron Vani; Antonio Pancrácio de Souza; Alexeia Barufatti Grisolia; Andréia Conceição Milan Brochado Antoniolli-Silva; Dênis Pires de Lima; Jeandre Augusto dos Santos Jaques; et al. (Environmental Science and Pollution Research, 2019)

Milk production and composition, food consumption, and energy balance of postpartum crossbred Holstein-Gir dairy cows fed two diets of different energy levels - Gustavo Bervian dos Santos; Felipe Zandonadi Brandão; Lilian dos Santos Ribeiro; Alexandre Lima Ferreira; Mariana Magalhães Campos; Fernanda Samarini Machado; Bruno Campos de Carvalho (Tropical Animal Health and Production, 2019)

Predicting Long-term Cognitive Dysfunction in Survivors of Critical Illness with Plasma Inflammatory Markers: a Retrospective Cohort Study - Marcus Maciel; Sabrina Ronconi Benedet; Elizabeth Buss Lunardelli; Henrique Delziovo; Rayane Lima Domingues; Francieli Vuolo; Cristiane Damiani Tomasi; Roger Walz; Cristiane Ritter; Felipe Dal-Pizzol (Molecular Neurobiology, 2019)

Emerging and Traditional Organic Markers in Areas with Multiple Anthropogenic Activities: Development of an Analytical Protocol and Its Application in Environmental Assessment Studies - Pollyana C. V. de Morais; Allyne F. Gama; Gabrielle M. Fernandes; Andre H. B. Oliveira; Marcielly F. B. Lima; Felipe R. dos Santos; Davi A. Martins; Ronaldo F. Nascimento; Rivelino M. Cavalcante (Bulletin of Environmental Contamination and Toxicology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Thermodynamic Characterization of Mixed Monolayers of a Novel Oxazolidine Derivative and Phospholipids - Felipe de Sá Rocha; Rafael Ramos da Silva; Gustavo Henrique Ribeiro Codeceira; Maria do Carmo Alves de Lima; Ivan da Rocha Pitta; Maria Danielly Lima de Oliveira; César Augusto Souza de Andrade (The Journal of Membrane Biology, 2018)

Megaviridae-like particles associated with Symbiodinium spp. from the endemic coral Mussismilia braziliensis - Luiz Felipe Benites; Arthur Weiss Silva-Lima; Inácio Domingos da Silva-Neto; Paulo Sergio Salomon (Symbiosis, 2018)

Polymorphisms in interleukins 17A and 17F genes and periodontitis: results from a meta-analysis - Felipe Rodolfo Pereira da Silva; Larissa dos Santos Pessoa; Any Carolina Cardoso Guimarães Vasconcelos; Weberson de Aquino Lima; Even Herlany Pereira Alves; Daniel Fernando Pereira Vasconcelos (Molecular Biology Reports, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Water quality, pollutant loads, and multivariate analysis of the effects of sewage discharges into urban streams of Southeast Brazil - Gerson Araujo de Medeiros; Ana Claudia Camargo de Lima Tresmondi; Brigida Pimentel Villar de Queiroz; Felipe Hashimoto Fengler; André Henrique Rosa; Joziane Martins Fialho; Renata Silva Lopes; Caio Villafanha Negro; Leandro Ferreira dos Santos; Admilson Irio Ribeiro (Energy, Ecology and Environment, 2017)

Cytotoxicity and genotoxicity of Guaribas river water (Piauí, Brazil), influenced by anthropogenic action - João Marcelo de Castro e Sousa; Ana Paula Peron; Louridânya da Silva e Sousa; Mércia de Moura Holanda; Ataíde de Macedo Vieira Lima; Vitor Alves de Oliveira; Felipe Cavalcanti Carneiro da Silva; Leonardo Henrique Guedes de Morais Lima; Leomá Albuquerque Matos; Sandra Maria Mendes de Moura Dantas; Raí Pablo Sousa de Aguiar; Muhammad Torequl Islam; et al. (Environmental Monitoring and Assessment, 2017)

Plant extracts as phytogenic additives considering intake, digestibility, and feeding behavior of sheep - Camila Sousa da Silva; Evaristo Jorge Oliveira de Souza; Gerfesson Felipe Cavalcanti Pereira; Edwilka Oliveira Cavalcante; Ewerton Ivo Martins de Lima; Thaysa Rodrigues Torres; José Ricardo Coelho da Silva; Daniel Cézar da Silva (Tropical Animal Health and Production, 2017)

Spineless cactus as a replacement for sugarcane in the diets of finishing lambs - Juliana Paula Felipe de Oliveira; Marcelo de Andrade Ferreira; Adryanne Marjorie Souza Vitor Alves; Ana Caroline Cerqueira de Melo; Ida Barbosa de Andrade; Juraci Marcos Alves Suassuna; Leonardo José Assis de Barros; Tobias Tobit de Barros Melo; Janaina de Lima Silva (Tropical Animal Health and Production, 2017)

Chemical composition and antimicrobial activity of the essential oils of Onychopetalum amazonicum R.E.Fr. - Bruna R. de Lima; Felipe M. A. da Silva; Elzalina R. Soares; Richardson A. de Almeida; Francinaldo A. da Silva Filho; Raimundo C. Pereira Junior; Álvaro J. Hernandez Tasco; Marcos J. Salvador; Hector H. F. Koolen; Afonso D. L. de Souza; Maria L. B. Pinheiro (Natural Product Research, 2016)

Effect of Sodium Fluoride on Bone Biomechanical and Histomorphometric Parameters and on Insulin Signaling and Insulin Sensitivity in Ovariectomized Rats - Rita de Cássia Alves Nunes; Fernando Yamamoto Chiba; Amanda Gomes Pereira; Renato Felipe Pereira; Maria Sara de Lima Coutinho Mattera; Edilson Ervolino; Mário Jefferson Quirino Louzada; Marília Afonso Rabelo Buzalaf; Cristina Antoniali Silva; Doris Hissako Sumida (Biological Trace Element Research, 2016)

Involvement of the GABAergic system in the anxiolytic effect of sulfated polysaccharides from the red seaweed Gracilaria cornea - Valdécio Silvano Monteiro; Felipe Barros Teles; Chistiane Oliveira Coura; Ricardo Basto Souza; Camila Nayane de Carvalho Lima; Deiziane Viana da Silva Costa; Eduardo Ribeiro Honório Junior; Sarah de Souza Escudeiro; Edna Maria Camelo Chaves; Silvânia Maria Mendes Vasconcelos; Norma Maria Barros Benevídes (Journal of Applied Phycology, 2016)

Effects of Sodium Arsenite and Arsenate in Testicular Histomorphometry and Antioxidants Enzymes Activities in Rats - Ana Cláudia Ferreira Souza; Sarah Cozzer Marchesi; Graziela Domingues de Almeida Lima; Rafael Penha Ferraz; Felipe Couto Santos; Sérgio Luis Pinto da Matta; Mariana Machado-Neves (Biological Trace Element Research, 2016)

The Pronociceptive Effect of Paradoxical Sleep Deprivation in Rats: Evidence for a Role of Descending Pain Modulation Mechanisms - Dabna H. Tomim; Felipe M. Pontarolla; Jessica F. Bertolini; Mauricio Arase; Glaucia Tobaldini; Marcelo M. S. Lima; Luana Fischer (Molecular Neurobiology, 2016)

Erratum to: Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Amanda Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

Ferulic acid chronic treatment exerts antidepressant-like effect: role of antioxidant defense system - Juliana Lenzi; Andre Felipe Rodrigues; Adriana de Sousa Rós; Bianca Blanski de Castro; Daniela Delwing de Lima; Débora Delwing Dal Magro; Ana Lúcia Bertarello Zeni (Metabolic Brain Disease, 2015)

ASR5 is involved in the regulation of miRNA expression in rice - Lauro Bücker Neto; Rafael Augusto Arenhart; Luiz Felipe Valter de Oliveira; Júlio Cesar de Lima; Maria Helena Bodanese-Zanettini; Rogerio Margis; Márcia Margis-Pinheiro (Plant Cell Reports, 2015)

Comparison of the tuberculin test, histopathological examination, and bacterial culture for the diagnosis of tuberculosis (Mycobacterium bovis) in buffaloes (Bubalus bubalis) in Brazil - Tatiane Teles Albernaz; Carlos Magno Chaves Oliveira; Danillo Henrique da Silva Lima; Natália da Silva e Silva; Douglas Pinheiro Cardoso; Cinthia Távora Albuquerque Lopes; Marilene de Farias Brito; Jenevaldo Barbosa da Silva; Felipe Masiero Salvarani; Rômulo Cerqueira Leite; José Diomedes Barbosa (Tropical Animal Health and Production, 2015)

A Metalloproteomics Study on the Association of Mercury With Breast Milk in Samples From Lactating Women in the Amazon Region of Brazil - Felipe André dos Santos; Bruna Cavecci; José Cavalcante Souza Vieira; Vanessa Pezza Franzini; Ademir Santos; Aline de Lima Leite; Marília Afonso Rabelo Buzalaf; Luiz Fabrício Zara; Pedro de Magalhães Padilha (Archives of Environmental Contamination and Toxicology, 2015)

Chemical composition and antimicrobial evaluation of the essential oils of Bocageopsis pleiosperma Maas - Elzalina R. Soares; Felipe M.A. da Silva; Richardson A. de Almeida; Bruna R. de Lima; Hector H.F. Koolen; Caroline C. Lourenço; Marcos J. Salvador; Adriana Flach; Luiz Antonio M. A. da Costa; Antonia Q.L. de Souza; Maria L.B. Pinheiro; Afonso D.L. de Souza (Natural Product Research, 2015)

Combining ALOS/PALSAR derived vegetation structure and inundation patterns to characterize major vegetation types in the Mamirauá Sustainable Development Reserve, Central Amazon floodplain, Brazil - Jefferson Ferreira-Ferreira; Thiago Sanna Freire Silva; Annia Susin Streher; Adriana Gomes Affonso; Luiz Felipe de Almeida Furtado; Bruce Rider Forsberg; João Valsecchi; Helder Lima Queiroz; Evlyn Márcia Leão de Moraes Novo (Wetlands Ecology and Management, 2015)

Physico-chemical quality parameters of herbal products from Agave sisalana - Alexsandra Conceição Apolinário; Morgana Lopes do Nascimento; Juliana Patrícia de Luna Vieira; Camila de Oliveira Melo; Felipe Fernandes Santos; Bolívar Ponciano Goulart de Lima Damasceno; Attilio Converti; Adalberto Pessoa; José Alexsandro da Silva (Natural Product Research, 2014)

Contrasting spatial genetic structure in Annona crassiflora populations from fragmented and pristine savannas - Rosane G. Collevatti; Mariana P. C. Telles; Jacqueline S. Lima; Felipe O. Gouveia; Thannya N. Soares (Plant Systematics and Evolution, 2014)

Daily variations in the thermoregulatory behaviors of naked neck broilers in an equatorial semi-arid environment - João Paulo Araújo Fernandes de Queiroz; João Batista Freire de Souza; Hiagos Felipe Ferreira de Lima; Monik Kelly de Oliveira Costa; Leonardo Lelis de Macedo Costa; Alex Martins Varela de Arruda (International Journal of Biometeorology, 2014)

The first report on flavonoid isolation from Annona crassiflora Mart - Gisele Avelar Lage; Felipe da Silva Medeiros; Werônica de Lima Furtado; Jacqueline Aparecida Takahashi; José Dias de Souza Filho; Lúcia Pinheiro Santos Pimenta (Natural Product Research, 2014)

Differential effects of paradoxical sleep deprivation on memory and oxidative stress - Alisson Menezes Araujo Lima; Veralice Meireles Sales de Bruin; Emiliano Ricardo Vasconcelos Rios; Pedro Felipe Carvalhedo de Bruin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

First detection of adenovirus in the vampire bat (Desmodus rotundus) in Brazil - Francisco Esmaile de Sales Lima; Samuel Paulo Cibulski; Felipe Elesbao; Pedro Carnieli Junior; Helena Beatriz de Carvalho Ruthner Batista; Paulo Michel Roehe; Ana Cláudia Franco (Virus Genes, 2013)

How long does it take to achieve steady state for an accurate assessment of resting $$ \dot{\text{V}}{\text{O}}_{2} $$ in healthy men? - Felipe A. Cunha; Adrian W. Midgley; Walace Monteiro; Raul Freire; Tainah Lima; Paulo T. V. Farinatti (European Journal of Applied Physiology, 2013)

Increasing antibiotic activity against a multidrug-resistant Acinetobacter spp by essential oils of Citrus limon and Cinnamomum zeylanicum - Felipe Queiroga Sarmento Guerra; Juliana Moura Mendes; Janiere Pereira de Sousa; Maria F.B. Morais-Braga; Bernadete Helena Cavalcante Santos; Henrique Douglas Melo Coutinho; Edeltrudes de Oliveira Lima (Natural Product Research, 2012)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

1-(7-Chloroquinolin-4-yl)-2-[(1H-pyrrol-2-yl)methylene]hydrazine: a potent compound against cancer - Raquel Carvalho Montenegro; Letícia Veras Lotufo; Manoel Odorico de Moraes; Cláudia do Ó. Pessoa; Felipe Augusto Rocha Rodrigues; Marcelle de Lima Ferreira Bispo; Camila Cataldi de Alcantara; Carlos Roland Kaiser; Marcus Vinícius Nora de Souza (Medicinal Chemistry Research, 2012)

Chronic methylphenidate administration alters antioxidant defenses and butyrylcholinesterase activity in blood of juvenile rats - Felipe Schmitz; Emilene Barros da Silva Scherer; Maira Jaqueline da Cunha; Aline Andrea da Cunha; Daniela Delwing Lima; Débora Delwing; Carlos Alexandre Netto; Angela Terezinha de Souza Wyse (Molecular and Cellular Biochemistry, 2012)

Acute hyperhomocysteinemia alters the coagulation system and oxidative status in the blood of rats - Aline A. da Cunha; Emilene Scherer; Maira J. da Cunha; Felipe Schmitz; Fernanda R. Machado; Daniela D. Lima; Débora Delwing; Angela T. S. Wyse (Molecular and Cellular Biochemistry, 2012)

Levels of copper in Nile tilapia from Brazil - Renato C.F. Neves; Paula M. Moraes; Jeisson E.M. Ferrari; Paula M. Lima; Felipe A. Santos; Gustavo Rocha de Castro; Margarida M. Barros; Pedro M. Padilha (Food Additives & Contaminants Part B-Surveillance, 2011)

Epidemiological and histological components of crown rust resistance in oat genotypes - Felipe André Sganzerla Graichen; José Antônio Martinelli; Caroline de Lima Wesp; Luis Carlos Federizzi; Márcia Soares Chaves (European Journal of Plant Pathology, 2011)

Simultaneous phenanthrene and cadmium removal from contaminated soil by a ligand/biosurfactant solution - Tânia M. S. Lima; Lorena C. Procópio; Felipe D. Brandão; André M. X. Carvalho; Marcos R. Tótola; Arnaldo C. Borges (Biodegradation, 2011)

Early Post-Natal Iron Administration Induces Astroglial Response in the Brain of Adult and Aged Rats - Liana Lisboa Fernandez; Maria Noêmia Martins de Lima; Felipe Scalco; Gustavo Vedana; Clívia Miwa; Arlete Hilbig; Mônica Vianna; Nadja Schröder (Neurotoxicity Research, 2011)

Biodegradability of bacterial surfactants - Tânia M. S. Lima; Lorena C. Procópio; Felipe D. Brandão; André M. X. Carvalho; Marcos R. Tótola; Arnaldo C. Borges (Biodegradation, 2011)

Neonatal Iron Treatment Increases Apoptotic Markers in Hippocampal and Cortical Areas of Adult Rats - Clivia Pazin Miwa; Maria Noêmia Martins de Lima; Felipe Scalco; Gustavo Vedana; Raquel Mattos; Liana Lisboa Fernandez; Arlete Hilbig; Nadja Schröder; Monica R. M. Vianna (Neurotoxicity Research, 2011)

Assessing the variability of Brazilian Vaccinia virus isolates from a horse exanthematic lesion: coinfection with distinct viruses - Rafael K. Campos; Mário C. S. Brum; Carlos E. W. Nogueira; Betânia P. Drumond; Pedro A. Alves; Larissa Siqueira-Lima; Felipe L. Assis; Giliane S. Trindade; Cláudio A. Bonjardim; Paulo C. Ferreira; Rudi Weiblen; Eduardo F. Flores; et al. (Archives of Virology, 2011)